The ordinary life of exceptional justice : procedural law in transition - Muñoz, Anamaria (Institut d'études politiques de Paris - Sciences Po, 2026)
This dissertation interrogates the extraordinary character of transitional justice as a legal project. My central claim is that treating procedure as dispensable in pursuit of expansive transformative goals is a disservice to the project itself. The prevailing assumption among scholars and practitioners has been that the existential battles of a transition are fought and won at the macro level: in the text of peace agreements, in constitutional amendments, or in grand normative commitments to truth, justice, and reparation. I show that some of the most consequential distributions of power take place elsewhere: in the granular procedural rules that govern how tribunals operate in practice. Procedural analysis serves here as both method and argument, disaggregating legal rules to reveal who bears costs and who captures benefits, and exposing how procedural opacity creates space for alternative sources of law to emerge. I contend that the exception in exceptional justice should not extend to procedural rigor, and that holding transitional tribunals to the same standards as any other apex court is not a limitation on what transitional justice can achieve, but the condition under which its achievements can be considered legitimate. Taken together, these moves advance a broader theoretical claim: that transitional justice sustains and reinforces the very same distributive arrangements as ordinary justice, rather than disrupting them. I develop these arguments by examining transitional justice in the Colombian 2016 peace process - one of the few ongoing transitional justice processes in the world, and therefore an important site for observing the legal project of transition in motion rather than in retrospect. I engage with Colombia as a matter of epistemic justice: my political commitment is that Latin America is not merely a recipient of international legal frameworks developed elsewhere but an important site in their production. I do not take Colombia as my object because it is exceptional. I take it because the claim that it is, and what that claim conceals, is precisely what this dissertation contests. Cette thèse interroge le caractère extraordinaire de la justice transitionnelle en tant que projet juridique. Mon argument central est que traiter la procédure comme accessoire, au nom d'objectifs transformateurs ambitieux, dessert le projet lui-même. L'hypothèse dominante a été que les batailles décisives d'une transition se gagnent au niveau macro : dans les accords de paix, les réformes constitutionnelles, les grands engagements normatifs en faveur de la vérité et de la réparation. Je montre que certaines des distributions de pouvoir les plus importantes se jouent ailleurs : dans les règles procédurales qui gouvernent le fonctionnement concret des tribunaux. L'analyse procédurale est ici à la fois méthode et argument : elle désagrège les règles juridiques pour révéler qui supporte les coûts et qui capte les bénéfices, et met en évidence comment l'opacité procédurale crée un espace pour l'émergence de sources alternatives du droit. Je soutiens que l'exception dans la justice exceptionnelle ne devrait pas s'étendre à la rigueur procédurale, et que soumettre les tribunaux transitionnels aux mêmes exigences que tout autre tribunal de rang supérieur n'est pas une limite à ce que la justice transitionnelle peut accomplir, mais la condition sous laquelle ses accomplissements peuvent être considérés comme légitimes. Ces arguments avancent une thèse théorique plus large : la justice transitionnelle maintient et renforce les mêmes distributions que la justice ordinaire, plutôt que de les remettre en cause. Je les développe en examinant le processus de paix colombien de 2016 - terrain privilégié pour observer la transition en train de se faire. J'aborde la Colombie comme une question de justice épistémique : l'Amérique latine n'est pas simplement destinataire de cadres juridiques élaborés ailleurs, mais un lieu important de leur production.
Issue: 2026IEPP0015
Keywords: Courts; Criminal law; Droit procédural; Droit pénal; Justice transitionnelle; Procedural law; Transitional justice; Tribunaux

Access to social rights for temporary labour migrant women in the EU : an intersectional perspective on seasonal and posted workers in France and Spain - Deverson, Audrey (Université de Strasbourg, 2026)
Temporary labour migration constitutes both a historical phenomenon and an enduring central issue within the European Union. This thesis adopts a socio-legal approach to analyse the cases of France and Spain, focusing on seasonal work and posting of workers in the agricultural sector. It examines the experiences of temporary migrant women workers at the intersection of migration law and labour and social security law, in particular with regard to social security. Drawing on an intersectional perspective articulated around the concept of vulnerability, this research highlights the structuring role of law in these women’s experiences. This thesis demonstrates that the applicable legal framework contributes to reinforcing their vulnerability by establishing a system of exclusion and invisibilisation based on migration status, employment status and a gendered and racialised labour division, thereby limiting these women’s effective access to rights linked to their participation in the labour market, such as unemployment benefits, as well as to those relating to their reproductive lives. La migration temporaire de travail constitue à la fois un phénomène historique et un enjeu toujours central au sein de l’Union européenne. Cette thèse analyse, dans une perspective sociojuridique, les cas de la France et de l’Espagne, en se concentrant sur le travail saisonnier et le travail détaché dans le secteur agricole. Elle examine l’expérience des travailleuses migrantes temporaires à l’intersection du droit des migrations et du droit social, notamment en matière de sécurité sociale. Mobilisant une perspective intersectionnelle articulée au concept de vulnérabilité, cette recherche met en lumière le rôle structurant du droit dans l’expérience de ces femmes. La thèse démontre que le cadre juridique applicable contribue à renforcer leur situation de vulnérabilité en instaurant un système d’exclusion et d’invisibilisation fondé sur le statut migratoire, le statut d’emploi, et une division du travail genrée et racialisée, limitant ainsi l’accès effectif de ces femmes aux droits liés à leur participation au marché du travail, tels que le droit au chômage, ainsi qu’à ceux relatifs à leur vie reproductive.
Keywords: Agriculture; Approches sociojuridiques; Droit au chômage; Droit de l’UE; Droits économiques et sociaux; Espagne; European Union law; France; Intersectionality; Intersectionnalité; Justice reproductive; Migration temporaire de travail; Pays de l'Union européenne; Posting of workers; Protection sociale; Reproductive justice; Seasonal work; Social protection; Socio-Legal studies; Spain; Statut juridique; Temporary labour migration; Travail détché; Travail saisonnier; Travailleuses étrangères; Unemployment benefits; Vulnerability; Vulnérabilité; Émigration et immigration

Artificial Intelligence of Everything (AIoE) in energy sectors : cybersecurity, data protection, and data localization - Mohaghegh Montazeri, Leila (Université de Montréal, 2026)
L'Internet est devenu une partie essentielle de la vie moderne. Un développement important est «l'Internet des objets» (IoT), qui connecte des dispositifs physiques à Internet. Plus récemment, un concept plus large est apparu: «l'Internet de tout» (IoE), intégrant quatre composantes, les personnes, les processus, les données et les objets. L'ajout de l'intelligence artificielle (IA) à l'IoE a donné naissance à «l'Intelligence Artificielle de Tout» (IAdT). Cette combinaison offre des avantages significatifs pour le secteur de l'énergie en optimisant la production, la distribution et la consommation d'énergie. Cependant, elle soulève également des défis critiques en matière de protection des données, de cybersécurité et de localisation des données. Dans cette thèse, j'explore comment les gouvernements et les entreprises énergétiques peuvent collaborer pour répondre aux risques liés à la confidentialité et à la cybersécurité des technologies IAdT. J'analyse également les exigences de localisation des données et j'examine les cadres réglementaires pertinents, en particulier au sein de l'Union européenne (avec un accent sur l'Irlande) et au Canada (y compris la province de l'Ontario). The Internet has become an essential part of modern life. One significant development is the “Internet of Things” (IoT), which connects physical devices to the Internet. More recently, a broader concept has emerged: the “Internet of Everything” (IoE), which integrates four key components: people, processes, data, and things. The addition of artificial intelligence (AI) to IoE has given rise to the "Artificial Intelligence of Everything" (AIoE). This combination offers significant benefits to the energy sector by optimizing energy production, distribution, and consumption. However, it also introduces critical challenges related to data protection, cybersecurity, and data localization. In this thesis, I explore how governments and energy companies can collaborate to address privacy and cybersecurity risks associated with AIoE technologies. I also analyze data localization requirements and review relevant regulatory frameworks, particularly within the European Union (with a focus on Ireland) and Canada (including the province of Ontario).
Intelligence Artificielle du Tout (AIoE) dans les secteurs de l’énergie : Cybersécurité, protection des données et localisation des données
Keywords: Artificial Intelligence; Artificial Internet of Everything (AIoE); Cybersecurity; Cybersécurité; Data Localization; Data Protection; Energy Industry; Intelligence artificielle; Internet artificiel de tout; Internet des objets; Internet of Things (IoT); Localisation des données; Protection des données; Secteur de l’énergie

Social media and structural injustice : a critical analysis of EU platform regulation - Griffin, Rachel (Institut d'études politiques de Paris - Sciences Po, 2025)
Cette thèse examine le traitement par la régulation européenne de la problématique des injustices structurelles sociales liées aux grands réseaux sociaux. Pour ce faire, elle opère une synthèse de nombreuses recherches empiriques qui mettent en évidence les inégalités dans la gouvernance des contenus, et s'appuie sur des perspectives théoriques tirées de la philosophie politique, de la théorie juridique féministe, et des recherches en droit et économie politique. Elle présente trois lignes d'argumentation principales. Premièrement, le droit européen n'empêche pas les injustices telles que la discrimination dans la modération, les violences en ligne, ou la visibilité inégale des différents groupes sociaux, parce qu'il conceptualise ces inégalités d'une manière individualiste et formaliste, visant à protéger les droits d'individus particuliers et à assurer l'application des règles prédéfinies, tout en ignorant la nature systémique des inégalitésDeuxièmement, le droit contribue souvent activement aux injustices : par exemple, en permettant aux agences policières de demander la suppression des contenus pour des raisons politiques. Troisièmement, les aspects du cadre réglementaire qui sont perçus comme les plus à même de combattre les inégalités systémiques, à savoir les obligations autour de la gestion des risques et les principes des droits de l'homme, se révèlent en réalité peu capables d'empêcher les injustices structurelles. Ces deux éléments restent en effet inscrits dans un paradigme de régulation technocratique, dépolitisée, et favorable au marché, et excluent toute contestation réelle du pouvoir ou des pratiques commerciales des plateformes de « big tech ». This thesis analyses EU regulation of social media content governance, focusing on how the law addresses the impacts of the largest platforms on structural social injustice. To do so, it draws on theoretical perspectives from political philosophy, feminist and queer legal theory, and law and political economy, and synthesises a wide range of empirical scholarship that illuminates the unjust impacts of social media platforms' content governance. It makes three main arguments.First, EU law cannot effectively address unjust impacts - such as discriminatory content moderation, online violence, or the unequal visibility of different social groups - because it regulates them in a highly individualistic and formalistic way, focused on protecting individual rights and consistently applying predefined rules, which overlooks systemic inequalities and their connections to underlying political-economic structures. Second, moreover, the law often actively contributes to injustice: for example, by excluding minority perspectives from platform governance, or by making it easier for state institutions to target politically disfavoured content for removal. Third, the two aspects of the legal framework which are widely seen by experts as the most promising levers to address systemic inequalities and power disparities - risk management obligations, and human rights principles - are also incapable of counteracting these problems. They remain limited by a technocratic, depoliticised and marketised regulatory paradigm, which excludes genuine political contestation of the power of 'big tech' platforms to organise online content in line with their own commercial interests.
Issue: 2025IEPP0034
Keywords: Digital law; Droit des technologies de l'information et de la communication; Droit européen; Droit numérique; Eu law; Feminism; Féminisme; Platform regulation; Régulation des plateformes; Réseaux sociaux

An evaluation of China’s securitization regulatory system - Cao, Lei (Université de Montréal, 2025)
Since its innovation as a modern financial product in the 1970s, securitization has swept the global financial market. In 2000s, in order to ease China’s concentrated debt risks in the banking system and to improve the country’s imbalanced financial system, the Chinese government started to promote a trial program of securitization. An associated regulatory system was then created to facilitate the development of the Chinese securitization markets. Unlike regulations drafted and applied in North America, where an ex-ante regulatory analysis procedure and an ex-post evaluation system are installed, the current Chinese securitization regulation system is built mainly upon a basis of trial and interim rules. In other words, Chinese regulations regarding securitization were not comprehensively assessed before their adoption and there has been no systemic ex-post evaluation of the current securitization regulatory system in the past 20 years. This raises the question of whether the Chinese securitization regulation system facilitates the achievement of its regulatory objectives. The author purports to answer this question using three tools: The theory of regulation, legal historical analysis of law, and comparative law. To begin the analysis, the author designs an analytical framework based on the theory of regulation to evaluate Chinese regulations on securitization. In this evaluative framework, perspectives and criteria are stipulated to guide and draw the boundary of the evaluation. While applying the analytical framework, the author reviews the development of the Chinese securitization regulatory system over the past 20 years. The author studies the historical context of regulations established and regulatory modifications adopted in order to assess whether the logic embedded in the current Chinese securitization regulatory system is still valid. To better evaluate the Chinese securitization regulatory system, the author also applies a micro comparison of certain Chinese securitization regulations with their counterparts in North America. The purpose of this comparison is also to understand whether the Chinese characteristics in Chinese securitization regulations facilitate the achievement of its regulatory objectives. At the end of this assessment, the author provides a report to find the merits and disadvantages of Chinese securitization regulatory system. Due to the evaluative nature of this research, no demonstrated solutions are proposed in this report. Depuis sa création dans les années 1970, la titrisation s’est répandue à travers le marché financier mondial. Dans les années 2000, le gouvernement chinois a commencé à promouvoir le programme de titrisation afin d'atténuer les risques liés à la concentration de la dette dans le système bancaire et d'améliorer un système financier déséquilibré. La règlementation associée a été mise en place pour faciliter le développement du marché chinois de la titrisation. Contrairement aux régles créées et appliquées en Amérique du Nord, qui suivent une analyse ex ante —c’est-à-dire avant leur adoption — et une évaluation ex post — soit après leur application pendant une certaine période, le système de réglementation de la titrisation actuellement en vigueur en Chine a été élaboré sur la base d’essais et de mesures provisoires. Autrement dit, la Chine ne s’est pas fondée sur une analyse ex ante approfondie, et n’a mené aucune évaluation systémique ex post de ses réglementations de la titrisation au cours des vingt dernières années. Ce système chinois de réglementation de la titrisation facilite-t-il ou non la réalisation de ses objectifs réglementaires ? L'auteur tente de répondre à cette question à partir de trois outils : la théorie de la réglementation, l’analyse historique du droit et le droit comparé. Pour commencer, l’auteur conçoit un cadre analytique basé sur la théorie de la réglementation pour évaluer les dispositions chinoises en matière de titrisation. Dans ce cadre d’évaluation, des perspectives et des critères sont proposés pour guider et délimiter l’évaluation. À la lumière de ce cadre analytique, l’auteur replace la réglementation chinoise de la titrisation dans son contexte historique et retrace les modifications apportées au cours de deux dernières décennies. Il s’agit ainsi d’évaluer si la logique qui a présidé à l’adoption de ces règles reste valide dans le contexte actuel. Mais pour mieux saisir les caractéristiques de la réglementation chinoise de la titrisation, l’auteur ajoute à cette analyse historique interne à la Chine des micro-comparaisons de la titrisation chinoise et de ses règles avec leurs homologues nord-américains dans différentes sections de cette thèse. C’est ainsi qu’il sera possible de voir si les caractéristiques chinoises de la réglementation en matière de titrisation facilitent ou non la réalisation de ses objectifs. Au terme de cette recherche évaluative, l’on proposera un rapport qui mettra en lumière les avantages et les inconvénients du système chinois. En raison de sa nature évaluative, cette thèse ne proposera aucune solution aux inconvénients repérés.
Keywords: China; Chine; Evaluation of Chinese; Financial Regulation; Marchés chinois; Réglementation financière; Securitization; Securitization Markets; Securitization Regulation; Titrisation; Titrisation (réglementation)

Predictive Artificial Intelligence Tools in the U.S. Criminal Trial : Reflections on Technology and Justice - Ilhan, Mina Ayşe (Université Côte d'Azur, 2025)
Under the aegis of efficiency and neutrality, algorithmic risk-assessment tools have been rapidly inserted into the realm of pretrial justice, promising scientific and objective prediction where presumption of innocence and scarce resources are pitted against each other. Their sprawl has been uneven and confined to looser pretrial rules than would govern similar proof at trial. These systems translate miscellaneous data into scores of “risk,” inviting courts to act on what might happen rather than on what has been proven, within a process already plagued by plea bargaining, racial disparity, and institutional asymmetry. This thesis argues that such tools do not merely constitute information about the defendant; they reorder what counts as usable knowledge and who is treated as a credible knower at the weakest stage of a criminal process. The thesis lays out how scores interact with judicial decision-making; how ostensibly neutral inputs (criminal history, prior contacts, residence, employment) can re-encode social disadvantage; and how opacity and trade-secret claims frustrate fundamental rights such as due process. The doctrinal analysis clarifies the boundary between regulation and punishment under United States v. Salerno, the demands of proportionality, and the significance of the presumption of innocence when decisions are predictive. A brief technical account explains why claims of “explainability” often exceed what such models can reliably demonstrate for legal purposes, but the core argument is juridical: claims of legitimacy must be substantiated by enforceable safeguards; falling short of that, systems described as ‘explainable' or ‘fair' remain as fancy adjectives. The thesis contends that the safeguards that govern the trial must be applied earlier in the criminal process, where liberty is already fragile. Accordingly, the thesis argues for invoking evidentiary rules early on: demonstrating reliability of the tools; reasoned judicial decisions that explain how any score was weighed against case-specific facts; meaningful opportunities for defence challenge; and, where appropriate, access to independent expertise to translate model outputs without displacing judicial authorship. The researcher is of the opinion that these emphases are necessary so that pretrial decisions remain individualised and proportionate and detention retains its status as an exceptional, non-punitive measure. Finally, it defends doubt as a juridical virtue, a disciplined moment of pause that reins in the allure of algorithmic certainty and reasserts judicial responsibility, so that the presumption of innocence and liberty remains the rule even in a predictive age. Sous l'égide de l'efficacité et de la neutralité, les outils algorithmiques d'évaluation du risque ont été rapidement introduits dans le domaine de la justice pré-procès, promettant une prédiction scientifique et objective là où la présomption d'innocence et la rareté des ressources se trouvent mises en tension. Leur déploiement a été inégal et s'est inscrit dans des règles pré-procès plus souples que celles qui régiraient des éléments de preuve similaires au stade du procès. Ces systèmes traduisent des données hétérogènes en scores de « risque », invitant les juridictions à agir en fonction de ce qui pourrait advenir plutôt que de ce qui a été prouvé, au sein d'un processus déjà marqué par le plaider-coupable, les disparités raciales et les asymétries institutionnelles. La présente thèse soutient que de tels outils ne constituent pas seulement une information relative au prévenu ; ils réorganisent ce qui compte comme connaissance mobilisable et déterminent qui est traité comme un sujet crédible de savoir au stade le plus fragile de la procédure pénale. Elle expose la manière dont les scores interagissent avec la prise de décision judiciaire ; comment des variables présentées comme neutres (antécédents judiciaires, contacts antérieurs avec la police, résidence, emploi) peuvent réencoder des désavantages sociaux ; et comment l'opacité ainsi que les revendications de secret commercial entravent des droits fondamentaux tels que le droit à une procédure régulière. L'analyse doctrinale précise la frontière entre régulation et punition au regard de l'arrêt United States v. Salerno, les exigences de proportionnalité et la portée de la présomption d'innocence lorsque les décisions sont de nature prédictive. Un bref exposé technique explique pourquoi les prétentions à « l'explicabilité » excèdent souvent ce que ces modèles peuvent démontrer de manière fiable à des fins juridiques, mais l'argument central demeure juridique : les revendications de légitimité doivent être étayées par des garanties effectives ; à défaut, les systèmes qualifiés d'« explicables » ou d'« équitables » ne demeurent que des adjectifs séduisants. La thèse soutient que les garanties gouvernant le procès doivent être appliquées plus en amont dans le processus pénal, là où la liberté est déjà fragile. En conséquence, elle plaide pour une mobilisation précoce des règles de preuve : démonstration de la fiabilité des outils ; décisions judiciaires motivées expliquant la manière dont tout score a été mis en balance avec les faits propres à l'affaire ; possibilités effectives de contestation par la défense ; et, le cas échéant, accès à une expertise indépendante permettant de traduire les résultats des modèles sans se substituer à l'autorité judiciaire. La chercheuse estime que ces exigences sont nécessaires afin que les décisions pré-procès demeurent individualisées et proportionnées, et que la détention conserve son caractère exceptionnel et non punitif. Enfin, la thèse défend le doute comme une vertu juridique, moment discipliné de suspension qui tempère l'attrait de la certitude algorithmique et réaffirme la responsabilité judiciaire, afin que la présomption d'innocence et la liberté demeurent la règle, y compris à l'ère prédictive.
Issue: 2025COAZ0023
Keywords: Algorithmes; Algorithmes predictifs; Algorithms; Criminal Justice; Intelligence artificielle en droit; Justice criminelle; Justice prédictive; Procès; Risk assessment tools; États-Unis

A framework for bank resolution in Namibia - Eiseb, Bryan Karl Gunther (University of Pretoria, 2025)
Banks are regarded as special financial institutions because, apart from the various critical intermediary and other functions they fulfil in a financial system, the hallmark of their business models is receiving deposits from the public and using such deposits for extending loans against interest from which they make profit. Unlike other companies, banks are however vulnerable to loss of public confidence and remain exposed to various risks and failure. Banks are thus critically important actors in domestic and global financial systems, - thus their safety is critical to the maintenance of financial stability. As a result, banks are subject to stringent regulation and supervision to ensure their safety. Despite prudential regulation, the failure of banks remains a reality. If the risk of bank failure is not adequately addressed through appropriate regulation and supervision, , it may result in a financial crisis like the 2008 Global Financial Crisis (2008 GFC). Because banks play a special role in an economy and their failure may have an adverse impact on financial stability and depositors, this thesis aligns with the view expressed by academics and international organisations that there is a need for a special regime (lex specialis) to deal with the failure of banks since normal insolvency procedures are not suitable for this purpose. f. This is because bank failures require swift, timely intervention by a supervisor to resolve failing banks in an orderly and optimal manner to ensure the maintenance of financial stability, depositor protection and relegating bailouts with taxpayers’ money as a last resort. A very notable lesson that emanated from the 2008 GFC is the criticality of special resolution frameworks for banks; the need to balance the interests of shareholders, creditors, and depositors, while promoting financial stability objectives. As a result, the need for special resolution frameworks for banks which empowers Resolution Authorities with adequate resolution tools and powers to resolve a failing bank timeous and orderly , has become a legislative imperative in contemporary financial systems. To deal with bank failures in Namibia, the Banking Institutions Act, 2 of 1998 (the BIA 1998) contained provisions that allowed for the assumption of control and liquidation of a failed bank. However, the newly enacted Banking Institution Act 13 of 2023 (the BIA 2023 which repealed the BIA 1998) has changed that position and introduced a single provision in section 70 that provides for bank resolution. Until now, prior to the introduction of this very new statutory provision, all bank failures in Namibia were dealt with under the limited supervisory tools of the BIA 1998. This study seeks to determine whether section 70 of the BIA 2023, is sufficiently aligned with international best practice as captured in the Financial Stability Board’s Key Attributes of Effective Resolution Regimes for Financial Institutions (FSB KAs), issued in 2011, as updated in 2014 and 2024. Alternatively, if the regime introduced by the BIA 2023 does not adequately align with the FSB KAs it is then considered whether the new Namibian bank resolution framework requires to be strengthened further to better align it with the FSB KAs. To consider possible further reforms to the new Namibian bank resolution regime, this thesis considers the resolution frameworks in Germany and Nigeria by way of comparative studies to observe best practices.
Keywords: Bank; Financial stability; Key Attributes; Namibia; Resolution

A comparative statutory analysis of the causes of bank failures in Zimbabwe - Tsaura, Oscar (North-West University, 2025)
Zimbabwean financial sector has experienced significant periods of financial distress as depicted by numerous bank failures since 1980. Bank failure occurs when a financial institution experiences significant financial distress, rendering it incapable of fulfilling its obligations to depositors, shareholders and other stakeholders. In other words, bank failure is when a financial institution undergoes substantial financial distress rendering it unable to meet its obligations as they become due. In this thesis, the researcher adopted the definition of bank failure which refers to a situation where a bank is in financial distress and is recapitalised either by the central bank or a strategic investor, acquired by another institution, surrenders its license or the license is suspended, or it closes its operations altogether. This thesis reveals that in Zimbabwe bank failures can be attributed to various factors including the failure of regulatory and supervisory systems to detect irregularities in the operations of banking institutions. In addition, poor corporate governance practices such as inadequate oversight, inexperienced management, undue influence by dominant shareholders, nonperforming loans, excessive risk-taking, abusive related party transactions and noncompliance with laws are commonly cited as causes of bank failures in Zimbabwe. Bank failures often pose negative implications to the banking sector and banking stakeholders such as depositors and investors. This owes to the fact that banks serve as intermediaries that facilitate the avenues for deposits and extend credit services to individuals and the production sector of the economy. It is submitted that the proper functioning of banks requires effective and adequate regulatory supervision. Failure to provide robust and effective regulation of banks could lead to bank failures. This thesis presents a comparative analysis of the banking statutory framework of Zimbabwe and those of the UK and South Africa to determine if the banking laws in Zimbabwe are robust enough to prevent bank failures. The thesis reveals that the banking statutory framework in Zimbabwe is not robust enough to curb bank failures in times of stress because it lacks effective regulatory oversight. This thesis further reveals that poor banking regulation, inconsistent enforcement, weak regulatory insolvency procedures, and inadequate supervision framework are some of the weaknesses in the current banking statutory framework which needs to be rectified in order to combat bank failures effectively in Zimbabwe. The Banking Act does not fully incorporate the international best standards on bank supervision to prevent bank failures. Consequently, the banking statutory framework in Zimbabwe does not comprehensively and effectively provide for the prevention of bank failures like those of the UK and South Africa. The robustness of the banking statutory framework is in providing adequate and effective regulatory provisions and enforcement mechanisms that curb bank failures in Zimbabwe. The researcher proposes the adoption of a new model, the Zimbabwean twin peaks model, comprising the Zimbabwean Prudential Regulatory Authority and the Zimbabwean Financial Sector Conduct Authority. It is argued that if the adoption of the twin peaks model is considered and robustly implemented, it can prevent the causes of bank failures in Zimbabwe.
Keywords: Bank failure; Banking legislation; Banking statutory framework; Banks; Curatorship; Financial regulations; Financial stability; Fraud; Money laundering; Political instability; Zimbabwe

From trustworthy AI to technical standards : The distinctive European approach to artificial intelligence regulation - Gornet, Mélanie (Institut polytechnique de Paris, 2025)
L'Europe a été à l'avant-garde de l'éthique de l'intelligence artificielle (IA), en élaborant des chartes et des principes non contraignants sur l'IA « digne de confiance ». Le terme « digne de confiance » est utilisé par l'Europe pour désigner les systèmes d'IA qui sont « éthiques », « légaux » et « techniquement robustes ». L'Europe a complété ces principes non contraignants par un texte de loi sur l'IA, connu sous le nom de règlement sur l'IA, ou AI Act. Le règlement sur l'IA est l'un des premiers cadres légaux au monde à réglementer les systèmes d'IA dans différents secteurs et cas d'utilisation, en mettant l'accent sur la sécurité et la protection des droits fondamentaux. Pour les questions opérationnelles, le règlement sur l'IA s'appuie principalement sur des normes techniques en cours d'élaboration. L'approche européenne combine donc trois niveaux d'instruments réglementaires : les chartes éthiques de l'IA, le règlement sur l'IA et les normes techniques.L'approche par la normalisation est traditionnelle dans le domaine de la sécurité des produits, mais dans le règlement sur l'IA, les normes sont également censées répondre aux préoccupations en matière de droits fondamentaux. Pour éviter de faire des choix normatifs difficiles, les organismes de normalisation jouent la carte de la sécurité en élaborant des normes qui restent à un niveau élevé. De plus, dans le cadre du règlement sur l'IA, la responsabilité de l'élaboration des normes techniques est déléguée à des organismes de normalisation privés, où les grandes entreprises multinationales sont surreprésentées et exercent une influence considérable. Ces normes sont également généralement payantes, bien que la situation puisse évoluer dans les années à venir après une récente jurisprudence de la Cour de justice de l'Union européenne. Les experts en normalisation sont donc sous pression pour fournir des normes à temps et de bonne qualité. Europe has been at the forefront of Artificial Intelligence (AI) ethics, developing non-binding charters and principles on "trustworthy'' AI. The term "trustworthiness'' is used by Europe to designate AI systems that are "ethical'', "legal'' and "technically robust''. Europe has supplemented these non-binding principles with a binding regulation on AI, known as the AI Act. The AI Act is one of the world's first comprehensive frameworks for regulating AI systems across different industries and use cases, focusing on safety and protection of fundamental rights. The AI Act relies, for operational questions, mostly on technical standards that are in the course of development. The European approach thus combines three layers of regulatory instruments: AI ethics charters, the AI Act and technical standards.The standardisation approach is traditional in product safety, but under the AI Act, standards are also expected to address fundamental rights concerns. To avoid making hard normative choices, standardisation organisations are playing it safe, developing standards which remain at a high-level. Moreover, under the AI Act, the responsibility for developing technical standards is delegated to private standardisation bodies, where large multinational companies are over-represented and hold significant influence. These standards are also often locked behind paywalls, although the situation may evolve in the coming years after a recent case law from the Court of Justice of the European Union. Standardisation experts therefore face pressures to deliver standards on time and of good quality.
Keywords: AI Act; Apprentissage machine; Artificial Intelligence; Ethics; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Machine learning; Normes techniques; Regulation; Règlement IA; Régulation; Technical standards; Éthique

Essays on banking and society - Heyert, Axelle (Université de Strasbourg, 2025)
This dissertation examines the relationship between banking and society. It contributes to a better understanding of how banking affects society and, in turn on how society shapes banking practices. The first chapter studies the impact of inflation on trust in banks. Chapter two deals with the effect of trust in banks on financial inclusion. The third chapter investigates whether financial inclusion influences life satisfaction. Chapter four delves into how female bank leadership affects firm credit. The final chapter focuses on the influence of bank leaders’ age on sustainable lending. Overall, this dissertation highlights the important role of banks in societal development and the major influence of society in shaping banking practices.
Keywords: ACCESS TO CREDIT; Accès au crédit; Banking; Banks; Banques; Bonheur; Confiance; Financial inclusion; Gender; Genre; Inclusion financière; Inflation; Life satisfaction; Prêts durables; Sustainable lending; Trust in banks

A trans-border African crypto asset licence to promote economic growth and deepen financial inclusion - Van der Lith, Johann Daniel (University of Pretoria, 2025)
Financial technology (Fintech) is a rapidly growing industry, both locally and globally. In various ways, Fintech is undeniably transforming financial services and products in every possible part of the financial sector by changing how people access and use financial services. By using innovative technologies, such as distributed ledger technology and cloud technology, and combining large data sets, including alternative data sets, better products can be provided that can be hyper-personalised for market segments and improve access and participation in respect of financial services. Fintech is solving issues that touch the consumer, through a bottom-up approach, considering the retail consumer as a starting point, in contrast to the common traditional finance evolution from the institutional investors to the retail consumer in a top-to-bottom approach. What is exciting about what Fintech can do for Africa, is that it can move inefficiencies in services and product life cycles to become efficiencies and move the frontiers for already efficient products and services. Fintech, therefore, provides an opportunity to improve the archaic and pave the way for the future. This study focuses mainly on crypto assets to limit its scope. It first examines the Fintech landscape in Africa, more specifically, the activity level in each selected comparative country, namely Mauritius, Kenya, Zambia, Namibia and South Africa, and how the activity benefits or can potentially benefit the economy in the host country and lead to the deepening of financial inclusion. It further examines the regulatory frameworks in those countries. The study examines the regulatory approach taken and the local activity, exploring some of the risks identified in each country, and considers the requirements that regulators chose to implement to mitigate these risks, as well as the current state of regulatory frameworks. Consideration is given as to whether similarities in both the risks and the mitigation requirements exist and how this can be aligned across jurisdictions. Recently, international standard-setting bodies have increased their focus on ensuring the alignment and cooperation of regulatory approaches globally. In light of the call for alignment and increased collaboration through policy recommendations and guidance, and or regulators to provide comprehensive and effective regulatory approaches without stifling innovation, this study considers the theoretical possibility of allowing certain Fintech companies, specifically crypto asset service providers (subject to specified conditions) to operate across jurisdictions with a trans-border licence. This study examines Europe’s Markets in Crypto Assets Regulation, as it was the first of its kind continental-wide framework for crypto assets, offering numerous lessons to be learned from this framework. The Commonwealth Model Law on Virtual Assets is also considered, as it is intended to assist member countries in implementing Virtual Asset and Virtual Asset Service Provider regimes in their respective jurisdictions, as they deem appropriate. Lastly, the study will explore what a theoretical trans-border regulatory framework containing prudential and market conduct requirements could look like and what embedded supervision tools, for instance, through forensic nodes or zero-knowledge proofs, could be utilised to ensure that all the regulators participating as part of a licencing panel receive real-time data and have a full view of the level of compliance with the requirements imposed by the joint framework and can proactively and intrusively act, when needed. The proposed trans-border regulatory framework aims to support crypto asset service providers with multi-jurisdictional strategies in Africa in scaling their operations, with a focus on building Africa as a global Fintech hub. The proposed framework aims to achieve this through a harmonised regulatory framework that simplifies compliance, increases efficiencies, enhances innovation, allows for scalability, and better risk management. In addition to the goal of positioning Africa as a globally recognised Fintech hub, the harmonised framework aims to realise the purported benefits of the technologies utilised by crypto asset service providers, thereby deepening financial inclusion and promoting inclusive economic growth through increased access and participation, as well as lower costs.
Keywords: Crypto assets; Embedded supervision; Financial inclusion; Financial technology; Regulatory frameworks

The future of a prohibition on indirect unfair discrimination as part of South African anti-discrimination employment law : a comparative reflection - Huysamen, Elsabe (Stellenbosch University, 2025)
ENGLISH ABSTRACT: The Constitution of the Republic of South Africa, 1996 (“Constitution”) enshrines the right to equality, emphasising “the full and equal enjoyment of all rights and freedoms”. This commitment embodies the principle of substantive equality, which extends beyond mere formal equality by addressing systemic inequities and striving for transformative change. The pursuit of transformative equality is underpinned by two constitutionally mandated mechanisms: affirmative action and the prohibition of unfair discrimination, both direct and indirect. Within this framework, the prohibition of unfair discrimination serves a dual purpose: It establishes a foundation for defending formal equality while simultaneously acting as a transformative tool, particularly in safeguarding against indirect discrimination. In a transformative context, the concept of protection against indirect discrimination specifically is significant as it acknowledges that equal treatment can still perpetuate inequality. The concept has the unique ability to identify hidden barriers and protect against more subtle forms of unfair discrimination, rendering it instrumental in advancing substantive equality and promoting long-term, systemic change. Yet, despite its transformative potential, the application of protection against indirect unfair discrimination in South African employment jurisprudence remains underdeveloped. And even in jurisdictions where the concept has received greater attention (for purposes of this study, the United States of America, Canada and the United Kingdom), it has not significantly advanced substantive workplace transformation. The reasons for this limited success are partly shared across these jurisdictions and partly unique to South Africa. Given the above, the primary objectives of this study are threefold: (i) to explore the protection against indirect discrimination in advancing transformative equality within the South African constitutional framework; (ii) to investigate the reasons for the limited development and application of this concept in South African employment law; and (iii) to assess whether the prohibition of indirect discrimination should be upheld as a distinct legal concept in employment law. These objectives were anchored by the fundamental question guiding the study: what role does the concept stand to play in employment law in SA in future and, if any, to what extent and in what form? The study begins by examining the broader concept of equality – a notion that is both complex and continually evolving. Key questions that are addressed include: What does equality mean? What are the objectives inherent to equality? What values underpin the concept? Following this exploration, the focus shifts to the role of equality within the South African Constitution, specifically the content of the right to equality as provided for in section 9 of the Constitution. This includes an overview of the constitutionally mandated mechanisms for enforcing equality, namely affirmative action and the prohibition of unfair discrimination, with particular attention to protection against indirect forms of unfair discrimination. The study thereafter narrows its focus to the application of the latter concept within South African employment law. It highlights the challenges that have hindered the effective development of the concept, which can be broadly categorised as conceptual and practical obstacles. The South African experience is compared to the development and application of the concept in the United States, Canada, and the United Kingdom, offering a comparative perspective on the concept’s evolution in the aforesaid jurisdictions. The study concludes by presenting suggestions and recommendations on the future role of indirect discrimination within South African anti-discrimination employment law. It also recommends strategies for more effective implementation of the concept.
Keywords: Affirmative action programs; Discrimination in employment; Employment; Labor laws and legislation; Law reform; South Africa; Unfair labor practices

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation; Mediation; and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation; Industrial; Officials and employees; Social justice

Implementation of safeguard measures in digital trade to protect African domestic industries and platforms - Rotich, Nelly Chepngetich (University of Pretoria, 2025)
As technology continues to advance, more trade is moving online. The increase in digital trade brings with it both opportunities and challenges in the international trade field. The increase in digital trade could for instance result in a spike in digital trade imports which may subsequently cause or threaten to cause serious injury to domestic industries and platforms dealing in like or directly substitutable digital data/content and services. This would necessitate the application of safeguard measures to avert any such serious injury or threat to serious injury caused to the domestic industries and platforms. The procedure for applying safeguard measures to digital trade currently is unclear. The current legal framework on safeguard measures does not apply to digital trade despite increased digital trade over the years. Thus, this study explores the prospects and practical challenges relating to safeguard measures’ application to digital trade with a specific focus on African domestic industries and platforms. While domestic industries and platforms in any part of the world could be affected by surges in digital trade imports, Africa is in a precarious position. Intra-Africa digital trade volumes could be increased and disadvantages of African domestic industries and platforms by surges in digital trade imports could be prevented through regulation and judicious use of safeguard measures. This study established the need to regulate to tap into the potential of digital trade and prevent African industries and platforms from falling behind and from the disadvantage of market dominance by big techs from outside Africa. In conclusion, the study noted legal and institutional gaps in the application of safeguard measures to digital trade. The study has recommended that specific institutions at the global, continental and national levels take necessary actions to build a clear and robust framework for safeguard measures in digital trade.
Keywords: Digital trade; International Trade

International investment regime reform : integrating sustainable development into Uganda’s bilateral investment treaty system – a new model bit - Asiimwe, Esther Muchwa (University of Pretoria, 2025)
This thesis critically analyses Uganda’s bilateral investment treaty (BIT) system to determine its compatibility with sustainable development imperatives and proposes a new model BIT that aligns with Uganda’s evolving development priorities. Recognising the country’s reliance on foreign direct investment (FDI) for economic growth, this study interrogates the extent to which Uganda’s current BITs—many of which were concluded during earlier policymaking eras—expose the country to legal, economic, and regulatory risks. These include susceptibility to investor–state dispute settlement (ISDS) claims, constraints on the host state’s right to regulate, and a lack of provisions promoting environmental, social, and developmental objectives. Through doctrinal and comparative legal analysis, the study traces the historical evolution of international investment law (IIL), critiques the limitations of Uganda’s domestic and treaty-based FDI frameworks, and identifies substantive and structural weaknesses in Uganda’s in-force and model BITs. The analysis also considers international reform efforts and best practices from new-generation investment agreements, including the AfCFTA Protocol on Investment, the Investment Facilitation for Development (IFD) Agreement, and the SADC and EAC Model BITs. Particular attention is paid to the South African BIT reform experience as a comparator for Uganda’s reform journey. The study finds that Uganda’s BIT system is outdated, overly protective of investors, and poorly aligned with its sustainable development goals (SDGs). It recommends terminating unratified and problematic BITs, renegotiating existing ones, and adopting a new model BIT that balances investor protection with Uganda’s regulatory autonomy and sustainable development objectives. To this end, a draft model BIT is proposed as an annex to guide future treaty negotiations and reform Uganda’s investment regime in line with contemporary global standards and regional aspirations.
Keywords: Bilateral Investment Treaties (BITs); ISDS; Investissements; Investment law reform; Investments; Investor-State Dispute Settlement; Uganda

Impact of the basel accords on small indigenous banks in developing countries : the case of Zambia - Rolls II, Douglas Walter (University of Pretoria, 2025)
The purpose of this thesis is to evaluate the impact of the Basel Accords on small indigenous banks in developing countries, with particular concentration on small Zambian banks. The problem statement intends to investigate whether implementing the three Basel Accords is conducive to the growth of small banks in Zambia. The study further aims to determine whether the present approach to legal regulation of small banks in Zambia is appropriate. The methodology is based on desk-bound research and examination of both primary sources and secondary sources of material such as books, journals, and relevant articles. The study is impacted by the dearth of secondary research work and the difficulty of getting information from sources like the Zambian central bank and other information centres. While Basel I and II seem to have stabilised the Zambian financial sector, the Basel III Accord appears to have impacted negatively on many small banks to the extent that they have been forced into merger and acquisition arrangements with larger foreign banks to fund their undercapitalised positions to survive. It also emerges that the Zambian financial system is strongly linked to the international global economy; regionalisation with organisations like SADC and COMESA being the first stages in the process. This situation is likely to introduce increased instability in the Zambian financial sector by making banks more vulnerable to the vagaries of the international financial markets. It is thus recommended that the Zambian central bank should be more proactive in lobbying for better conditions for small banks from the Basel Committee for Banking Supervision and other international financial regulatory bodies; it should also avoid “cutting and pasting” rules from other jurisdictions to avoid possible distortions in the banking sector. It should also encourage further development of primary and secondary markets in low-cost paper and provide small banks with long-term, low-interest loans to support their growth. The Bank of Zambia, the Zambian central bank, should consider establishing a separate Act financial services Act for small banks to better regulate them. The central bank should also seek out non-Basel Accord solutions for small banks including re-examining the positive aspects of the infant-industry argument. Lastly, it should introduce a formal system for classifying banks in Zambia. At the international level, it is suggested that the global standard-setting bodies should undergo radical reforms to ensure that they are in tandem with the problems that banks in developing countries face as well as allow them to have a say in global standard setting. It is recommended that global standard-setting bodies apply simpler rules for smaller banks. The impact of the Basel Accords on small indigenous banks in developing countries and Zambia, in particular, is important because of the role that small banks play in developing economies in growing small and medium-sized businesses that are often ignored by large foreign banks. It is also important that small banks are allowed to grow into large and medium-sized banks to effectively compete against foreign multinational banks. Institutions based on neoliberal ideals appear to only serve Western businesses’ interests despite their call for all countries to create a level playing field. Due to the dearth of empirical research, there are several gaps in the work that may provide opportunities for further research in this important area of the law.
Keywords: Banking supervision; Basel accords; Basel committee; Developing countries; Financial regulatory framework; Small banks

From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Van Gool, Elias (Université de Lille, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents; Accidents de biens de consommation; Biens d'occasion; Biens de consommation; Circular economy; Commerce d'occasion; Consommateur (protection); Consumer product accidents; Product liability; Produits d'occasion; Repair; Responsabilité (droit); Responsabilité du fait des produits; Responsabilité du fait des produits (droit européen); Responsabilité du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Gool, Elias van (Université de Lille ; Katholieke Universiteit Leuven, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Issue: 2024ULILD015
Keywords: Accidents de biens de consommation; Biens d'occasion; Circular economy; Consumer product accidents; Product liability; Repair; Responsabilité du fait des produits et du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

The role and liability of internet service providers in South Africa : a critical and comparative appraisal - Nameka, Celeste Zara (University of South Africa, 2024)
This research uses a comparative approach to explore the role and liability of internet service providers in South Africa. The research aims to analyse and compare the role and liability of internet service providers for crimes and civil infractions committed by content providers and/or internet users. Against this aim, the researcher argues that internet service providers, as intermediaries, are ideally placed to monitor and control illicit content provision and/or internet use by the end user. The research focuses on South Africa, China, Ireland, and Nigeria. The research interrogated legislative control and queried the fitness for purpose of these mechanisms for internet service providers and the lacunae created by a rapidly expanding digital world comparatively. The research points out recurrent controversial and problematic concerns that affect both the internet service provider and the consumer. The researcher further explores challenges in applying legal imperatives to internet service providers that affect their end users. The comparative analysis assists in indicating how internet service providers operate in practice and their control (or lack thereof) by various legal frameworks. The researcher makes recommendations and offers solutions to assist with the future role and development of internet service providers and their impact on the end-user and criminal justice system.

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

Compliance with decent work standards by multinational enterprises - Maluleke, Tirhani Foster (University of Pretoria, 2024)
In contemporary times, the issue of human and labour rights violations has gained significant momentum, rendering it imperative for international organisations, states, and businesses to address this critical concern. It is widely acknowledged that while multinational enterprises can aid in achieving economic growth by investing directly overseas and raising the standard of living for the residents of host nations, their business operations may also result in abuse of human and labour rights. The United Nations (UN) Charter was drafted to set forth obligations for individual states, yet businesses do not bear international legal obligations. The Universal Declaration on Human Rights was adopted to implement the substantive contents of human rights referred to in the UN Charter in the general way. The preamble of the Universal Declaration refers to all organs of society, but, at the time of its adoption, businesses were not considered among such organs. It was inconceivable that business organisations would become so economically powerful within a few decades that they would pose a significant risk to human and labour rights, which would not be easily regulated under the national law of their host nations. It is the hypothesis of this study that numerous multinational enterprises (MNEs) violate core human and core labour rights, and that the existing regulatory framework does not adequately regulate them. To prove this hypothesis, this thesis will adopt a two phased approach. Firstly, a careful case law and literature review will reveal the inadequate regulation of MNEs. Evidence suggests that MNEs are guilty of flagrant labour standards and human rights violations. As a result of globalisation, MNEs have gained stronger international influence, and they are able to move their businesses to countries with low cost of labour and less regulations. This phenomenon weakens the governments of host nations as they are keen to promote foreign direct investment in order to reduce unemployment and to ensure economic growth. As a result, the host nations are encouraged to set laws that will attract MNEs at the expense of human and core labour rights. As result, MNEs are not held accountable in respect of their violation of human and labour rights. Secondly, this thesis will assess the efficacy of the regulatory instruments developed by the international community in response to the mentioned problem. This aspect is covered in Chapter 3 to 7 of this thesis. The strategies include the public and private hard law and soft law mechanisms developed at international level as well as campaigns by Non-Governmental Organisations (NGOs). Based on evidence, this thesis will conclude that a soft law approach is not fully effective. As such, Chapter 8 of this thesis proposes the introduction of some hard law measures to improve the existing soft law instruments to augment the existing legislative frameworks of the host countries. In particular, the thesis recommends regulatory reforms, which will empower the International Labour Organisation to intervene to prevent the labour rights violations by MNEs and where such violations occur, to at least provide effective remedies to vulnerable employees. This thesis constitutes a theoretical study, which attempts to provide suggestions regarding the implementation of realistic measures, which if implemented, may contribute to the attainment of decent work for all men and women who are engaged in work for MNEs.
Keywords: Codes of conduct; Decent work; Hard law; Human rights; Human rights due diligence; ILO MNE declaration; International Labour Organisation; International framework agreements; Labour rights; Multinational enterprises; OECD guidelines; Regional free trade agreements; Soft law

Corporate Social Responsibility Practices in the Nigerian Public Sector - Mohammed, Abbas (University of Plymouth, 2024)
This study examines Corporate Social Responsibility (CSR) practices in Nigerian public sector organisations using a comprehensive mixed-methods approach. The data collection process involved analysing 185 organisation-year observations from annual reports spanning 2011–2020, as well as questionnaires distributed to key stakeholders and interviews with senior executives from various organisations.The analysis utilised a multi-pronged strategy, including quantitative techniques such as regression analysis to explore the relationship between CSR practices and corporate governance mechanisms and qualitative methods such as narrative analysis and thematic coding to gain insights from survey responses and interviews.The findings indicate that CSR practices in the Nigerian public sector are moving in a positive direction. Organisations demonstrated commitment to CSR activities, including community development, education, environmental conservation, and philanthropy. Survey results showed that 83% of organisations engaged in CSR, driven by community acceptance and moral obligation. Additionally, 84% of organisations complied with regulatory frameworks, and 79% aligned their CSR policies with national or international standards. The analysis also found a significant positive relationship between CSR practices and factors such as larger board sizes, greater board independence, the presence of women on the board, and CEOs with longer tenures, higher educational qualifications, and international exposure.By triangulating these findings, it is clear that organisations have a strong commitment to giving back through various CSR initiatives, such as humanitarian assistance, youth empowerment, and educational programmes. Despite challenges such as budgetary constraints and weak accountability frameworks, organisations recognise the perceived benefits of CSR, including increased public confidence, improved stakeholder perceptions, enhanced organisational reputation, trust-building, community engagement, and empowering marginalised communities through education.The insights gained from this study conducted in an emerging economy namely, Nigeria, provide a new understanding of CSR practices in public-sector organisations. They also highlight the proactive approach of public sector organisations towards responsible practices. Consequently, the implications of this research extend beyond national boundaries, encouraging diverse and dedicated leadership to enhance CSR efforts and create lasting social impact. Future studies could explore comparative analysis between the public and private sectors or different countries, as well as sector-specific impact assessments.
Keywords: CSR; Corporate Social Responsibility; ESG; Sustainability

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

"Non erit innocens malus". Looking for Justice over maritime Crimes of International Concern. A tale of dichotomies - Guizzardi Righetti, Giampaolo (Université Côte d'Azur ; Università degli studi di Milano, 2024)
This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern. This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern.
Keywords: Compétence; Droit de l'homme; Droit de la mer; Justice maritime; Responsabilité (droit international); Violation des droits de l'homme; État

A comparative appraisal of creditor protection mechanisms under South African company law - Sibanda, Mandhlaenkosi (University of South Africa, 2024)
The study comparatively scrutinised creditor protection mechanisms entrenched in South African Corporate law to determine their effectiveness in advancing creditor interests in company affairs. The enquiry was triggered by the need for corporate laws to adapt to and align with the pace of global economic changes in open and democratic societies. The 2004 DTI Policy document on South African Corporate Law Reform (SACLR) proposed a shift from the traditional shareholder-centric view, which espouses shareholder importance in corporate governance, to a model that retains the supremacy of shareholder interests while simultaneously catering to the interests of other stakeholders (the enlightened shareholder value approach). In light of the DTI policy proposal, the parliament, in enacting the South African Companies Act 71 of 2008 (the Companies Act), reflected on the need to provide appropriate redress to investors' and third parties (creditors`) rights in the preamble to this piece of legislation. It was based on the forgoing expositions that this research work sought to establish whether the South African Corporate law had been adequately modelled to protect creditors and to look beyond the traditional company’s goal of profit maximisation for the shareholder at the expense of other stakeholders, such as the creditors, who equally have stakes in the success and continuation of the company. Thus, a comparative doctrinal and critical analysis of creditor protection laws from selected cognate jurisdictions was undertaken to determine the efficacy of the protection mechanisms accorded to creditors under the South African corporate jurisprudence. It is thus the researcher's findings that the South African provisions on mechanisms to protect creditors are set in motion and are, therefore, effective to a greater extent, subject to legislature dealing with some discrepancies as per lessons drawn from comparator jurisdictions and recommendations. Conclusively, the Companies Act should clearly include the creditor’s interests in those of the company and thus give a secondary duty to directors to ensure creditor interests, among other non-member stakeholders, are assertively safeguarded.
Keywords: Company controllers; Company law; Corporate entity; Corporate law; Corporate veil; Credit systems; Creditor interests; Creditor protection mechanisms; Creditors; Directors; Employees; Investors; Shareholders; Stakeholder constituencies; Stakeholder interests; Stakeholders; Third parties

A comparative legal analysis of the accommodation of neurodiversity in the workplace : towards a universal right to reasonable accommodation - Conradie, Riana (Stellenbosch University, 2024)
Workforces are made up of individuals with differences in personal characteristics, differences that may be traced back to unique personality types and traits and – sometimes – neurodivergence. Due to the inherent subjectivity of the interpersonal relationships that form the foundation of a work environment, these differences in personal characteristics inevitably lead to tension. In addition, as part of managing a work environment employers frequently take decisions that may be influenced by views and perceptions regarding employees’ personal characteristics. This study starts with a descriptive examination of the meaning of personality and the influence that personality traits and types may have on employment. This is followed by a descriptive examination of neurodivergence, the various forms of neurodivergence, and the impact of these conditions on the work environment. Building on these descriptive and conceptual underpinnings, the legal implications of neurodiversity in the workplace are investigated by identifying which principles of the existing South African employment law framework may be utilised to provide protection and promote respect for neurodiversity and the neurodiverse differences between employees. This encompasses a discussion of the South African employment law rules relating to recruitment and selection of employees, some of the rules applicable to the day-to-day management of employees, and the rules relating to termination of employment that may be (in)directly influenced by considerations of neurodiversity. The focus thereafter shifts to consider the legal principles of employment discrimination law, where it is found that the listed ground of disability and an unlisted arbitrary ground may potentially be used as the applicable grounds of discrimination by employees if they are prejudiced due to their neurodiverse characteristics. In addition, the possibility that the rules on reasonable accommodation may be utilised as primary mechanism to properly regulate neurodiversity in the work environment and protect against prejudicial treatment of employees due to their inherent personal neurodiverse characteristics is also considered. The South African position and potential employment law rules that may apply to the management of neurodiversity in the work environment is compared to the position in the United Kingdom by focusing on the meaning of disability, the right to reasonable adjustments, and the right to request flexible working arrangements. Finally, the conclusions that may be drawn from this study are emphasised and are followed by some recommendations on how (reasonable) accommodation of neurodiversity in the work environment may appropriately be used as primary mechanism to provide employees with sufficient and appropriate protection of differences in neurodiverse characteristics. Even though this study focuses on neurodiversity and neurological differences between employees, the principles and recommendations from this study may be of value in relation to the appropriate management and regulation of all inherent differences between employees.
Keywords: Discrimination in employment; Diversity in the workplace; Employment; Labor laws and legislation; Neurodivergent people; Neurodiversity; People with disabilities

Corporate law, governance, and sustainability : the public turn in the global socio-ecological transition - Junqueira, Gabriela de Oliveira (Universidade de São Paulo, 2024)
The overlap of financial, economic, ecological, and political crises has pushed the consensus on the need to promote a socio-ecological transformation, or, in short, a green transition. The discontent with the corporate world for its contributions to those crises has taken a central stage, with calls for greater corporate responsibility being articulated under a sustainability imperative. In the context of a new round of debates on the purpose of companies, this thesis examines the turning of corporate law and governance into a site for advancing a new capitalism. More specifically, the research investigates institutional changes occurring under the label of the public turn in corporate law, addressing the following questions: what constitutes the so-called public turn? What are its drivers and the perspectives on it? Which structural features led to targeting corporate law and governance to push for responsible corporate conduct? How does the public turn in corporate law relates to the broader set of actors and norms that shape corporate governance? Guided by critical approaches to the green transition and by political theories of corporate governance, the thesis resorts to different scholarships to examine the current wave of public oriented corporate governance mechanisms from within and from without corporate law. On the one side, the thesis offers a taxonomy of corporate law strategies being employed as well as a rich account on the multiple dimensions assumed by the new tools, placed at the intersection of human rights and environmental protection, corporate social responsibility, and global value chains. On the other, the thesis embeds corporate laws public turn within the unfolding of global capitalism, as the field evolves from corporate law to corporate governance to sustainable corporate governance. The thesis argues that the public turn in corporate law, caught in between the global and the local, enables the investigation of changing roles of states, businesses, and civil society within the political and epistemic terrain of the transition to a more just and sustainable economy. A sobreposição de crises financeiras, econômicas, ecológicas e políticas impulsiona o consenso sobre a necessidade de uma transformação socioecológica, ou, em resumo, uma transição verde. O descontentamento com o mundo corporativo assume centralidade, motivando demandas por mais responsabilidade corporativa, articuladas em torno de um imperativo de sustentabilidade. No contexto de uma nova rodada de debates sobre o interesse social, esta tese examina a transformação do direito societário e da governança corporativa em um locus de promoção de um 'novo capitalismo'. Mais especificamente, a pesquisa investiga as mudanças institucionais ocorrendo sob "a virada pública no direito societário", abordando as seguintes perguntas: o que constitui a esta virada? Quais são seus impulsionadores e perspectivas? Quais características estruturais levaram a mirar o direito societário e a governança para promover conduta corporativa responsável? Como a virada pública no direito societário se relaciona com o conjunto mais amplo de atores e normas que moldam a governança corporativa? Guiada por abordagens críticas da transição verde e por teorias políticas da governança corporativa, a tese recorre a diferentes correntes acadêmicas para examinar a atual onda de mecanismos de governança corporativa orientados para o público, de dentro e de fora do direito corporativo. Por um lado, a tese oferece uma taxonomia das estratégias do direito societário utilizadas, bem como um relato abrangente sobre as múltiplas dimensões assumidas pelas novas ferramentas, na interseção de direitos humanos, proteção ambiental, responsabilidade social corporativa e cadeias de valor globais. Por outro lado, a tese contextualiza a virada pública do direito societário nos desdobramentos do capitalismo global, à medida que o campo evolui do direito societário para a governança corporativa para a governança corporativa sustentável. A tese argumenta que a virada pública no direito corporativo, situada entre o global e o local, permite a investigação das mudanças nos papéis dos estados, empresas e sociedade civil no terreno político e epistêmico da transição para uma economia mais justa e sustentável.
Keywords: Corporate governance; Corporate law; Corporate sustainability; Direito societário; Economia política; Governança corporativa; Political economy; Private regulation; Regulação privada; Sustentabilidade corporativa

The legitimacy of dismissals for off-duty misconduct in South African labour law - Phulu, Thandekile (University of Pretoria, 2024)
The main aim of this thesis is to solve the uncertainties brought about by dismissals for off-duty misconduct. First, it should be acknowledged that the world as we know it has changed and continues to evolve. Dismissals have been significantly impacted by the use of social media outside the workplace. The legalisation of the use of cannabis by an adult person has also brought uncertainties in the way dismissals are handled, especially in cases where an employee consumes cannabis off-duty. These two aspects have significantly influenced dismissals for off-duty misconduct in South Africa, with employees alleging that their rights to privacy, dignity and freedom of expression are infringed. The thesis reveals that regardless of these modern changes, off-duty misconduct dismissal is still governed by the generic provisions of the Labour Relations Act 1995 and its Code of Good Practice: Dismissal. The thesis underscores the lack of clarity regarding the regulation of dismissals for off-duty misconduct in South Africa. Furthermore, despite the judiciary’s establishment of tests (the nexus test and the breakdown of the employment relationship), challenges in adjudicating off-duty misconduct cases persist. This thesis analyses the South African legal framework governing dismissals for off-duty misconduct. The research investigates the evolution of South African dismissal law, tracing its development from the pre-democratic era to the post-democratic era. This investigation scrutinises the shifts in the legal landscape regarding dismissals for off-duty misconduct. The analysis encompasses a range of legal instruments pertinent to South Africa, including legislation, international law, common law, and judicial precedent. The current need for a Code of Good Practice for off-duty misconduct dismissal is highlighted. This rationale is prompted by a comparative examination of other countries where, despite the absence of specific codes addressing off-duty misconduct, a proactive stance has been adopted to safeguard employees’ off-duty rights by enacting relevant legislation. These chosen states have statutes regulating employees’ off-duty conduct and clarifying which conduct is protected and in which circumstances. Consequently, the thesis proposes a Code of Good Practice: Dismissal for Off-duty Misconduct. This Code would assist in the uniformity of application of relevant aspects in determining the fairness of dismissals for off-duty misconduct, thus alleviating labour suits concerning this type of dismissal. The Code would also provide employers with guidelines on how to draft off-duty misconduct policies without infringing employees’ constitutional rights.
URI: https://repository.up.ac.za/handle/2263/97021
Keywords: Cannabis use; Dismissal; Labour law; Misconduct; Off-duty; Social media; South Africa

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Antitrust policy and EU labour markets : lessons from the US and comparative prospects - Langlois D'estaintot, Isaure (European University Institute, 2024)
Recent empirical evidence suggests that labour markets are not as competitive as previously thought. In that context, mobilizing antitrust policy has been discussed as a possible solution. The proposition sounds counterintuitive, however. If workers are paid below the competitive level, doesn’t this promote consumers’ outcomes by reducing downstream prices? Given that antitrust policy promotes consumer welfare, why would antitrust authorities intervene against such a state of affairs? Besides, why would stepping up on antitrust enforcement improve workers’ outcomes? Their interests have traditionally been protected through their exclusion from the scope of antitrust enforcement, not by the enforcement of antitrust rules to their benefit. This thesis demonstrates that those spontaneous assumptions do not hold. Consumer welfare does not speak against the defence of workers’ interests. First, the focus on consumers is a by product of methods: it does not prevent consideration of other types of market participants. Moreover, consumers benefit from competitive labour markets. The welfare effects of monopsony power simultaneously worsen workers and consumers’ outcomes. As for the promotion of workers’ interests, it can be achieved through both positive and negative enforcement of antitrust. So far, the EU Commission has been less proactive than the American DOJ and FTC on the issue of antitrust enforcement in labour markets ( although the state of affairs is evolving). While this difference may stem from EU workers benefitting from higher levels of social protection than US workers, those higher levels of protection may not negate the usefulness of antitrust ’s intervention. The low levels of antitrust enforcement in EU labour markets may result from legal uncertainty and case law inconsistency more than an absence of harm. Just like the merger control apparatus, Article 101 and 102 TFEU can be used to scrutinize labour markets. While doing so involves some practical complexities, they can be overcome.
Accepted: 2024-04-08T07:03:10Z
Keywords: Antitrust law; European Union countries; Labor laws and legislation; Unfair competition

Global Common: The Rights and Responsibilities of the State and the Investor in Renewable Energy Foreign Investment - Pang, Hui (UNSW Sydney, 2024)
States poured millions of dollars to attract foreign renewable energy investments for climate change mitigation, however, when it becomes too hefty for some states, they have modified regulations to reduce the level of support. These regulation changes have led to dozens of investors filing arbitrations against the host states, alleging breaches of investment treaty obligations. This thesis examines whether the current investor-state dispute settlement (‘ISDS’) regime adequately addresses environmental concerns when adjudicating renewable energy investment cases. While renewable energy investments can help protect a global common (the atmosphere) and mitigate climate change, the regulation changes also seek to protect a domestic public good (financial stability of the host state). Therefore, when the protection of a global common conflicts with a domestic public interest in renewable energy ISDS cases, what are the rights and obligations of the host state and the investor? Are the existing approaches of the ISDS regime toward environmental concerns and other public interests fair and adequate, and if not, what interventions can be made? This thesis explores these questions by conducting doctrinal analysis on more than 60 renewable energy cases and the arbitral jurisprudence regarding international environmental obligations. It uses the constitutionalisation of international law to break the self-contained regime of international investment law and argues that common values should be regarded as equally important as investment protection goals in ISDS. This thesis finds that the ISDS regime considers international environmental obligations to be insignificant in supporting the host state’s defences in non-compliance of bilateral investment treaties or the investor’s claims for investment protection. This thesis shows that the current approach furthers discrepancies between climate change mitigation and international investment law. Not only does this approach fail to acknowledge the environmental connections of renewable energy investment, but it also creates opportunities for fossil fuel investors to seek compensation against environmental regulation changes using the same arguments. As an intervention against the current approach, this thesis proposes to reconstrue the concept of legitimate expectations to place common values on equal grounds with investment protection incentives. This thesis makes two significant contributions to knowledge. Firstly, it extends existing analyses of the conflicts and synergies between international investment law and environmental protection and contributes to the growing body of scholarship on this topic. Research on this topic has mainly focused on how the state safeguards environmental interests against investor protection claims. While this narrative comprises many cases, it does not capture the full picture and overlooks the possible contributions of private parties in protecting global commons. Instead, this thesis examines whether international environmental obligations can serve as a ‘shield’ for the state’s non-compliance in investment protection, or as a ‘sword’ for investors to compel the state to fulfil its international obligations. Secondly, this thesis makes an intervention to reconstrue ‘legitimate expectations’, where common values are reinforced and not only the interests of investors are protected but also the ‘legitimate expectations of a responsible investor’ from the state and local communities are taken into account.

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
https://escholarship.mcgill.ca/concern/theses/cn69m944k
Keywords: HCCH; Hague Conference on Private International Law

A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

Legal protection of the individual's image against unauthorised commercial exploitation in South Africa : a critical evaluation of existing law and suggestions for law reform - Van Gensen, Layckan Inge (Stellenbosch University, 2023)
URI: https://scholar.sun.ac.za/handle/10019.1/128896
Keywords: Commercial exploitation; Human rights; Image rights; Intangible property; Intellectual property; Personality; Right of privacy

Developing a legal framework for determining forum choices in transnational intellectual property litigation - Ho, Vannessa May Ha (Macquarie University, 2023)
As communication technologies have assisted in the rapid transfer of information and goods across borders, there has been a commensurate rise in transnational intellectual property litigation. In particular, use of the Internet for trade and consumption of information has led to simultaneous infringement of parallel intellectual property rights in multiple States. The chosen forum to resolve such a dispute is perceived to have significant effect upon the outcome of litigation. There is a need to closely evaluate current jurisdiction rules and recent reform proposals to determine the extent to which they facilitate or prevent litigants from making forum choices that can promote efficiency and fairness in the dispute resolution process. However, there is currently no formal international treaty that regulates how litigants may make forum choices during transnational intellectual property litigation. As a result, the range of forum choices available to litigants are determined by divergent domestic rules, meaning that litigants must enforce their intellectual property rights in forums within every State where the rights exist and have been infringed upon. In such as context, a critical issue is to consider is whether an international regulatory framework could be developed to facilitate appropriate forum choices which advances and calibrates efficiency and fairness in transnational intellectual property litigation. As most conceptions of appropriate forums are from a doctrinal perspective, it is necessary to create a theoretical framework to determine what constitutes an appropriate forum choice during a transnational intellectual property dispute. This theoretical framework can then be used to evaluate the merits of current rules on jurisdiction and determine whether they define a suitable range of available forums that allow litigants to make appropriate choices. The forum non conveniens doctrine also needs to be evaluated as it has the most developed case law that considers appropriate forums for civil disputes. Finally, the risks and benefits of developing an international regulatory framework needs to be examined to assess which method would be the most suitable way to facilitate appropriate forum choices. It is hoped that this research will assist courts and legal practitioners when making decisions about complicated jurisdiction issues during transnational intellectual property disputes, as well as enable policy makers to promote reform that facilitates more efficient and fair forum choices.
Keywords: Forum choice; Forum non conveniens; Forum shopping; Intellectual property litigation; International regulatory framework; Kyoto Guidelines; Lucasfilm v Ainsworth; Private international law; Rational choice; Subject matter jurisdiction

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Meyer, Carolina (University of Pretoria, 2023)
In law it is common to encounter two separate pieces of legislation which govern a single matter or transaction, for example, the Companies Act 71 of 2008 (the Companies Act) and the Securities Transfer Act 25 of 2007 both of which address the sale of shares. Similarly, the Income Tax Act 58 of 1962 (the Income Tax Act) and the Companies Act both have regulations which govern, respectively, tax law and company law matters in South Africa. These two Acts overlap in various business and commercial fields as tax is frequently an important component of any business transaction undertaken by a company. Issues, however, arise when the regulations in these two Acts, are inconsistent. This can be observed if one compares the current South African Income Tax and Companies Act, specifically as regards the sections involving merger and amalgamation transactions. Section 44 of the Income Tax Act governs merger and amalgamation transactions from a tax perspective and provides for tax rollover relief if certain requirements are met. The regulations governing mergers and amalgamations under the Companies Act are contained in sections 113, 115 and 116 of the Act. Although these sections in both Acts address the same transaction – a merger or amalgamation between two or more companies – there are several discrepancies between the regulations in the two Acts which appear to operate entirely independently of one another. In practice, one often sees that other sections in the Companies Act and Income Tax Act are used to achieve a merger due, in the main, to the uncertainties in the application of the relevant merger sections in the two Acts and the limited interaction between them. This study identifies and assesses the impact of the discrepancies identified in these two Acts in relation to merger and amalgamation transactions. The study makes recommendations to address these discrepancies and to align the South African Companies Act and Income Tax Act as regards merger/amalgamation transactions.
URI: https://repository.up.ac.za/handle/2263/94064
Keywords: Amalgamation; Companies Act; Income Tax Act; Merger; Taxation

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

The Law of the Sea and Nigeria's Marine Policy: A Critical Evaluation - Tagowa, Wonotanzokan Nzeda (Ahmadu Bello University, 2023)
Keywords: Droit maritime; Marine policy; Nigeria; Sea

Fishing for Rights ! The Protection of the Individual in Fisheries - Longo, Andrea (Università degli studi di Milano, 2023)
La pêche est une activité humaine ayant un impact considérable sur l'environnement. Une mauvaise gouvernance, des mécanismes d'application faibles ou inexistants et des subventions excessives et non réglementées ont entraîné la surexploitation des stocks de poissons dans le monde entier, en produisant des conséquences potentiellement désastreuses sur l'écosystème marin et la sécurité alimentaire. Cependant, les pratiques de pêche non durables sont également liées à des abus à bord des navires de pêche : les organisations internationales et non gouvernementales attirent progressivement l'attention sur les pratiques répandues de violations des droits de l'homme et de crimes en mer, en appelant à repenser le régime international pour la conservation et la gestion des pêches en vue de concilier la sécurité économique et environnementale avec la dimension sociale de la pêche durable.Dans ce contexte, la présente thèse de doctorat aborde les problèmes conceptuels et pratiques qui se rattachent à la protection des individus impliqués dans ou autrement affectés par l'activité de pêche, en se concentrant particulièrement sur les victimes à bord des navires de pêche. La thèse s'appuie sur les études relatives à l'interaction des régimes en vue de favoriser le dialogue entre le droit international des droits de l'homme et le droit de la mer, deux régimes relevant du système plus large du droit international public. Après avoir exploré la portée de la question de recherche et fourni le contexte théorique et factuel, le premier chapitre se penche sur le régime du droit des droits de l'homme et examine la notion de juridiction telle qu'elle s'applique aux violations des droits de l'homme en mer, en étudiant en particulier l'utilisation potentielle de la norme sur la juridiction de l'État du pavillon comme critère pour attirer une violation des droits de l'homme à bord de navires de pêche relevant de la juridiction de l'État du pavillon. Le chapitre explore également le contenu et la portée des obligations en matière de droits de l'homme, en se concentrant notamment sur un ensemble de six droits prétendument violés à bord des navires de pêche, à savoir le droit à la vie, l'interdiction de la torture et des traitements inhumains et dégradants, l'interdiction de l'esclavage et des formes modernes d'esclavage, l'interdiction de la privation arbitraire de liberté, le droit à un travail décent et le droit à la santé. Ensuite, le deuxième chapitre se concentre sur le droit de la mer, en retraçant spécifiquement le développement historique qui a conduit à la consolidation du régime actuel de la pêche et en explorant la portée de la notion de pêche illégale, non déclarée et non réglementée et du phénomène de la criminalité dans le domaine de la pêche. Enfin, le dernier chapitre traite de la notion de juridiction telle qu'elle est utilisée dans le droit de la mer, en étudiant spécifiquement son contenu en ce qui concerne tous les acteurs étatiques de ce régime, à savoir l'État côtier, l'État du pavillon, l'État du port et l'État du marché. En particulier, ce chapitre examine de plus près les obligations de chaque État en ce qui concerne la protection de la personne à bord des navires de pêche, en accordant une attention particulière aux pouvoirs d'exécution de l'État côtier et à l'exercice par l'État du pavillon du contrôle des ses navires. Enfin, et surtout, il apporte un éclairage sur la contribution potentielle que les États du port et les États du marché pourraient apporter à la protection des personnes à bord des navires de pêche.
Cotutelle : Université Côte d'Azur
Keywords: Droit de la mer; Droits de l'homme; Fisheries regime; Fisheries resources; Fishing vessels; Human Rights; Law of the Sea; Navires de pêche; Pêches; Ressources halieutiques; Régime de pêche

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Alternate link : https://diposit.ub.edu/bitstreams/83cde66e-b943-45b6-830b-831df41cb73f/download
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

Developing a regulatory framework for electronic commerce in the Southern African Development Community: the prospects and challenges - Chimeri, Vongai (University of Fort Hare; Faculty of Law, 2023)
Keywords: Community law; E-commerce; Electronic Commerce; Electronic Transactions; Intra-regional trade; Regional integration; SADC; SADC Model Law

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
URI: http://hdl.handle.net/10019.1/127343
Keywords: Antitrust law; Australia; Competencia; Competition Act; 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

The legal regulation of trade union recognition in South Africa in historical and comparative context - Germishuys-Burchell, Wilhelmina (Stellenbosch University, 2023)
This study investigates the impact and importance of the legal regulation of trade union recognition and associated challenges in South Africa. It evaluates the current regulation of trade union recognition, including legislation and judicial attitudes apparent from the interpretation, application, and enforcement of such legislation, to ascertain its continued appropriateness in the current South African industrial relations environment. The study considers the policy choices of both voluntarism and majoritarianism underlying the Labour Relations Act 66 of 1995 (“LRA”) and the “workplace” constituency to which it applies as factors that might be contributing to challenges experienced in the current regulation of collective bargaining in South Africa. It evaluates the current model of trade union recognition and representativeness as it applies to the acquisition by trade unions of organisational rights, collective bargaining rights and trade union recognition for purposes of retrenchment consultation. It recognises that the specific model chosen to regulate the representative status of trade unions has a significant effect on the ability of trade unions to organise and conclude collective agreements and, as such, on the distributive effects of such agreements in the labour market and broader society. The study commences with an historical overview of the regulation of trade union recognition under the 1956 LRA and thereafter considers the 1995 LRA as a product of criticism against the 1956 LRA. Specific issues considered, largely based on the analysis of the relevant decisions by the Constitutional Court, include the following: the impact of Constitutional Court jurisprudence relating to trade union recognition on the process of collective bargaining and on the legal regulation of the right to strike; the role of representativeness and its link with the workplace as the constituency for recognition and acquisition of organisational rights; the often winner-takes-all effect of the current model on collective bargaining as a major cause of labour unrest; the reactive role the legislature has played over the past, almost three decades to address challenges; the extent to which intervention should take place to safeguard the institution of collective bargaining from being undermined as well as the regulation of collective agreements as the product of collective bargaining and as the primary source of terms and conditions of employment. The comparative review of Canadian law focuses on a number of issues selected specifically for their potential to provide insights into how the weaknesses in South African regulation may be remedied. This includes insights into the accommodation of special or significant minority interests and how to address recognition in the context of multi-location employers. The thesis concludes with remarks on the insights gained from the Canadian model and the 1956 LRA. Where appropriate, suggestions are made on the way forward for South Africa as to the appropriate regulation of trade union recognition and representativeness.
URI: http://hdl.handle.net/10019.1/127125
Keywords: Collective bargaining; Collective labor agreements; Dismissal of employees; Employee rights; Industrial laws and legislation; Labor disputes; Labor unions; South Africa

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

The Double Life of State-Owned Enterprises in International Economic Law: States, Corporations or Both? - Kikarea, Eirini (University of Cambridge, 2023)
State-owned enterprises (SOEs) have recently gained prominence in global markets and feature among the world’s most influential enterprises. The aim of this research project is to analyse the international norms in force regulating whether SOEs are considered state or non- state actors, and their conduct state or non-state conduct, the interpretation and application of these norms by adjudicators in different international regimes, and to provide alternative prisms through which these rules and decisions can be assessed and re-thought by political actors. I show that, in relation to SOEs, the concepts ‘state and ‘act of state’ have been ascribed diverse meanings by adjudicators and other international actors, who have employed legal standards with divergent wording and thresholds when dealing with similar questions. I argue that the fragmented meaning of these terms should be understood, in part, as a result of the inherent malleability of these terms and the different expert vocabularies employed across regimes. It is exhibited that adjudicators in the international trade and investment regimes are more inclined towards piercing the corporate veil of SOEs, potentially evidencing the existence of biases against SOEs, which are perceived as inherently economically inefficient and politically motivated actors in an indiscriminatory manner. In the last chapter, I introduce alternative lines of thought regarding the regulation of SOEs in international law. I suggest that, instead of engaging in theoretical discussions on the proper delineation between the public and the private sector, it is more useful to focus on the distributional impact of international rules on various actors, especially on developing and emerging economies where the presence of SOEs is very high. Such alternative prisms of analysis open paths for future research and practice, with the goal of designing an international economic order that incentivises institutional experimentation in the pursuit of economic development and distributional equity.
Keywords: International Economic Law; International Investment Law; International law; International trade law; Public enterprises; State capitalism; State-owned enterprises

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
http://hdl.handle.net/10962/419230
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments

Legal harmonisation of non-tariff barriers of regional economic communities as a catalyst to the realisation of the African continental free trade area - Achancho Etagha Epse Abia, Elisabeth (University of KwaZulu-Natal, 2023)
Legal harmonisation is an integral aspect of regional integration and the desire to promote regional and sub-regional economic integration in Africa is exemplified by the establishment of the African Continental Free Trade Area (AfCFTA) in 2018. The 2012 decision of the AU to create the CFTA by 2017 was reiterated in Aspiration two of Agenda 2063. The legal harmonisation of non-tariff barriers has been a vital instrument in the achievement of EU economic integration and the Organisation for the Harmonisation of Business Laws in Africa (OHADA). The study seeks to critically examine the theoretical and conceptual underpinnings of regional integration and legal harmonisation of non-tariff barriers by the AU and RECs. It also analyses the current political, economic, and legal reinforcements to regionalism in Africa and practices needed to advance intra-regional trade within the framework of Agenda 2063. This was done by evaluating the key legal frameworks of the AU (the Abuja Treaty, the Constitutive Act of AU, 2007 Protocol on relations between AU and RECs and Agenda 2063) with the aim of identifying best practices, gaps and impediments pertinent to strengthening Agenda 2063 CFTA. At the end of the study, the abilities of three selected RECs (SADC, COMESA and EAC) were assessed to drive home the AfCFTA. This was done by identifying flaws in existing treaties of RECs, while advancing a model of legal harmonisation of NTBs between them. It was found out that the AU and RECs have not vigorously considered the significance of legal harmonisation in their integration agendas. This resulted in the lack of unambiguous and concrete provisions for the legal harmonisation of NTBs in their guiding policies. Where some attempts are evident, such as in the EAC, they have been implemented unsatisfactorily with lack of a compliance mechanism. This study contended that if legal barriers to free trade are not eliminated, even if all other barriers were to be removed, the effective realisation of the AfCFTA would still be hindered. Hence, this study recommends the principles of direct applicability and direct effects of regional laws to addressing the legal harmonisation challenge underscored. Iqoqa Ukuvumelanisa okusemthethweni kwezithiyo ezingakhokhiswa intela kuyisici esibalulekile sokudidiyelwa kwesifunda kanye nesifiso sokugqugquzela ukuhlanganiswa komnotho wesifunda kanye nesifunda esincane e-Afrikha sibonakala ngokusungulwa kweNdawo Yezwekazi Lase-Afrikha Yokuhweba Ngokukhululekile (i-AfCFTA) ngowezi-2018. Isinqumo sowezi-2012 se-AU sokwakha i-CFTA ngowezi-2017 saphindwa Esifisweni Sesibili soHlelo- 2063. I-CFTA iphinde ibe wuhlelo olubalulekile oHlelweni-2063 futhi impumelelo yayo ibalulekile. Ucwaningo luhlose ukuhlola ngokujulile izisekelo zethiyori nezomqondo zokuhlanganiswa kwesifunda kanye nokuvunyelaniswa kwezomthetho kwezithiyo ezingakhokhisi yi-AU kanye nama-REC. Iphinde ihlaziye ukuqiniswa kwamanje kwezepolitiki, ezomnotho, kanye nezomthetho kuzwelonke e-Afrikha kanye nezinqubo ezidingekayo ukuze kuthuthukiswe ukuhwebelana kwangaphakathi kwesifunda ngaphakathi kohlaka loHlelo-2063. Lokhu kwenziwa ngokuhlola izinhlaka zomthetho ezibalulekile ze-AU (iSivumelwano sase-Abuja, UMthetho-sisekelo we-AU, 2007 Protocol on relationship between AU and RECs and Agenda 2063) ngenhloso yokuhlonza izindlela ezingcono kakhulu, amagebe kanye nezithiyo ezihambisana nokuqinisa uHlelo-2063 CFTA. Ekupheleni kocwaningo, amakhono ama-REC amathathu akhethiwe (i-SADC, i-COMESA kanye ne-EAC) ahlolwa ukuze aqhubekisele phambili i-AfCFTA. Lokhu kwenziwa ngokuhlonza amaphutha ezivumelwaneni ezikhona zama-RECs, ngenkathi kuthuthukiswa imodeli yokuvumelana okusemthethweni kwama-NTB phakathi kwawo. Kwatholakala ukuthi osopolitiki base-Afrikha abazange bayicabange indlela eqinile yokuhlanganisa umnotho wesifunda, nakuba indlela enjalo yaphakanyiswa abasunguli besifunda sase-Afrikha. I-AU kanye nama-REC awazange acabangele ngamandla ukubaluleka kokuvumelana kwezomthetho ezinhlelweni zawo zokuhlanganisa. Lokhu kuholele ekuntulekeni kwezinhlinzeko ezicacile nezibambekayo zokuvumelana ngokusemthethweni kwama-NTB kuzinqubomgomo eziqondisayo. Lolu cwaningo lwagomela ngokuthi uma izithiyo ezingokomthetho zokuhwebelana ngokukhululeka zingaqedwa, ngisho noma zonke ezinye izithiyo zizosuswa, ukufezeka ngempumelelo kwe-AfCFTA kusazothikamezwa. Ngaphakathi kwalokhu kwangemuva, lolu cwaningo luncoma izimiso zokusebenziseka okuqondile kanye nemiphumela eqondile yemithetho yesifunda ukuze kubhekwane nenselele yokuvumelana kwezomthetho egcizelelwe.
Keywords: Common External Tariff; Direct Effect; Legal harmonisation

Environmental protection under national legislation and agreements between oil and gas multinational corporations and host communities - Adedipe, F. (Canterbury Christ Church University, 2023)
The exploration, production and shipment of crude oil and gas by multinational corporations (MNCs), involved in bilateral treaties in Nigeria has perpetrated environmental disasters upon host communities. This has been as a result of oil and gas leaks from MNCs facility into the air, land, water, marine habitat, and cultural life of host communities are heavily polluted. International law has attempted to regulate the activities of MNCs particularly in the protection of the environment in which they operate through four main treaties: Universal Declaration of Human Rights,1International Covenant on Economic, Social and Cultural Rights (ICESCR), 2 Declaration of the United Nations Conference on the Human Environment (Stockholm Declaration)3and Declaration of the United Nations on Environment and Development (Rio Declaration). In addition, the demand for environmental protection is foregrounded under the right to life recognized in article 6 of the International Covenant on Civil and Political Rights (ICCPR). However, a major criticism of international law is its inapplicability to non-State actors such as corporations. This creates a lacuna in the legal framework of protections which has been exploited by opportunistic MNC’s. International soft law such as the Global Compact, Organization of Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises and United Nations Guiding Principles (UNGPs) on Business and Human Rights encourages corporations to respect environmental rights and creates substantive standards for States to hold corporations accountable for environmental and human rights violations. The challenge remains that these international laws having soft law status are not binding on corporations. Also, a further problem is that several developing state governments may be complicit in the environmental abuses perpetrated by MNCs for the purpose of boosting economic development. Therefore, this research proposes the regulation of MNCs under national legislation and bilateral investment treaties. It recommends certain preventive and mitigation measures against the adverse environmental effect of their activities in the exploration of natural resources, waste disposal and other connected operations in developing communities in Nigeria. Some of these preventive measures include environmental impact assessment (EIA), mandatory reporting and disclosures, community stakeholder participation, environmental management and safety practices, with activity, temporal and spatial management as mitigation measures. Also, clean-up and compensation by MNCs are effective remedies for environmental abuses. Furthermore, fines, blacklisting, withdrawal of license and criminal charges are recommended for the enforcement of environmental protection of host communities.
Permalink: https://repository.canterbury.ac.uk/item/95yw5/environmental-protection-under-national-legislation-and-agreements-between-oil-and-gas-multinational-corporations-and-host-communities
Keywords: Agreement; Environment (protection); Host communities; Multinational corporations; Oil and Gas Industry

The regulation of Corporate phoenix activity in South Africa - Basson, André Stephan (University of Johannesburg, 2023)
Phoenix activity involves conduct whereby a failing company (the old company) is replaced by a second company (the new company) in the operation of the same or a similar business and that involves the same or similar company controllers. Transactions of this nature can be legal and even be beneficial to society, since entrepreneurs who pursue a viable business may, if the new company succeeds, benefit the economy and many other stakeholders. These transactions are referred to as legal phoenix activity. Problems arise however when phoenix activity is engaged in with the goal of evading the debt of the old company, known as illegal phoenix activity. In other cases, even well-intentioned company controllers can cause significant harm by resurrecting a fundamentally flawed business. This conduct, although not illegal, is unduly prejudicial to stakeholders and is known as problematic phoenix activity. While this thesis focuses on illegal phoenix activity, several measures identified should also curb problematic phoenix activity. This study identifies the elements and common characteristics of illegal phoenix activity. It then analyses regulation pertaining to those elements and common characteristics with the aim of finding effective solutions to the problem. This includes evaluating measures that reverse prejudicial transactions that occur during illegal phoenix activity as well as holding complicit parties, such as company controllers and the new company, accountable for their actions. Regulation aimed at preventing and investigating illegal phoenix activity is also considered. This thesis uses the comparative legal approach to analyse regulatory responses to illegal phoenix activity. Australia, the United Kingdom, and the United States of America are examined. Several reported cases in South Africa involving what appear to be illegal phoenix activity are explored, along with the existing measures that are applicable to illegal phoenix activity in South Africa. A single anti-phoenix provision is undesirable as it has the potential to unjustifiably infringe on legal phoenix activity. This thesis proposes a multi-pronged approach, which involves a combination of better enforcement of existing laws and the introduction of smaller targeted amendments to legislation aimed at reducing the incidence illegal phoenix activity.
Keywords: ABUSE OF THE CORPORATE FORM; Bankruptcy fraud; Evasion of liability; Fraud on creditors; Phoenix activity; Phoenixism; Strategic bankruptcy; Successor liability; Transactions prejudicing creditors; Transfers at an undervalue

A legal analysis on how France, Germany, the European Union and South Africa responded to the United Nations guiding principles on business and human rights - Buis, Jeanette (University of Pretoria, 2023)
Globally, companies pursue profitability; they want lower prices for the goods they buy and for the services they use. To gain profit and keep their prices low, they contribute to human rights violations and/or the devastation of the environment. The UNGP is the UN unanimously endorsed instrument that encourages states to pass legislation to compel companies to exercise human rights due diligence and to report on their efforts. The United Nations Guiding Principles (UNGP) impose a duty on companies to conduct human rights due diligence that apprises them of possible human rights or environmental risk exposure in their international operations. States have a responsibility to assist those harmed by a company’s activities to seek judicial relief. The UNGP is a soft law instrument but has had a major effect in the field of business and human rights. Though a voluntary obligation, the UNGP has become the reference document and is used by Civil Society Organisations (CSO) to pressure states into passing regulations on business and human rights. In 2016 Germany passed a National Action Plan (NAP) and the Lieferkettensorgfaltspflichtgesetz (Supply Chain Due Diligence Act) in 2021. France passed a Vigilance Law (Loi de Vigilance) in 2017. Additionally, a UN resolution has initiated a treaty-making process, which might lead to an internationally legally binding instrument that will articulate companies’ responsibilities to avoid, mitigate and remedy human rights violations that their activities cause. The South African government’s response to the UNGP has focused on negotiating a legally binding instrument at an intergovernmental level. This research examines three countries’ varying responses to the UNGP, a soft law instrument. In February 2022 the EU Commission published a proposed directive on corporate sustainability due diligence. The proposed EU legislation aims to advance respect for human rights and environmental protection. The goal is to create a level playing field within the European Union which leads to the exploration of the role China plays in a globalised world. China aims to be more than the world's factory and to become a leader in innovation and high-end manufacturing.
URI: https://repository.up.ac.za/handle/2263/93522
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights due diligence; Mandatory corporate due diligence; RSE; United Nations Guiding Principles; responsabilité sociale des entreprises

The commercial sexual exploitation of children perpetrated by the private sector: can international law be improved? - Hecht, Mark (Université de Sherbrooke, 2023)
International law is a robust system designed to unite world governments in an effort to, inter alia, cease human rights violations and hold those who commit them accountable. As it currently stands, and by its own design, the international human rights legal regime focuses on and applies only to state actors, meaning that violations committed by non-state actors, such as multinational corporations (MNCs), are seemingly conducted with impunity inside this space. Multinational corporations are powerful international players that have undoubtably fostered a significant role in reducing global barriers. By their very nature, they are far more mobile than states, allowing them to evade domestic power and regulatory schemes by detaching from their home state and relocating to a host state with weaker oversight and/or enforcement powers. Simply stated: even though MNCs have better financing, heightened mobility, and a disproportionate amount of influence when compared to world states, they operate with less global accountability. Commercial sexual exploitation of children (CSEC) is a fundamental violation of children’s rights. It consists of sexual abuse by the adult and remuneration in cash or kind to the child or a third person or persons. The child is treated as a sexual object and as a commercial object. Multinational corporations have been implicated in CSEC through acts of omission and commission. And despite the fact that much international law has been drafted to protect children around the world from CSEC—most notably the United Nations Convention on the Rights of the Child and its Optional Protocols—the numbers of children who have been emotionally and physically harmed by and through MNC conduct has only increased in the past decade. There have been numerous efforts by international organizations to address the challenges when regulating and monitoring human rights violations by MNCs. States, civil society organizations, and the private sector itself have also attempted to address these human rights violations through domestic law, modifying international law principles, and with civil regulation. Obstacles exist in the effectiveness of each of these approaches, leaving children at risk with no single effective strategy to combat and address rights violations by MNCs. The dissertation conducts a review of the current landscape of child law, through the lens of corporate accountability for CSEC. Then, it suggests a new alternative, putting forward an international solution to an international problem.
Keywords: Commercial sexual exploitation of children; Convention on the rights of the child; Corporate Social Responsibility; International child law

Land Reform in Sub-Saharan Africa: Exploring Interested Parties Perspectives on Cameroon's Land Tenure and Land Law Reform. - Kenfack Kenjio, Jacques Wilfried (Antioch University, 2023)
This research study seeks to understand interested parties’ perspectives on Cameroon's existing land tenure systems, the 1974 land law, and ongoing efforts to reform this land law. It identifies both concerns and specific recommendations from these parties on the formulation and implementation of future reforms. In the decades following the achievement of independence from European colonizers, most governments in sub-Saharan Africa (SSA) have adopted new national land tenure policies to meet their countries’ needs and aspirations. In some parts of SSA, however, this process of land tenure formalization has negatively impacted the land rights of people observing customary land tenure. This has been a result of government interventions such as compulsory land acquisitions, which while technically legal, are ethically questionable. In the face of this challenge, efforts to reform post-colonial land laws have become a matter of urgency. A national land reform process for Cameroon, announced in 2011 has adopted a multistakeholder approach. My study seeks to understand interested parties’ perspectives on Cameroon’s existing land tenure systems, the 1974 land law, and ongoing efforts to reform the land law. This study applied a case study methodological approach and a convergent mixed-method design. Evidence from this study shows that interested parties in Cameroon are in agreement on 1) the reform of the 1974 land law, 2) the recognition of customary land tenure, 3) the continued use of multistakeholder participation in land law reform, and 4) the promulgation of the new land law through mass sensitization and information dissemination.
URI: http://rave.ohiolink.edu/etdc/view?acc_num=antioch1684431556060359
Keywords: Government-Driven Land Dispossessions; Land Expropriations; Land Law; Land Reform; Land Tenure; Mixed Methods; Multistakeholder Participation; Sub-Saharan Africa

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

The goals of competition law for merger analysis in developing jurisdictions : a critical appraisal of merger analysis under Kenyan competition law - Njako, Priscilla Mumbua (University of Pretoria, 2023)
This thesis considers whether jurisdictional exigencies should influence competition law enforcement, with a specific focus on merger analysis. It examines various approaches and schools of thought regarding the goals of competition law and how these play out within jurisdictional parameters. The history of enforcement of American antitrust is scrutinised to establish the nature of the interplay between greater economic policy direction and the goals of competition law. The study also explores the issue of convergence and whether developing jurisdictions should align their competition law to that of developed jurisdictions with mature competition law.
URI: https://repository.up.ac.za/handle/2263/91683
Keywords: American antitrust; Competencia; Competition law; Concurrence (droit); Kenya; Merger analysis

Harmonisation in the rules governing the recognition of foreign judicial ship sales - Shao, Yingfeng (World Maritime University, 2023)
Ships, the high-value asset used in both seagoing and inland navigation, and in which various legal and natural persons have interests, must be secured against legal risks arising from any cross-border legal divergence. Legal certainty of ownership of the ship is therefore desirable but it is under challenge with regard to the judicial sale of a ship: the effects of a judicial sale may be denied in a jurisdiction other than the place where it was sold under the principles of state jurisdiction. Multiple efforts have been made to address legal uncertainty. Particularly important is a new treaty governing the international effects of judicial sales: the United Nations Convention on the International Effects of Judicial Sales of Ships (Beijing Convention). This dissertation is intended to contribute to that process by setting out two tasks; first, it seeks to identify the obstacles to the recognition of foreign judicial sales, providing additional knowledge which may aid national legal orders when deciding recognition approaches; second, it looks for a universal solution that better guarantees recognition which would benefit shipping. A comparative legal research exercise exploring similarities and dissimilarities in the municipal and international laws governing the recognition and sale procedures is undertaken. Research results are presented in this kappa and research papers, exhibiting the profuse difficulties a party seeking recognition may encounter in the current legal framework, and explains the new recognition approach under the Beijing Convention. Based on the research findings, a universal solution is proposed that avoids révision au fond, defines the finality of a judicial sale, and sets forth a fixed number of grounds for denial of recognition which may bring greater certainty. This purported optimal solution should guarantee equal treatment for all foreign sales seeking recognition before the registry while minimising the registrar’s burden of finding and examining foreign laws. In the interest of universality, this solution better accommodates disagreeing principles underlying certain aspects of the sale, viz., the ship’s location at the time of sale, the notification of sale, and the variance in the standard sale, namely, court-approved private sales, in a manner that more states may accept. This solution is largely in line with the recognition approach under the Beijing Convention. Considering the greater legal certainty the new instrument may bring, ratification is supported.

The public domain and the legal protection of Indigenous Knowledge Systems - Verhoef, Gerardus (North-West University, 2023)
IKS stakeholders often debate the divide between indigenous and other knowledge systems. IP rightsholders seek advice on how they can strengthen and secure their proprietary rights or broaden the public domain, while other interest groups such as indigenous peoples and local communities want to know how the public domain can be enclosed. One reason for this divide seems to be that the IP regime operates in a sphere where the public domain is demarcated by individual rights, as opposed to the indigenous knowledge systems regime where the public domain is demarcated by social embeddedness and connected to the land on which indigenous peoples and local communities live. This problem manifested itself over centuries of colonialism and technological development worldwide, but also because indigenous worldviews do not share the pre-appropriation narrative of the public domain than technological advanced societies. Within the context of this narrative the research question was posed, namely "what are the appropriate legal instruments for protecting Indigenous Knowledge Systems without compromising the public domain?" To answer this question, the public domain was analysed from three perspectives, namely international law instruments, human rights and IP rights. It was found that none of these perspectives lead to a narrow interpretation of the public domain – in fact, they all aim to broaden the public domain. These early findings on the public domain assisted to apply the fundamentals of the public domain to international law instruments and their application to IKS. In this regard it has been shown that the existing international law instruments, as well as the natural evolvement of these instruments over time, adequately provides for the protection and commercial exploitation of IKS worldwide. There is a proviso, though: IKS need to be viewed through the WIPO lens, which provides for the distinct delineation of categories of IKS, namely traditional knowledge, traditional cultural expressions and genetic resources. For example, the Bern Convention is founded on the three principles of droits des auteurs, droit moral, and domaine public. The boundaries of the public domain within the context of IKS can be reconciled with all three of these principles, and national legislators merely need to apply these principles to national legislation. With these insights gained on international law instruments, a few countries were analysed to ascertain how they address their local challenges pertaining to IKS. The countries that were analysed all aimed to appreciate international law instruments to which they are signatories, while they develop country specific IKS-related jurisprudence, although it cannot be said to be the same in each country. None of the findings pertaining to these countries could provide convincing arguments as to why a sui generis system for IKS can work. The research then moved to a legal analysis of South African legislation in relation to IKS. It has been shown that in general, South African legislation on IP is well aligned with international law instruments. These findings assisted with the research question at hand and was instrumental with coming to the early conclusion that IKS neatly fits into South Africa's current IP regimes and their associated public domains. Throughout the thesis, the rights and obligations of IKS rightsholders were demarcated since no right is absolute, as has been shown when the South African Constitution was discussed. In this regard, the droit moral of individuals from indigenous peoples and local communities, as well as the indigenous peoples and local communities, are to be respected. This approach led to more practical measures to ensure that matters such as prior informed consent, secrecy and sacredness, equity and access to TK, TCE and GR and benefit sharing were all understood within the boundaries of the public domain.
Keywords: Indigenous knowledge (protection); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Savoirs traditionnels

The Law Applicable to Security Interests in Intermediated Securities under OHADA Law - Monsenepwo Mwakwaye, Justin (Universität Würzburg, 2022)
In recent decades, the technical handling of custody business in the OHADA region has undergone a lasting change. There has been a shift from a direct to an indirect holding system, in which the interests of an investor in respect of the underlying securities are recorded in the books of an intermediary (such as a bank or a securities firm). Under the law of all states within the OHADA region, the traditional conflict of laws rule for determining the enforceability of a securities pledge that occurs in the indirect holding system is the lex rei sitae (or the lex cartae sitae or the lex situs ) rule. However, the traditional lex rei sitae rule cannot be appropriately applied to a system where the dematerialised securities are held through multiple layers of intermediaries located in different jurisdictions. Yet, until the intermediated system and the collateralisation of intermediated securities in the OHADA region will continue to operate in somewhat legally murky waters, leading to more instability in the financial markets. Therefore, Justin Monsenepwoaims to find an appropriate and consistent approach that reflects the reality of the indirect holding system in the OHADA region. “This publication is essential reading for policy makers, academics, market participants, and legal practitioners in the OHADA region and beyond. I am convinced that its in-depth analysis of OHADA’s substantive and conflict of laws rules will go a long way in filling the gap in this area and encouraging further development in the future.” Christophe Bernasconi, Secretary General of the „Hague Conference on Private International Law“ – HCCH in the foreword
Keywords: Competencia; Competition law

Overcoming Divergence in English and French Contract Law: A Common Taxonomy of Commercial Contracts - Pedamon, Catherine (University of Westminster, 2022)
The works presented for the PhD by publication are all connected in the way they engage in a functionally comparative study of the English and French law responses to common problems pertaining to contractual performance and contractual interpretation. My comparative inquiry demonstrates that both France and England have stayed true to their historic responses in times of peace and crisis confirming different mentalités juridiques. As neither England nor France offers ideal solution, parties may be better off finding a resolution to their disputes beyond the legal realm and respond to calls for collaboration. This nevertheless shows persisting differences in Anglo-French approaches. This thesis however argues that these divergences may nevertheless lead to common results through the lens of a taxonomy of commercial contracts – professionally drafted contracts may lead to converging results given the common application and interpretation of frequently used clauses beyond a domestic legal culture; by contrast, rudimentary contracts produce diverging results as the interpretation of these agreements is marked by a distinctive domestic socio-legal culture. This taxonomy has the potential to improve the predictability of outcomes in commercial disputes in England and France.
Keywords: Commercial contracts; Contract law; England; France

Reforming investor-state dispute resolution: Focusing on the roles of domestic courts - Ma, Wanli (Erasmus University Rotterdam, 2022)
While a universally applicable multilateral agreement on investment is not yet available, a broad network of BITs and investment chapters in FTAs has been put in place to protect foreign investors and their investments. Meanwhile, investment arbitration has become a defining feature of modern international investment law over the recent decades, enabling foreign investors to launch an investment arbitration against host states, often without the need to go through local remedies before that. With the caseload of investment arbitration increasing at a rather rapid speed, such a dispute resolution method has also attracted fierce criticism. Many commentators have alleged, among other, that the decision-making of investment arbitrators has been inconsistent and unpredictable, that investment arbitration has become a threat to public interest, that investment arbitration proceedings are not transparent enough, that the arbitrators involved are not independent nor diverse enough, that the lack of an applellate mechanism compromises the quality of decision-making, and that investment arbitration has become far too costly and time-consuming. Against such a backdrop, the global community has made joint efforts to reform the investment arbitration system, not least through various initiatives developed at ICSID and UNCITRAL. Almost at the same time, national states also seem to have started to reconsider the costs and benefits of including investment arbitration in their investment agreements as a method for the resolution of disputes with foreign investors. Although the caseload of investment arbitration continues to grow and national states keep concluding IIAs containing investment arbitration clauses, at least some countries in their more recent investment treaty making practice have demonstrated a policy trend to rein in investment arbitration and ramp up the role of domestic courts in resolving investment disputes. They often do so by exiting the ICSID system, terminating their investment agreements with economic partners, excluding investment arbitration from their investment agreements, and conditioning investment arbitration upon the prior use of litigation via domestic courts. While the state practice mentioned above surely does not suggest the global society has any intention to abandon investment arbitration any time soon, it prompts us to take a step back and reconsider the role that domestic courts may play in resolving investment disputes, instead of solely focusing on the piecemeal reform of investment arbitration. When it comes to investor-state dispute resolution, domestic courts can indeed play different roles along the process. Like investment tribunals, domestic courts can also adjudicate investment disputes between foreign investors and local authorities. Such a judicial role sometimes is also confirmed in investment agreements through, for example, the exhaustion of local remedies rule, the clause demanding pursuit of local remedies prior to investment arbitration and the fork-in-the-road provision. In the context of non-ICSID arbitration, disputing parties are often entitled to applying for the review by domestic courts loci arbitri of the rulings and awards rendered by investment tribunals. Domestic courts loci arbitri would thus assume a supervisory role with regard to arbitration proceedings and arbitral outcomes, as they may set aside arbitration awards in question according to the review grounds enumerated in local arbitration laws. Moreover, domestic courts in a broader sense may be called upon to support the conduct and / or authority of investment arbitration, by recognizing and enforcing the investment awards rendered by arbitral tribunals and issuing interim measures of a judicial nature to facilitate the arbitration process. Since litigation through domestic courts and investment arbitration are two primary remedies that foreign investors often rely on for the resolution of investment disputes, this study constructs three models of institutional design with regard to the allocation of jurisdiction over investment disputes between domestic courts and investment tribunals. While the reality may turn out to be more complicated, such three models roughly represent the institutional choices facing national states. These three models are: (i) utter reliance on domestic courts as the exclusive forum for investor-state dispute resolution, (ii) investment arbitration operating as a substitute for litigation via domestic courts, and (iii) investment arbitration working as a complement to litigation via domestic courts. In order to conduct a comparative institutional analysis of the three models to reveal their respective tradeoffs, this study employs a goal based approach which is increasingly used to analyze the effectiveness of international adjudicatory mechanisms. As a result of the employment of the goal-based approach, the goals of investor-state dispute resolution are recognized as achieving fair and efficient dispute resolution, promoting state compliance with investment treaty norms, facilitating the objectives of the investment law regime, and legitimizing the underlying investment treaty regime. While the quality of the national judiciaries of many developing countries is not the same as it was decades ago largely due to the judicial reforms launched around the world, fairness and efficiency in dispute resolution still cannot be fully guaranteed in the domestic courts of those countries without a robust legal system and a good record of the rule of law. However, there are certain institutional characteristics of court litigation that may facilitate the efficiency in the resolution of investment disputes, such as the unique advantage of domestic courts that they can work as a single forum for dispute resolution and the better knowledge of court judges of the domestic legal framework at issue. Domestic courts also hold great potential in promoting the compliance by national states with investment treaty norms not least because they have more flexibility in awarding both primary and secondary remedies, but that of course depends on whether domestic courts can adjudicate investment disputes in a fair and impartial manner. Moreover, while utter reliance on litigation via domestic courts may strengthen the domestic rule of law and improve the investment climate in the long term by pressing host states to improve their legal systems and judicial institutions, it may also invite the politicization of investment disputes and the diplomatic intervention from home states in investor-state dispute resolution. Furthermore, despite the risks created for foreign investors, reliance on domestic courts as the exclusive forum may enhance the legitimacy of the investment treaty regime by reducing the sovereignty costs incurred by national states and putting domestic investors and foreign investors on the same footing. Investment arbitration operating as a substitute for domestic courts, on the other hand, demonstrates certain advantages, which are typically affiliated with international arbitration, in achieving the fair and efficient resolution of investment disputes. Unlike domestic courts, which are an integral part of the state apparatus, investment arbitrators are often immune from the influence of domestic politics and are thus believed to be independent and impartial. Meanwhile, the specialization of arbitrators in a particular area of knowledge and the procedural flexibility of arbitration proceedings, among others, are expected to improve efficiency in the resolution of investment disputes. However, empirical evidence presented in the literature sometimes suggests that, in reality, investment arbitrators may not be that unbiased and investment arbitration proceedings often drag on with a bill of a massive amount. Besides, although investment tribunals have a broad scope of jurisdiction over the behavior of different government branches, the practical difficulties they face in awarding primary remedies may damage their ability in promoting state compliance with investment treaty norms. In addition, the introduction of investment arbitration grants to foreign investors a standing in international arbitration proceedings, to a large extent reducing the need for diplomatic protection and home state intervention. However, the positive impact of investment arbitration in facilitating the development of the domestic rule of law and the maintenance and increase of foreign capital is less certain. As for the preservation of the legitimacy of the underlying investment treaty regime, investment arbitration as an alternative to domestic courts cannot be relied on to produce much positive impact. For instance, the increasing sovereignty costs and financial burden imposed on national states would probably prompt more of them to turn against the investment treaty regime. The complement model, in which domestic courts assumes primary jurisdiction and investment tribunals secondary jurisdiction over investment disputes, stands a good chance in keeping the advantages of both court litigation and investment arbitration while avoiding their disadvantages. In the complement model, domestic courts will act as the first line of defense in adjudicating investment disputes, and the institutional advantages of court litigation will be enabled to release their potential. At the same time, even if foreign investors are not satisfied with the judicial outcome or regard the court proceedings as corrupt or unfair, they may escalate the specific disputes to investment tribunals for further consideration. Since court judges are more knowledgeable and experienced in the interpretation and application of domestic law, the legal analysis of court judges will also benefit the decision-making of investment arbitrators in the subsequent arbitration proceeding. Allowing domestic courts to have a first try at investment disputes will also increase the likelihood that primary remedies could be accorded, thus the unique advantages of primary remedies in promoting state compliance with investment treaty norms are not discarded in the complement model. Moreover, the complement model is also more promising in facilitating the achievement of the objectives of the investment treaty regime, and that is because domestic courts are not marginalized in the complement model, the antagonism between foreign investors and host states may be expected to decrease, and the depolicization of investment disputes will not be lost since investment arbitration is kept as an option. Furthermore, the complement model strikes a better balance among the interests of foreign investors, host states and other stakeholders, thus it is more likely to preserve and even enhance the legitimacy of the underlying investment treaty regime than the other two institutional choices. Although the complement model serves the goals of investor-state dispute resolution the best in theory, not any casual combination of court litigation and investment arbitration will do the job; instead, only a smart mix of the two dispute resolution methods can give full play to the advantages of the complement model. Now, we switch to the supervisory role of domestic courts in investor-state dispute resolution. While a systemic appellate mechanism has not been created for investment arbitration, disputing parties may rely on setting-aside proceedings in non-ICSID arbitration to challenge arbitration awards. In other words, domestic courts loci arbitri may conduct a judicial review of the rulings and awards made by investment tribunals. However, a theoretical analysis of the judicial review mechanism supported by empirical evidence has shown that the mechanism has several flaws, which include but are not limited to the points that follow immediately. Since there is only a casual link between the seat of arbitration and the investment dispute, it is inappropriate to subject the decision-making of arbitrators to the judges from the place where the arbitration proceedings took place. The very fact that review courts have been overwhelmingly located within the developed North could raise concern that the judicial review mechanism is inherently biased against developing countries which have already shown a somewhat negative sentiment towards investment arbitration. Given that judicial review proceedings could easily go through more than one instance of court proceedings in many jurisdictions, the dispute resolution process may consume more time and generate higher costs. From this point of view, the judicial review mechanism favors the richer party in investment arbitration and could become a weapon of dilatory tactics available for such a party. Considering the higher error costs relating to investment arbitration than that relating to commercial arbitration, limited review grounds and a copious amount of deference to arbitral tribunals may not prove to be as effective in the scrutiny of investment awards. Moreover, the idiosyncrasies as to review grounds and standards across jurisdictions indicate that inconsistency would also probably permeate the judicial review practices, which would then encourage forum shopping that leads to increased costs and decreased efficiency. In addition, as both review courts and enforcement courts may exercise control over investment awards, the setting-aside decision may be merely disregarded at the enforcement stage and the overall efficiency of investor-state dispute resolution may be reduced. In order to overcome many of the flaws mentioned above, a delocalized form of review should be introduced to take place of the current judicial review mechanism.

Corporate Governance and Women on the Board of Directors : the Legal Framework towards a Minimum Harmonisation in the European Union - Lamy Martin, Joy (Université Paris-Saclay, 2022)
This thesis concerns the recent and considerable change in corporate governance legislation, specifically how boards of directors address the issue of parity and the appointment of its members in public limited companies. This research will challenge European Union law which, to date, does not propose EU harmonization.The UK, France, Germany and Norway (a non-member country but one that will be included in this research) have introduced changes to their national legislation in relation to company boards in public listed companies. This research will focus on a comparative study of parity on company boards under European Union law and its application in the UK (pre-Brexit), Germany, France and Norway. The application of corporate governance codes or soft law and the proposal for a hard law directive demonstrate a fragmentation in the EU, as the application of law by hard quotas divides member states and parliamentarians in European Union law. Corporate governance law in the member states varies considerably, but it must respect the EU's primacy law. Comparisons of legislation between member states reveal the marked differences in law.Women are significantly under-represented on the corporate boards of public limited companies in Europe. Legitimate questions need to be asked. Does the European Commission have the right to make a proposal for a directive allowing for parity on the boards of public limited companies in the EU? The reality is that the Commission does not have a solid approach in dealing with the issue of parity. As long as there is too much inconsistency between Member States, this leaves considerable room for further research. Legislation and governance law between member EU member states diverge considerably and demonstrate inconsistency with the legislation between them, resulting in little or no consensus in the interpretation of EU law. Or member states diverge with opposing interpretations of EU law, especially concerning sovereignty.National legal systems differ considerably in the way legislation allows for the appointment of board members and the notion of parity. A review of corporate governance matters concerning shareholders, the composition and appointment of board members corporate governance codes reveal the gap between member states. The research focus on parity by way of a comparison of the soft and hard laws of the member states.. The research upholds European law Article 157(3) Treaty of the Functioning on the European Union (TFEU), which is the fundamental principle of EU law and basis of gender equality and parity.The research will contribute to raising awareness of this issue through quota legislation and the question of parity on boards in public limited companies in the EU.
Issue: 2022UPASH012
Keywords: Board of directors; Comparative Law; Conseil d'administration; Corporate Governance; Droit comparé; Gender and parity; Genre et parité; Gouvernance des entreprises; Quotas; The European Union; Union européenne

The protection of the national labour force against foreign competition under labour migration laws and policies : a comparative analysis between the Democratic Republic of Congo and South Africa - Kamwimbi, Kasongo Theodore (University of South Africa, 2022)
Labour migration, which involves both labour immigration and labour emigration, refers to ‘the cross-border movement of people from a homeland to a location outside that homeland, with the purpose of taking up employment’.1 Labour migration has become an ever more important feature of the globalising world as it plays an important role and has a direct impact on African countries’ economies and societies. Recognising the significant benefits of labour migration to countries of origin and destination, the African Union urges African States to enact labour migration laws, regulations, and policies in a regular, transparent, and comprehensive manner at both continental and country levels. In this regard, many African countries have exercised their prerogative to regulate labour migration, which falls within each state’s sovereign discretion. By way of illustration, this thesis focuses on two specific countries, namely the Democratic Republic of Congo (DRC) and South Africa, which have regulated the employment of foreign-born workers. The two countries have established a legal and regulatory framework aimed at protecting the national labour force against foreign competition. The two countries have been selected for this study because they are comparable in many ways while differing as much as possible in terms of the institutional set-up of their migration systems and labour markets. In fact, this study seeks to compare the DRC’s and South Africa’s labour migration laws, regulations and policies, particularly how these legal and regulatory instruments effectively protect the national labour force against foreign competition. In this sense, the study explores the overall successes and challenges of these legislative and regulatory endeavours, while identifying the shortcomings and merits of the implementation of the laws and policies in the two countries.
Keywords: Congo (Democratic Republic); Contract of employment; Emigration and immigration law; Foreign workers; Labor laws and legislation; Labour market; Manpower policy; Migrant workers; South Africa

A comprehensive analysis of the law regulating equal pay in South Africa - Ebrahim, Shamier (University of South Africa, 2022)
The purpose of this thesis is as follows. Firstly, to identify the problems associated with the causes of action in section 6(4) of the EEA; the onus in section 11 of the EEA; the right to access pay related information; the grounds of justification in section 6(2) of the EEA and the Employment Equity Regulations; the equal pay provisions in sections 198A-198C of the LRA; and section 27 of the EEA. Secondly, to discuss and analyse the South African equal pay legal framework in order to provide answers and solutions to the research problems. Thirdly, to discuss and analyse the international legal framework regulating equal pay and the United Kingdom equal pay law in order to provide answers to the research questions to the extent and breadth called for. Fourthly, to summarise the answers to the research questions as sourced from South African law, international labour law and the United Kingdom equal pay law.
Keywords: Comparator; Equal pay claims; Equal pay for substantially the same work; Equal pay for the same work; Equal pay relating to non-standard (atypical) employees; Grounds of justification; Hypothetical comparator; Onus in section 11 of the EEA; Right to access pay-related information; Same employer; Section 27 of the EEA; Section 6(4) of the EEA; Sections 198A-198C of the LRA; Subordinate comparator; Terms and conditions of employment

Legal texts on trade facilitation: comparative analysis of the World Trade Organisation and the African Continental Free Trade Area - Shumba, Willie (University of South Africa, 2022)
Trade agreements are a common feature in international economic law as they govern trade relations between states. These agreements are anchored by a firm foundation of the requisite legal provisions to support trade. In this regard, the World Trade Organisation (WTO) and the African Continental Free Trade Area (AfCFTA) have each developed their own legal texts that acknowledge the significance of trade facilitation and would, when implemented, facilitate the movement of goods and services across international borders. The thesis was a comparative analysis of the legal texts on trade facilitation of the WTO and the AfCFTA whose aim was to identify the resemblances and divergences between the two. The WTO has a broader mandate of global trade and ensures that trade amongst its members is conducted in conformity with global rules. On the other hand, the AfCFTA is a trade agreement that has been negotiated by African member states pursuant to the political vision of the African Union (AU), and within the confines of WTO, specifically Article XXIV of GATT 1994. This research was therefore undertaken against the backdrop of these seemingly contradicting circumstances. The central research question for the study concerns the differences and similarities between the legal texts on trade facilitation of the WTO and the AfCFTA. The study was qualitative involving a desktop review of primary and secondary sources of data. Among others, the thesis finds that the AfCFTA complies with the strategic goals of the AU, and at the same time, complements the multilateral trading system of the WTO. The thesis concludes that while there are certain similarities, the legal texts on trade facilitation of the WTO and the AfCFTA are different. The inherent dissimilarities in the texts are not contrary to the principles of the WTO. The thesis contributes to scholarly literature in trade facilitation with respect to both the AfCFTA and the WTO. It also identifies new areas for further studies and provides the necessary groundwork. The study recommends some improvements that can be made to the respective legal texts on trade facilitation.
Keywords: AfCFTA; AfCFTA Agreement; African Continental Free Trade Area; Comparative analysis; Customs union; Free trade area; GATT; General Agreement on Tariffs and Trade; Global trade; International Trade; Legal texts; Multilateralism; Regional Economic Community; Regional Trade Agreements (RTAs); Regionalism; Trade Facilitation Agreement (TFA); Trade agreement; Trade facilitation; World Trade Organization

An evaluation of the strengths and weaknesses of South Africa’s corporate rescue regime as a potential benchmark for Uganda - Waiswa, Abudu Sallam (University of South Africa, 2022)
This thesis evaluates the strengths and weaknesses of the legal framework on corporate rescue in South Africa and Uganda. Although corporate rescue was initially not one of the objectives of insolvency law, it has now become the focus of modern insolvency law. South Africa became the first country to recognise the need to create a legal framework for rehabilitating financially distressed companies when it incorporated judicial management in the Companies Act of 1926. Judicial management was, however, not successful as a corporate rescue procedure. The South African policy makers however continued to explore ways through which financially distressed but viable companies could be saved from collapsing. This culminated into the introduction of business rescue in Chapter 6 of the Companies Act 71 of 2008. The study presents a detailed analysis of the strengths and weaknesses of the South African business rescue framework. It posits that unlike the Ugandan system, the South Africa legal regime reflects the principles of a modern and effective corporate rescue system. Whereas the government of Uganda attempted to embrace corporate rescue through the introduction of administration in the Insolvency Act 2011, the law is devoid of the internationally recognised features of a modern and effective business rescue framework. Administration has remained a white elephant in Uganda’s insolvency system, with liquidation continuing to be the predominant procedure used by both creditors and financially distressed companies. It is recommended that Uganda’s policy makers should benchmark the South African system to reform Uganda’s corporate rescue framework. This thesis is based on the law as at 31st of May 2022, found in the sources available in South Africa and Uganda.
Keywords: Bankruptcy; Business rescue; Corporate insolvency; Corporate insolvency law; Corporate reorganizations; Corporate rescue; Insolvency; Judicial management; Provisional administration; Rescue finance; South Africa; Uganda

Three Essays on Digital Platforms and Competition Policy - Yan, Jun (Université Toulouse 1 Capitole, 2022)
Cette thèse se compose de trois chapitres indépendants et examine différentes questions antitrust liées aux plateformes de gatekeeper. Le chapitre I explore le problème du verrouillage vertical dans les marchés bifaces. Dans le cadre des Accelerated Mobile Pages (AMP) de Google, le chapitre 2 examine la question de l'accès des plates-formes de contrôle d'accès aux données des utilisateurs professionnels. Le chapitre 3 se concentre sur le droit d'auteur numérique et étudie le comportement de Google consistant à utiliser le contenu des éditeurs pour afficher des réponses courtes sur les pages de résultats de recherche.Le premier chapitre examine comment l'intégration verticale d'une plate-forme monopolistique, qui se caractérise par des externalités de réseau bilatérales entre groupes, influe sur son incitation à s'engager dans le verrouillage en aval. Je me concentre sur un environnement où la plate-forme et les vendeurs en aval sont confrontés à l'incertitude quant aux gains du commerce au stade de la passation des marchés. Le choc aléatoire étant non contractile, la contractualisation crée des frictions qui faussent la structure tarifaire de la plateforme. En revanche, l'intégration verticale atténue ce problème en permettant à la plate-forme d'intégrer le choc aléatoire des prix à la consommation. En raison de l'interaction entre la friction des transactions et les externalités de réseau intergroupes, je trouve que l'intégration verticale pourrait réduire l'incitation de la plate-forme à la forclusion.Le deuxième chapitre est un travail conjoint avec Doh-Shin Jeon. Nous étudions comment l'adoption par les journaux d'AMP, un format de publication qui permet le chargement instantané de pages Web dans les navigateurs mobiles, modifie l'allocation des données et, par conséquent, les incitations des journaux à investir dans un journalisme de qualité. L'adoption d'AMP permet à Google d'obtenir des données sur les consommateurs à partir d'articles AMP et de les combiner avec d'autres sources de données sur les consommateurs pour améliorer le ciblage des publicités diffusées par Google sur d'autres sites Web. Même si une telle combinaison de données augmente l'efficacité statique, elle peut réduire l'efficacité dynamique lorsqu'elle diminue les revenus publicitaires par trafic de journal, réduisant ainsi la qualité du journalisme. Les journaux sont confrontés à un problème d'action collective car l'adoption de l'AMP par un journal génère des externalités négatives pour les autres journaux via le classement des recherches et la fuite de données. Google peut tirer parti de son pouvoir de marché dans la recherche et l'intermédiation publicitaire pour inciter les journaux à adopter AMP. Nous fournissons des recours politiques.Le troisième chapitre construit un modèle théorique de biens d'information divisibles pour examiner comment l'utilisation d'extraits par un moteur de recherche monopolistique impacte la consommation et la création de contenu. En affichant des extraits dans la zone de réponse sur les pages de résultats de recherche, le moteur de recherche dissocie les informations essentielles et les informations supplémentaires des articles. Elle crée donc deux effets opposés sur l'incitation des éditeurs à investir dans la qualité : l'effet de taille du marché et l'effet d'élasticité. Son impact sur le bien-être social est ambigu. D'une part, la boîte de réponse améliore l'efficacité de la recherche en offrant un accès plus large aux informations essentielles et en permettant aux consommateurs inframarginaux de substituer les informations essentielles à l'article complet. D'un autre côté, cela pourrait réduire le trafic sur le site Web, réduire les revenus publicitaires des éditeurs et les inciter à investir dans la qualité. J'examine les impacts des différentes politiques qui obligent le moteur de recherche à payer pour l'utilisation d'extraits.
Keywords: Antitrust law; Competencia; Competition Policy; Competition law; Concurrence; Concurrence (droit); Digital Platforms; Economie des médias; Google; Intellectual property; Marché biface; Media Economics; Online Advertising; Plateformes digitales; Propriedade intelectual; Propriété intellectuelle; Publicité en ligne; Technologies de l'information et de la communication – Aspect économique; Two-Sided Market

EU copyright reform : an institutional approach - Mangal, Natasha (Université de Strasbourg, 2022)
Cette thèse a pour objet d’étudier comment le dispositif institutionnel actuel pour l’adaptation du droit d’auteur dans l’Union européenne peut être reconsidéré afin de promouvoir le niveau de cohérence plus élevé dans les pratiques réglementaires des États membres, ainsi que dans l’intérêt de la promotion d’un corps de règles européennes plus dynamiques en la matière.À l’aide de l’outil normatif de l’analyse institutionnelle comparative, les dispositions institutionnelles actuelles sont examinées, en se concentrant sur la qualité de la participation des parties prenantes du droit d’auteur dans le système politique, le marché et les tribunaux. Des exemples d’institutions administratives du droit d’auteur dans certaines juridictions (États-Unis et Canada) sont analysés plus en détail, en tirant des conclusions sur leurs fonctions et leurs rôles dans leurs systèmes juridiques respectifs. Enfin, cette thèse propose plusieurs solutions politiques, y compris la possibilité d’envisager une nouvelle autorité au niveau de l’Union européenne pour le droit d’auteur. En fin de compte, la remise en question du statu quo institutionnel dans l’Union européenne peut révéler de nouvelles voies prometteuses pour développer les fonctions administratives, quasi judiciaires, d’observation et de conseil nécessaires à la gestion du droit d’auteur à l’ère du numérique.
Keywords: Analyse institutionnelle comparative; Comparative Institutional Analysis; Copyright; Digital Single Market; Droit de la propriété intellectuelle; Droit d’auteur; Droits d'auteur; Institutions; Intellectual property; Intellectual property law; Marché unique numérique; Union européenne

Performance and rarity of worker-owned firms : empirical evidence from France - Mirabel, Thibault (Université Paris 10, 2022)
This thesis compares the performance of worker-owned firms (WOFs) and conventional firms (CFs). These firms differ by their distribution of ownership rights and their mode of governance. In WOFs, the ultimate control is held by the suppliers of labor, whereas in CFs the ultimate control is held by the suppliers of capital. WOFs represent an implementation of democracy in firms and, as such, are likely to be immune to institutional harassment and socialwashing. WOFs have also been supported by citizens, politicians, and economists from across a wide ideological spectrum. Despite their attractiveness, WOFs represent a minute proportion of firms in our contemporary economies. This thesis seeks to bring new insights and stylized facts to better understand the rarity of WOFs. Chapter 1 studies how the interaction of the sunk costs of human capital and physical capital impacts the probability of WOF entry. I show that the likelihood of WOF entry is the highest when the sunk cost of human capital is dominant while the sunk cost of physical capital is negligible. Chapter 2 compares the survival patterns of WOFs and CFs. I show that WOFs survive longer than CFs regardless of whether they have different or similar entry resources, and that some entrepreneur and firm characteristics impact WOF and CF survival differently. Chapter 3 compares the survival patterns of WOFs distinguished by their entry mode (i.e., newly created, worker buyouts of sound CFs, worker buyouts of CFs in difficulty, and worker buyouts of nonprofit organizations). I show that any type of worker buyout survives longer than newly created WOFs. Overall, this thesis suggests that the rarity of WOFs is more likely to result from entry barriers specific to WOFs rather than from poor performance compared to CFs. Cette thèse compare la performance des coopératives de travailleurs (SCOPs) et des entreprises conventionnelles (ECs). Ces entreprises diffèrent par leur distribution des droits de propriété et leur mode de gouvernance. Au sein des SCOPs, les travailleurs ont le contrôle ultime de leur entreprise. Les SCOPs instituent la démocratie dans le monde économique et, à cet égard, furent et sont encore défendues par des économistes appartenant à une large palette idéologique. Malgré leur attractivité, les SCOPs représentent une fraction minuscule des entreprises dans le monde. Cette thèse entend apporter des éléments nouveaux pour comprendre la rareté des SCOPs. Le Chapitre 1 étudie comment l’interaction des coûts échoués en capital et en travail impacte la probabilité de créer une SCOP. Je montre que la probabilité de créer une SCOP est maximale lorsque le coût échoué en travail est dominant et que le coût échoué en capital négligeable. Le Chapitre 2 compare les profils de survie des SCOPs et des ECs. Je montre que les SCOPs survivent plus longtemps que les ECs indépendamment du fait que leurs ressources à l’entrée diffèrent ou non. Je montre aussi que certaines caractéristiques de l’entrepreneur différemment la survie des SCOPs et des ECs. Le Chapitre 3 compare les profils de survie des SCOPs en distinguant quatre modes d’entrée (les SCOPs nouvellement créées, les reprises d’entreprises saines, les reprises d’entreprises en difficulté et les reprises d’organisations à but non-lucratif). Je montre que les reprises en SCOPs survivent plus longtemps que les SCOPs nouvellement créées. Dans l’ensemble, cette thèse suggère que la rareté des SCOPs est due à des barrières à l’entrée spécifiques aux SCOPs plutôt qu’à leur prétendue moindre performance vis-à-vis des ECs.
Keywords: Coopératives; Coopératives ouvrières de production; Coûts échoués; Democracy; Efficacité de l'organisation; Entry mode; France; Mode de création; Participation à la gestion; Performance; Personnel; Scop; Sunk costs; Survie; Survival; Worker-owned firms; Études comparatives

An examination of the challenges posed by the internet economy for the South African income tax regime - Odhiambo, Oluoch Rodney (University of South Africa, 2022)
The way of doing business has changed significantly since the turn of this century due to the growth of internet technology and the global digital economy. This growth has reduced the importance traditionally attached to tangible assets and physical location in both commerce and taxation. This implies that any country that relies on physical presence to trigger tax liability in today’s digital economy may be forced to reconsider the relevance, effectiveness, and efficiency of its income tax legislation. This thesis postulates that South Africa’s income tax law and the international taxation principles it relies on in taxing cross-border and digital transactions have not grown in tandem with the changing landscape of today’s digital economy. The thesis contends that South Africa will not receive its fair share of tax from giant multinational enterprises such as Google, Facebook, and Amazon which operate and trade in the country, if it does not amend its income tax laws to address the challenges posed by the internet economy. In examining the challenges posed by the internet economy to South Africa’s income tax regime, the thesis commences in Chapter 2 by discussing the growth of the digital economy and its implications for South Africa’s income tax system. Chapter 3 offers a critical analysis of South Africa’s income tax laws and the international principles on which they rely in taxing the digital economy. Chapter 4 discusses the measures that South Africa’s government has taken to tax its digital economy, while Chapter 5 compares how the Organization for Economic Cooperation and Development (OECD), the European Union (EU), Kenya, India, and New Zealand have dealt with the issue of taxing the digital economy and the lessons to be learned from these jurisdictions. The thesis concludes in Chapter 6 by proposing recommendations that South Africa could consider to make its income tax regime more efficient and effective in taxing transactions that take place in today’s digitised economy.
Keywords: Cryptocurrency; Digital economy; Digital tax; E-commerce; E-signature; Electronic commerce; Formulary apportionment; Income tax; Internet industry; Signature électronique; Taxation; Virtual currency

The use of MASS in the context of International Law of the Sea - Mandrioli, Daniele (Università degli studi di Milano, 2022)
L'automatisation et la numérisation redéfinissent l'ergonomie des comportements humains. En se limitant au domaine maritime, les nouvelles technologies permettent d'automatiser entièrement l'activité traditionnelle de la navigation ; aujourd'hui, les navires peuvent être contrôlés depuis le rivage et l'intervention humaine dans la boucle de décision n'est plus nécessaire.Cette innovation disruptive offre de grandes opportunités pour l'industrie maritime. Intuitivement, les profits tirés du transport de marchandises et de personnes en mer peuvent être maximisés ; la réduction ou l'absence d'équipage à bord entraîne une réduction considérable des coûts pour les opérateurs (et pour les consommateurs), surtout en cette période historique marquée par la propagation mondiale du virus SARSCOV-2. En ce qui concerne la sécurité maritime, l'innovation que constitue le contrôle autonome réduit fortement le risque d'accidents dus à des erreurs humaines, qui sont à l'origine de la plupart des accidents maritimes. En ce qui concerne la protection de l'environnement marin, la navigation autonome peut en outre rendre le transport maritime plus durable.Pour ces raisons, les États et les entités privées financent plusieurs projets de développement de navires autonomes : au cours des dernières années, les premiers navires de surface autonomes (ci-après dénommés MASS) ont été testés et produits. En l'état actuel des connaissances, l'adoption de cette nouvelle technologie n'est plus un événement futuriste : plus d'un millier de MASS naviguent actuellement sur les océans du monde.Étant donné que l'activité humaine de la navigation est sujette à des changements, on peut se demander si les règles internationales qui la régissent sont d'une certaine manière remises en question par l'essor de l'automatisation.Habituellement, une nouvelle invention technologique s'accompagne de nombreuses questions réglementaires. D'une part, la loi est tenue de contrôler et de prévenir les conséquences involontaires découlant du recours à la nouvelle technologie. D'autre part, la loi est appelée à admettre et à autoriser son utilisation.Par conséquent, l'objectif de cette thèse est d'étudier les implications juridiques internationales découlant de l'utilisation croissante des moyens autonomes de transport maritime. En quelques mots, il s'agit ici d'aborder la question de savoir si et comment le recours à la technologie MASS a un impact sur le cadre juridique international préexistant qui régit l'exécution de la navigation et le contrôle de l'Etat sur celle-ci.Au cours des dernières années, ce sujet a suscité une attention croissante. En particulier, en 2019, le Comité de la sécurité maritime (CSM) de l'OMI a approuvé les "Directives provisoires pour les essais de navires autonomes de surface (MASS)". En outre, l'Organisation a très récemment achevé le "Regulatory Scoping Exercise on Maritime Autonomous Surface Ships" (ci-après RSE), qui avait débuté trois ans auparavant.La recherche proposée veut s'inscrire dans ce débat ouvert (et le dépasser) afin de fournir un panorama étendu des implications juridiques internationales émergeant de l'utilisation de l'automatisation et du contrôle dans le domaine maritime. Ce faisant, l'attention se concentrera sur trois blocs normatifs : les règles internationales sur la sécurité de la navigation (chapitre I), les règles internationales régissant l'attribution de la juridiction des États sur les navires (chapitre II) et les règles internationales traitant de l'assistance aux personnes trouvées en détresse en mer (chapitre III).
Keywords: Commande automatique; Droit de la mer; Droit maritime; Law of the Sea; Mass; Navires; Pilotes automatiques (navigation); Ships; Systèmes de guidage

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

The Economics of Trade, Innovation and the Technology Revolution - Tharwat, Ismaeel (Université Paris-Saclay, 2022)
Cette thèse étudie principalement l'impact du commerce international sur l'innovation, avec un accent particulier sur les pays en développement. Elle couvre également l'impact des retombées commerciales sur les inégalités de genre. Le chapitre 1 présente un aperçu de la littérature économique théorique et empirique récente traitant de l'effet de la concurrence des importations sur les résultats liés à l'innovation. Ce chapitre est divisé en quatre sections. Tout d'abord, un historique des brevets et des marques déposées en tant qu'indicateurs d'innovation est présenté. Deuxièmement, les mécanismes théoriques qui sous-tendent l'impact de la concurrence des importations sur l'innovation sont discutés. Troisièmement, une revue de la littérature des études empiriques récentes sur le commerce et l'innovation est résumée. Enfin, une analyse empirique est menée pour examiner l'impact de la concurrence des importations chinoises sur l'innovation, mesurée par l'activité de dépôt de brevet, dans les pays en développement.Le chapitre 2 est un exercice empirique qui examine l'impact de la concurrence des importations chinoises sur l'innovation, en utilisant une nouvelle mesure qui est le dépôt de brevet. L'étude utilise un ensemble de données de panel de 1995 à 2018 sur plus de 100 pays en développement. Le modèle empirique corrige l'endogénéité en utilisant une approche de variable instrumentale qui permet d'identifier la part du développement dû aux importations chinoises dans d'autres pays en développement. Les principales estimations trouvent un effet global décroissant de la concurrence des importations sur l'activité de dépôt de brevet. Les résultats de la variable instrumentale sont particulièrement robustes pour les demandes de brevet, mais pas pour les enregistrements. Cela suggère que la concurrence des importations affecte négativement les nouvelles innovations locales de produits ou de services dans les pays en développement.Enfin, le chapitre 3 aborde la question de l'impact des retombées du commerce international sur les normes d'égalité de genre. La majorité des études existantes documentent l'effet des épisodes de libéralisation sur les inégalités de genre. Celui des acteurs commerciaux, en revanche, a été largement ignoré. L'inégalité de genre au sein d'un pays est-elle affectée par ses partenaires commerciaux? Nous avons examiné cette question dans cet article en adoptant un modèle spatial du commerce entre 123 pays sur la période 1997-2013. Nous utilisons l'indice d'inégalité de genre pour capturer les tendances globales sur le genre au sein d'un pays. Nous avons ensuite désagrégé les échanges commerciaux au niveau produits afin d'identifier un canal technologique. Les résultats montrent que des normes d’égalité de genre plus élevées à l'étranger se répercutent, via les importations de produits de moyenne, haute technologie et minéraux, sur des normes d'égalité de genre plus élevées au niveau national. Ces résultats suggèrent qu'une révolution technologique affecte les entreprises, les ménages et les gouvernements en ayant un impact sur l'autonomisation des femmes.
Keywords: Brevets; Brevets d'invention; Economie du genre; Economie internationale; Gender Economics; Innovation; International Trade; Marques commerciales; Marques de commerce; Patents; Technologie; Technology; Trademarks; Économie de marché; Études sur le genre

The legal framework for multimodal transport in West Africa: the African Continental Free Trade Area in perspective - Osinuga, Damilola (World Maritime University, 2022)
This thesis examines how multimodal transport can play a role in achieving the objectives of the African Continental Free Trade Area (AfCFTA). The thesis argues that multimodal transport is cheaper compared with unimodal transportation. While there are a number of issues affecting the operationalisation of multimodal transport in Africa, this study considers, at its core, the legal regimes and other fragmented institutional and governance frameworks of multimodal transport in West Africa. The fragmentation of the legal framework governing multimodal transport leads to uncertainty and unforeseeability of the liability of parties involved in multimodal transport, consequently leading to increased legal costs. There is an undisputed view that for effective regional integration, which Africa is seeking to achieve through the establishment of the African Continental Free Trade Area, there is a need to eliminate all trade barriers. Trade barriers (tariff or non-tariff barriers) should be removed to improve competitiveness and reduce trade friction costs. In other words, to achieve the objectives of the African Continental Free Trade Area, it is essential that all unnecessary costs associated with trade are eliminated or reduced to the barest minimum. The process of doing this is called trade facilitation. This thesis looks at the impact of trade facilitation on regional integration and trade. This thesis’ original contribution to knowledge is that Africa’s regional integration process needs cost-effective transportation in order to achieve smooth market access, and multimodal transportation can provide the most cost-effective solution. However, the legal uncertainty and complexities that could potentially ensue from the use of multimodal transport make it unattractive to prospective users. Accordingly, actions must be taken to reduce legal ambiguity and create a system in which liability is foreseeable and predictable. This study reveals that the current legal framework is incomplete, unsatisfactory and, ultimately, leads to uncertainty. The thesis further contends that neither the option of freedom of contract nor improving the current system of various Economic Community of West African States (ECOWAS )member-states’ view of multimodal transport, can significantly improve the current fragmented system or deliver the needed certainty. Accordingly, the thesis proposes that a modified uniform system would help achieve the legal certainty needed for multimodal transport. The thesis finally submits that the ECOWAS should establish a legally binding, regional governance regime on multimodal transport and a majority of its member-states should ratify the instrument.

Foreign Bank Penetration, Institutional Structures and Banking Sector Stability in Sub-saharan Africa - Abeka, Mac Junior (University of Cape Coast, 2022)
Link broken
Keywords: Bank penetration; Banking sector; Sub-Saharan Africa

The rising role of China and Chinese enterprises in transnational labour law: Theoretical inquiries and case studies in the context of Chinese outward mining investment in Africa - Chen, Si (McGill University, 2022)
Transnational labour law scholarship has emerged over the past three decades. However, relatively limited scholarship has explored the role of actors from emerging market economies and the challenges and opportunities they have brought for achieving decent work in a globalized economy. This thesis addresses the research gap through an in-depth investigation into the role of actors from China in the dynamics of multi-level governance of labour rights in a globalized economy. Building on a multi-level, actor-centred and processual approach, this thesis argues that China and Chinese enterprises are playing a rising role in developing and shaping the dynamics of multi-level governance of labour rights in the global cobalt supply chain. Furthermore, the thesis suggests that actors from China have started challenging some unequal patterns of existing labour governance in the global cobalt supply chain and have demonstrated the potential to form a counterbalancing force to challenge the dominant role of actors from the global North. A multi-level governance framework has recently emerged and rapidly evolved in the global cobalt supply chain to eliminate child labour in the artisanal copper-cobalt mining sector in the Democratic Republic of the Congo. This framework is complex, pluralistic, and decentred. A wide range of state and non-state actors are developing various governance initiatives and shaping the dynamics of multi-level governance. Actors from China are playing a rising role in the global cobalt supply chain alongside a few other actors that have also provided proposals from the global South. Over the past decade, Chinese state agencies, nationwide industry associations and mining enterprises have proactively engaged in developing and shaping the multi-level governance framework to address governance deficits on decent work in the global cobalt supply chain. State agencies have developed various regulatory documents to enhance the social dimension of the Chinese regulatory framework for outward foreign direct investment. Nationwide industry associations have further conceptualized the term “corporate social responsibility” and have taken labour rights as key to the social responsibilities of Chinese enterprises operating overseas. Specifically, a Chinese nationwide industry association for the mining industry has developed comprehensive guidelines and initiatives to clarify and operationalize the labour component of social responsibilities in Chinese outward mining investment. The changing dynamics of multi-level governance have played a crucial role in shaping the private labour governance initiatives that Chinese mining enterprises are developing in the global cobalt supply chain. The contributions of this thesis are original, significant, and timely, given the notable research gaps on China and Chinese enterprises’ engagement with the dynamics of multi-level governance of labour rights in a globalized economy and the ongoing development of a multi-level governance framework in the global cobalt supply chain
Identifier: https://escholarship.mcgill.ca/concern/theses/7d2790853
Keywords: Chinese enterprise; Droit du travail; Investment in Africa; Labour law; Transnational labour law

Local Content Requirements in WTO Law: Between Free Trade and the Right to Development - De Lima Figueiredo, Natalia (Maastricht University; Universidade de São Paulo, 2022)
In the international arena, there is a strong rhetoric against a type of industrial policy measure called local content requirements (LCRs). They are often characterised, especially by developed countries, as protectionist measures. However, under certain circumstances, LCRs can have a central role in a country’s development process. Indeed, both developed and developing countries use them to boost their economies. Despite this developmental aspect of LCRs, WTO (World Trade Organization) rules restrict their use. The WTO Agreement, however, has a development dimension and WTO law is supposed to be read in light of the wider corpus of international law. The right to development, in turn, is a principle rooted in core human rights treaties, is consolidated in several instruments of soft law nature and could potentially play a role in the interpretation of WTO provisions. In this scenario, the thesis investigates if it is possible to further a development-oriented interpretation of WTO rules affecting LCRs so that those measures that incorporate genuine development goals are not considered a violation of WTO rules.
Keywords: Development; Free Trade; Human rights; Local content requirements (LCRs); WTO; World Trade Organization

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
https://phaidra.univie.ac.at/detail/o:1417287
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

Sanitary and phytosanitary measures as barriers to trade : a South African perspective - Joubert, Biandri (North-West University, 2022)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health, within World Trade Organization (WTO) Member territories, from the risks associated with the introduction and spread of pests and diseases into such territories through trade. The WTO, through its Agreement on the Application of Sanitary and Phytosanitary Measures (WTO-SPS), guides the application of sanitary and phytosanitary measures and provides a set of guiding principles, rights and obligations applicable to Member States. Dispute resolution through the processes of the WTO is available to Members on a Member to Member level within a defined scope and on specific terms. Private parties who operate within the SPS chain at a national level, whether involved in import or export or neither, are dependent on solutions to barriers or disputes available to them through national legislation. In the absence of an enabling legal framework to facilitate aspects of trade such as certainty and continuity in standard setting, the basis of measures taken in science, transparency and legal recourse to resolving barriers or disputes arising, private parties are vulnerable to fluctuations in, for example, their country’s disease-free status. Private parties are also vulnerable to losing relevance as trading partners in periods of ongoing SPS events and to the loss of trust that trading partners have in the country’s ability to trade safely. These are matters that affect private parties who do not have legal recourse to the WTO dispute resolution procedures which are well within WTO concern as they are directly related to the purpose of SPS measures, the principles, rights and obligations on which they are based. Given the importance of agriculture and the increasing inseparability of international rights, obligations and principles in a field of WTO law such as SPS, the importance of a national legislative framework in as far as being the translator of such rights, obligations and principles into legally enforceable rights, obligations, principles, processes and procedures is significant. The rights, obligations, and principles of SPS measures apply to all products, processes and procedures that are within the scope of the agreement and may include at least 36 chapters of the harmonised tariff book. It is necessary to consider also that international trade, national trade and the associated rights, obligations, and principles of the WTO-SPS agreement interact with the social, political, and economic realities of the country within the countries to which the agreement applies. Therefore, researching some of the persistent challenges experienced by the red meat industry in South Africa prone to negative trade-related consequences during and after the outbreak of a notifiable disease, provides insight into the perception of the ability of the legislative framework to provide solutions to these consequences. This research applies a mixed methodology approach whereby qualitative research by means of semi-structured interviews was combined with doctrinal legal research and a quantitative content analysis using Rprogramming. The qualitative research focused on the role of legislation and the perspectives of selected actors in the red-meat industry, specifically in reference to the foot-and-mouth-disease (FMD) outbreaks and subsequent loss of disease-free status since 2019. The doctrinal legal analysis and content analysis focused on the SPS-related legislative framework. The combination of these methods provides a multi-perspective analysis of SPS measures as barriers to trade from a South African perspective and contributes to the mixed-methods turn in legal studies. The objective of this research is to identify and explore persistent challenges to the prevention and resolution of barriers or disputes connected to sanitary and phytosanitary (SPS) measures in the South African context. Ultimately, this research recommends potential practical solutions to the identified challenges with specific focus on SPS-related barriers or disputes that are beyond the strict terms of dispute resolution available through the World Trade Organization (WTO).
Keywords: AfCFTA; Barriers to trade; CADA; CAQDSA; Content analysis; Dispute resolution; FMD; NTB; OIE; Qualitative research; Rstudio; SADC; SPS; Sanitary and phytosanitary measures; WTO

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
URI: http://hdl.handle.net/1828/14772
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

Climate change and development : the global administrative law of the UNFCCC financial mechanism - Larrea, Gonzalo (European University Institute, 2022)
This research deals with the legal responsibility of states to provide climate finance to developing countries in order to facilitate climate mitigation and adaptation. The research demonstrates that the area of climate finance has not escaped globalization, where global actors operating at a level beyond the state (the UNFCCC and several Climate Funds) have increasingly taken over some of the climate finance functions previously performed by states. Against this backdrop, the thesis also examines the role of international bodies in providing climate finance, assesses to what extent these bodies are accountable to affected local stakeholders, and puts forward recommendations to foster increased accountability. The research project employs Global Administrative Law (GAL) as a normative framework for assessing and fostering accountability. This thesis is relevant, first and foremost, as an examination of the extent to which global climate finance is adequate for addressing climate change impacts in developing countries. To this end, it engages in a detailed analysis of the international legal framework for climate change and of the relevant financial instruments. It also engages in a normative evaluation of these instruments using the standards proposed by GAL. In keeping with this, the research gives substance and a better definition to these standards. As such, the thesis has the potential to contribute not only to the literature on climate finance, but also to the literature on GAL. It also sheds light on the relationship between climate finance and GAL, a topic that has been largely neglected in the academic literature so far.
Accepted: 2022-03-02T09:10:59Z
Keywords: Climate Change; Climatic changes; Environmental Law

Letters of credit and demand guarantees : a legal study on the impact of targeted financial sanctions from a South African perspective - Lupton, Cayle Selwyn (University of Johannesburg, 2022)
The purpose of this study is to provide a legal analysis of the impact of targeted financial sanctions on letters of credit and demand guarantees. The letter of credit is an important method of payment used in international trade. The demand guarantee plays a significant role as an instrument of security in commercial transactions. In their simplest form both instruments constitute an undertaking by a bank to pay a beneficiary against delivery of certain stipulated documents. Letters of credit and demand guarantees are known to be reliable and provide a considerable measure of certainty and predictability to the underlying transaction. Consequently, they have been described as the “lifeblood of international commerce”. Targeted financial sanctions entail assets freezing and prohibitions to prevent funds or other assets from being made available, directly or indirectly, for the benefit of designated individuals and entities. Endorsed by the United Nations and implemented by the vast majority of jurisdictions around the world, targeted financial sanctions are increasingly being used to combat financial crime, including money laundering, terrorism financing and weapon proliferation financing. Banks play a critical role in financial crime prevention and detection. Hence they have been identified as institutions that must comply with targeted financial sanctions. The relationship between targeted financial sanctions and letters of credit and demand guarantees has generally not been well documented. It is hoped, therefore, that this study will make a meaningful contribution to the jurisprudence on letters of credit and demand guarantees. In investigating the impact of targeted financial sanctions, the study can be categorised into three parts. Part one investigates a bank’s compliance with domestic targeted financial sanctions. The chief findings of the study in this regard are that banks are under a legal obligation to comply with sanctions and, as a result, a bank that refuses to perform its contractual obligations under a letter of credit or demand guarantee may have a defence in law. In South African law the bank can raise the so-called defence of legal impossibility of performance to resist a claim for, or potential litigation in respect of, payment. Part two investigates a bank’s compliance with foreign targeted financial sanctions. Because compliance in this regard has no (legal) basis, the bank may conceivably be sued by the beneficiary for payment on the basis of breach of contract. Part three investigates problematic documentary practices that banks have adopted or conceivably may adopt to manage their sanctions risk exposure. In this regard, attention is given to so-called sanctions clauses and other non-documentary conditions. The issue of unjustified amendments by the beneficiary for the purposes of sanctions evasion is also considered in part three. The general conclusion arrived at is that by interfering with payment, targeted financial sanctions render letters of credit and demand guarantees unreliable, thereby having the effect of reducing their value to international trade and commerce. The author proposes certain recommendations and initiatives aimed at mitigating the impact of targeted financial sanctions on credits and guarantees. Key terms: letters of credit; demand guarantees; financial crime; sanctions evasion; targeted financial sanctions; compliance; banks; due diligence; payment; reimbursement; credits; guarantees.
Keywords: Banks; Compliance; Credits; Demand guarantees; Due diligence; Financial crime; Guarantees; Letters of credit; Payment; Reimbursement; Sanctions evasion; Targeted financial sanctions

Airport Charges Regulation: A Private Law Approach - Mei, Di (McGill University, 2022)
This thesis explores the regulation of airport charges, which is an important but marginalised topic. It particularly examines how private law instruments can play a role in the regulatory process. Airports used to be subject to traditional regulation, which operates in a command-and-control mode. As the airport industry becomes increasingly complicated, traditional regulation seems problematic. First, the method that is associated with traditional regulation to draw a line between regulated and unregulated airports has downsides. Second, the international regulatory framework on airport charges lacks binding rules. This suggests that traditional regulation is not the best niche for airport charges regulation. Third, good regulation needs independent regulatory bodies, which are hard to achieve in practice.In this context, this thesis argues that a private law approach can serve as a more flexible and effective way to regulate airport charges. There are two instruments under this overarching approach. First, contracts can be adopted to incorporate airport charges regulations. Second, robust corporate governance generates the effect of good regulation. This is an interdisciplinary work that has engaged air law, contract law, corporate law, competition law, and aviation business and management. It also employs the method of case studies. Chapter 4 examines the regulation of airport charges in the UK, Canada, and India. The three case studies demonstrate that private law instruments have been implicitly implemented to different degrees in these countries. These demonstrate the feasibility of applying private ordering in the regulatory process. I also look into the regulation of countries and regions including Australia, Ireland, the EU, and Germany throughout this thesis. This study also examines a specific sector of airport charges, namely, charges for ground-handling services. This sector possesses a unique feature in that it is between aeronautical and non-aeronautical services. A private law approach can also be adopted in the regulation of charges relating to ground-handling services. Additionally, ICAO as an important international organisation governing international air transport can also contribute to a private law approach of airport charges through its soft-law making function. This thesis aims to shed light on a private law approach, as an innovative regulatory mechanism, to airport charges. That said, regulation by this approach and traditional regulation are not contradictory but can cooperate to an extent, depending on how much power one wants to give to private ordering
Identifier: https://escholarship.mcgill.ca/concern/theses/8910k0504
Keywords: Airport; Regulation

Articulating clearer fair and equitable treatment clauses within Tanzania’s international investment agreements: correcting the disparity between host state and international investor interests - Ntangeki, Joanitha (Canterbury Christ Church University, 2022)
International Investment Agreements seek to promote foreign investment whilst protecting foreign investors. Despite the goal of International Investment Agreements being to secure parity between the interests of the host State and the foreign investor, there has been consequential disparity in the protection of the interests of both parties. Notably, the host State is susceptible to disadvantage. This research examines the extent to which International Investment Agreements in Tanzania have facilitated this disparity. In particular, the research evaluates the inclusion of fair and equitable treatment provisions in Tanzania’s International Investment Agreements and the extent to which fair and equitable treatment provisions have in some way facilitated this disparity. The research examines systematically the fair and equitable treatment provisions contained in twenty IIAs signed by Tanzania between 1965 and 2013 (eleven of which are still in force). The research takes a comparative approach in evaluating and contrasting the Tanzanian provisions with other fair and equitable treatment clauses in IIAs signed by India, Morocco and the Netherland. The Tanzanian provisions are vague and non-uniform in comparison. The research is situated in the broader context of national sovereignty and the relationship between Tanzania and its foreign investors under international law. The substance of the analysis centres on foreign investors in the mining sector in Tanzania and the extent to which these investors have sought to take advantage of the fair and equitable treatment clauses in the IIAs in order to pursue their activities to the detriment of local populations. The research evidences the negative impact of their claims that changes in government policy (often aimed at benefiting citizens) amount to unfair treatment of the foreign investor. This has a significant impact on the ability of the government to develop its policies around sustainable development, environmental protection and the guarantee of human rights of the citizens of the host State. The research demonstrates that a clearer and fuller articulation of fair and equitable treatment clauses within Tanzania’s IIAs can act as a corrective to the disparity between the host State and the international investor. This requires that IIAs are drafted to include an exhaustive and full list of the State’s obligations towards the foreign investor so as to limit foreign investor claims against the host State. The impact of not doing so has grave implications for the rights of the citizens of Tanzania and unnecessarily tips the balance of power in favour of the foreign investor and away from the host State. This undermines the ability of the host State to assert its sovereignty within its own borders.
Permalink: https://repository.canterbury.ac.uk/item/9714v/articulating-clearer-fair-and-equitable-treatment-clauses-within-tanzania-s-international-investment-agreements-correcting-the-disparity-between-host-state-and-international-investor-interests
Keywords: Foreign investment; International investment; Investor interest; Tanzania

Story of a legal codex(t) : writing law in code - Ma, Megan (Institut d'études politiques, 2021)
How is the law measured? For long, it appeared that the law cannot be measured. While there are standards and processes, the law was not regarded as quantifiable. Only in the advent of recent technological advancements in law have there been considerations for metrics. These technologies sought to tackle the legal field’s inherent protectionism fueled by deep asymmetries in information. Consequently, the rise in legal ‘metrics’ stems from an access to justice perspective. The assumption is that in making the law more quantifiable, knowledge that has been historically opaque and inaccessible outside of the legal community may be revealed.Alternatively, it may be argued that the law has always been measurable. Words, through linguistic devices, have shaped legal meaning. In effect, the law conceivably has been measured by its words. In fact, “law exists as text” (Hildebrandt, 2015). I further this line of thinking by investigating natural language as the key vessel through which the law has manifested itself. Does the law depend on natural language to do its work? Importantly, is the language sufficient at housing legal norms?This dissertation seeks to tell a narrative. Broadly, it chronicles the story of law’s intimate relationship with language. But more specifically, the thesis details the law’s recent encounter with the digital. When law met technology, its relationship with language changed, invoking skepticism around its fitness for the conveyance of legal concepts. With the introduction of an innovative player – code – the law had perceivably found its new linguistic match. As a result, code was tested for its ability to perform and accommodate for the law’s demands. Ultimately, confronted by natural language and code, the law is asked whether code can be its language. Comment mesure-t-on le droit ? Longtemps, le droit semblait résister à la mesure. Bien qu'il existe des normes et des processus, le droit n'était pas considéré comme quantifiable. Ce n'est qu'avec l'avènement des récentes avancées technologiques dans le domaine du droit que l'on a commencé à envisager une telle quantification. Ces technologies ont cherché à s'attaquer au protectionnisme inhérent au domaine juridique, alimenté par de profondes asymétries d'information. Par conséquent, l'essor de la "métrique" juridique découle d'une perspective d'accès à la justice. L'hypothèse est qu'en rendant le droit plus quantifiable, des connaissances historiquement opaques et inaccessibles en dehors de la communauté juridique peuvent être révélées.On peut également faire valoir que le droit a toujours été mesurable. Les mots, par le biais de dispositifs linguistiques, ont façonné la signification juridique. En effet, il est concevable que le droit ait été mesuré par ses mots. En effet, "le droit existe en tant que texte" (Hildebrandt, 2015). J'approfondis cette ligne de pensée en examinant le langage naturel en tant que vecteur clé à travers lequel le droit s'est manifesté. La loi dépend-elle du langage naturel pour faire son travail ? Plus important encore, le langage est-il suffisant pour abriter les normes juridiques ?Cette thèse cherche à raconter une histoire. De manière générale, elle relate l'histoire de la relation intime du droit avec le langage. Mais plus spécifiquement, la thèse détaille la rencontre récente du droit avec le numérique. Lorsque le droit a rencontré la technologie, sa relation avec le langage a changé, suscitant le scepticisme quant à son aptitude à transmettre des concepts juridiques. Avec l'introduction d'un acteur innovant - le code - le droit a visiblement trouvé sa nouvelle adéquation linguistique. En conséquence, le code a été mis à l'épreuve quant à sa capacité à fonctionner et à répondre aux exigences du droit. Finalement, confronté au langage naturel et au code, le droit se demande si le code peut être son langage.
Keywords: Connaissance du contexte; Contextual knowledge; Droit et informatique; Informatique; Langage juridique (informatique); Langages de programmation; Law and computation; Linguistics; Linguistique; Programming languages

Four Essays on Tax Transition Reform in Developing Countries - Adandohoin, Kodjo (Université Clermont Auvergne, 2021)
Ces dernières années, la plupart des pays en développement sont confrontés à la nécessité de concilier deux impératifs : d’une part, une demande sociale forte qui nécessite un besoin de ressources publiques supplémentaires, et d’autre part le désarmement tarifaire consécutif aux politiques d’ouverture commerciale, qui les prive de la majeure partie de leurs recettes budgétaires. D’où l’impérieuse nécessité pour ces pays d’assurer une transition dans la structure de leur prélèvement public c’est à dire de transférer la pression fiscale du commerce extérieur vers la fiscalité domestique. Cette thèse s’intéresse à cette problématique et vise à étudier les conditions de réussite d’un tel phénomène dans les pays en développement au travers de quatre essais empiriques. Le premier essai concerne le rôle de la TVA et des droits d’accises dans une première vague de transition. La TVA étant un impôt neutre et à très large assiette fiscale, cette dernière a été suggérée comme outil majeur pour réussir le transfert des ressources publiques du cordon douanier vers la fiscalité domestique et en complémentarité avec les droits d’accises. Nos investigations empiriques soutiennent cette assertion théorique et montrent que le couple TVA-accise joue bien ce rôle de substitut aux recettes de porte en quasi baisse suite au démantèlement tarifaire dans les pays. Néanmoins le rôle d’appui de la TVA et des droits d’accises est limité à partir d’un certain seuil de baisse des recettes de porte, qui traduit aussi le fait que le potentiel de mobilisation fiscale par la TVA dans ces pays est limité et qu’il faudra s’en préoccuper. Dans le second essai nous analysons la transition de seconde génération basée sur les impôts directs (impôts sur les revenus et impôts fonciers). Nous trouvons que les impôts directs sont des outils pauvres de transition fiscale dans les pays en développement. Pourtant, nous trouvons que le développement financier est un médiateur certain et incontestable à une politique de transition fiscale de seconde génération basée sur les impôts directs, car permettant de recouper l’information sur les revenus des contribuables et de générer des traces documentaires à l’administration fiscale, qui permettent d’envisager une mise à fiscalisation des contribuables, gage de recettes fiscales directes supplémentaires dans les pays. Dans le troisième essai, nous nous intéressons à l’effet de la mise en place d’une réforme de transition fiscale sur l’efficience dans la collecte des recettes en menant une étude de cas pour l’union économique et monétaire ouest africaine (UEMOA). Nos résultats supportent l’affirmative, en ce sens que la réforme accroit globalement une mobilisation efficiente des recettes dans la zone UEMOA. Cette efficience entrainerait par ailleurs avec elle une amélioration du climat des affaires dans la zone, suite à la mise en place de cette réforme. Enfin nous terminons cette thèse par un quatrième essai qui interroge quand à lui les impacts distributifs et de pauvreté d’une réforme de transition fiscale basée sur la TVA. Quoique les résultats montrent une incidence régressive de la réforme sur le revenu des ménages, une redistribution par la dépense aurait le mérite d’atténuer l’incidence sociale de cette stratégie de réforme sur le revenu des contribuables.
Keywords: 2SLS-IV model; Accises; Administration fiscale; Analyse des frontières stochastiques; Business climate; Climat des affaires; Computable general equilibrium; Contrôle Synthétique; Coordination fiscale; Corporate tax; Developing countries; Développement financier; Efficience; Efficiency; Effort fiscal; Excise; Exemptions; Exonérations; Financial development; Fiscalité; GMM; Harmonisation; Harmonization; Impôt foncier; Impôt sur le revenu; Impôt sur les sociétés; Income tax; Inequality; Internet; Inégalités; Micro-simulation; Modèle 2SLS-IV; Pauvreté; Pays en développement; Politique fiscale – Pays en voie de développement; Potentiel fiscal; Poverty; Probit and Logit; Probit et Logit; Propensity scores; Property tax; Réforme fiscale; Scores de Propension; Stochastic frontier analysis; Synthetic control; TVA; Tax administration; Tax coordination; Tax effort; Tax potential; Tax reform; Tax transition; Taxation; Taxes sur le commerce extérieur; Trade taxes; Transition fiscale; VAT; Équilibre général calculable

Abuse of dominance and the Internet : an assessment of the South African Regulatory Framework - Koornhof, Pieter Gerhardus Jacobus (Stellenbosch University, 2021)
While electronic commerce in South Africa is still comparatively small, it is growing rapidly. The advent of the internet has potentially fundamental impacts on business and the law both locally and internationally. It is submitted the free competition on the internet is important and will continue to be so in the future. The research in this thesis relates to the rise of so-called internet monopolies (such as Google, Facebook and Amazon) and its implications for competition law enforcement. A particularly problematic aspect of the products provided by some of these companies is that their products and services are ostensibly free to consumers. This thesis examines whether the traditional model for the regulating abuse of dominance would be effective in the instance where such an internet monopoly is charged with a contravention under South African competition law. The research and analysis in the thesis are effectively divided into three parts. The first considers whether abuse of dominance related to the internet deserves closer analysis and also assesses the purposes of competition law and how these are changing (or should change) in the light of new technology and markets. The second part deals with abuse of dominance both generally and specifically in relation to the internet. In this context, the thesis considers how harms may manifest and how dominance may be determined in the context of the internet. The final part considers specific issues that may be problematic in light of the internet. The interrelationship between intellectual property and competition law is analysed, along with aspects pertaining to the assertion of jurisdiction, the nature of competition law enforcement and the extent to which different jurisdictions may (and/or should) cooperate in dealing with abuse of dominance on the internet. The thesis submits that the South African legislative framework for regulating abuse of dominance on the internet is broadly fit for purpose, but that there is a need for developing new approaches and policy within that framework. It contributes to the existing body of knowledge and discourse by providing a comprehensive overview of the regulatory framework in South Africa, informed by comparative analysis; by applying this in a new context (hitherto under-researched in the South African context), and by offering concrete suggestions to frame policy and approach.
URI: http://hdl.handle.net/10019.1/123687
Keywords: Competencia; Competition law; E-commerce; Electronic commerce; Internet monopolies; South African competition law; South African legislative Framework

Botswana’s Anti-Money Laundering and Combating the Financing of Terrorism Regime - Tshiamo-Kgati, Kuda (University of Pretoria, 2021)
Money laundering, the financing of terrorism and proliferation financing continue to be serious threats to the stability of the international financial system. The international community therefore has prioritised the fight against these activities. For example, international bodies such as the Financial Action Task Force (FATF) and others have developed standards and recommendations against which countries and organisations are measured in this regard. Against this background, this thesis investigates to what extent Botswana’s legislative framework regarding money laundering, terrorism financing and other illicit financial flows complies with international standards, especially the FATF Recommendations. The study sets the scene by defining and describing money laundering, financing of terrorism and proliferation financing, after which the current statutory framework in Botswana is discussed in detail. After subsequently setting out the various global and regional (specifically African) initiatives in the fight against money laundering and other financial crimes, the current state of affairs in Botswana is benchmarked against both the South African framework as well as the FATF Recommendations. The investigation is limited to a technical assessment (doctrinal analysis) of Botswana law to determine the current compliance (or lack thereof) of the country’s statutory provisions and to make recommendations regarding how the framework can be improved. It is difficult for some countries, especially African countries like Botswana, to comply fully with the FATF Recommendations, since compliance can be expensive and dependent on high levels of expertise on the part of the relevant authorities. Therefore, such more vulnerable countries tend to face a higher risk of being used as conduits for money laundering and related activities. Despite these and other challenges, Botswana has gone to great lengths to re-assess and improve its anti-money laundering and combating the financing of terrorism (AML/CFT) legislation with a view to move towards full compliance with the FATF Recommendations. Nevertheless, the evaluation indicates that there are some remaining shortcomings in Botswana’s legislation. Consequently, the thesis concludes by proffering certain recommendations towards ensuring that Botswana’s AML/CFT legislation is rendered fully compliant with the FATF Recommendations.
URI: https://repository.up.ac.za/handle/2263/82675
Keywords: AML/CFT; Anti-money laundering; Botswana; Financement du terrorisme; Financial law; LBC/FT; Lutte contre blanchiment de capitaux; Money laundering

Challenges and solutions for the harmonisation of contract law within the BRICS countries. Invalidity of contracts and hardship - Veronese, Lígia Espolaor (Universidade de São Paulo, 2021)
The present thesis is concerned with a comparative study of contract law applicable in the BRICS countries Brazil, Russia, India, China and South Africa with a strong focus on the issues of invalidity of contracts and hardship. The purpose is to identify commonalities and divergences in these systems with different legal backgrounds, particularly the influence of civil law tradition in Brazil, Russia and China as opposed to common law in India, and the mixed system in South Africa. Among the identified divergences and challenges, the thesis purports to demonstrate that the obstacles are not insuperable and that there are rooms for the harmonisation and compatibility within the BRICS context with respect to the two selected topics of contract law. Even when full harmony is not reached, the research also purports to demonstrate that some countries may benefit from others divergent experiences. Detecting mutual contribution is of particular relevance to this group of countries, since they share the characteristic of being evolving systems which have undergone recent reforms in their legislation on contract law and may be more open to assess and incorporate more efficient contract practices.
Keywords: BRICS; Brazil; Common law vs. Civil law; Comparative law; Contract law; Contribuição; Contribution; Direito comparado; Direito contratual; Hardship; Harmonisation; Harmonização; Invalidade dos contratos; Invalidity of contracts; Russia; South Africa; Validade dos contratos; Validity of contracts

Firm Performance, Financial Constraints, and Dual-Class Share Structure - Ahamed, Fatematuz Tamanna (Victoria University of Wellington, 2021)
This thesis addresses two aspects of financial constraints focusing, firstly, on the impact of financial constraints on firm performance and, secondly, on the impact of dual-class share structure on financial constraints. The first issue has been addressed in a large number of research studies, but the results are mixed. This study, therefore, conducts a meta-analysis of those earlier studies to provide a summary view of the results which, in contrast to narrative reviews of the empirical literature, provides an objective overview. The second issue examines the impact of dual-class share structures on financial constraints. The period of the global financial crisis is used to test the impact of the state of the economy on that relationship. To examine the impact of financial constraints on firm performance, 26 empirical studies with 189 effect sizes representing listed firms have been analysed. The study finds that overall there is a positive relationship between financial constraints and firm performance. The study also shows that the set of market-based measures of firm performance has a significant negative impact on the relationship, compared with the set of accounting-based measures. In terms of the financial constraints measure, the set of external financial constraints measures have a positive and highly significant impact on the relationship. The meta-regression analysis suggests that the choice of measure, regional difference, journal quality and publication status all have a significant impact on the relationship, and explain the variation in the association. To examine the impact of dual-class share structures on financial constraints the study analyses a sample of non-financial US firms over the period 2002-2018. Share structure is measured by the existence of a dual-class structure and also by excess voting rights and the proximity of the superior class shareholders in such structures. The study also shows that if financial constraints are measured by the WW index, irrespective of how dual-class share structure is measured, it increases the level of financial constraints. Similar results are obtained where financial constraints are measured by the KZ and SA indexes, except where dual-class share structure is measured by the proximity of superior class shareholders. The study also finds that if financial constraints are measured by the WW index, dual-class had a reduced impact during the period of the global financial crisis, thus, providing support for the propping theory. However, if financial constraint is measured by the SA index, dual-class share structure appears to have an increased impact during the GFC years. Among the additional tests, the HM index has been used as a measure of financial constraints, and the findings show that the impact of dual-class structures on financial constraints appears to be driven by their effect on debt constraints. The study also shows that firm age moderates the impact of dual-class share structures if financial constraints are measured by the WW index. The KZ, WW, and SA indexes are based on firm characteristics and, therefore, the study also tests for an impact of dual-class structures when financial constraint is measured by a text-based index, the BLM index. However, the results do not provide evidence of an impact in that case.
Keywords: Dual-class share structure; Financial Accounting; Financial Constraints; Firm Performannce; Meta analysis

Value Relevance of Integrated Reporting using a Novel Approach: Comparative Cross Country Evidence of Mandatory and Voluntary Implementers - Mohaimen, F. J. (Victoria University of Wellington, 2021)
This thesis examines the value relevance of accounting information under integrated reporting (IR) in a comparative mandatory and voluntary setting. A meta review is conducted of all published work focusing on integrated reporting since 2011, which provides detailed insight into the gaps in the IR literature. Multiplicative log-linear model is used in measurement, which is a novel technique that mitigates the shortcomings of traditional value relevance models. The findings show that value relevance of summary accounting information increases after the implementation of IR in the mandatory setting. In the voluntary setting, market effect and the existing reporting paradigm effect the value relevance of accounting information under IR. If the market is large and existing reporting requirements are robust voluntary adoption of IR has minimal to no effect. However, in smaller markets with less rigorous reporting environment, adoption of IR does result in increased value relevance of accounting information. Compared to traditional models, the multiplicative model provides estimates that are more stable over time and shows better explanatory power. Overall, the findings of this thesis show that capital providers value the information content of IR under specific circumstances. This thesis contributes to the IR and value relevance literature by providing the first comparative cross-country evidence of the effect of IR in the change in value relevance of reported accounting information. It provides policy relevant input to the standard setters of IR by demonstrating the effect of IR in the decision usefulness of summary accounting information. The thesis further provides robust evidence of the efficacy of using the multiplicative log-linear model in measuring value relevance instead of the traditional linear additive models.

Compensation for Regulatory Expropriation in International Investment Law - Khachvani, David (Université de Genève, 2021)
The States, international organizations and interest groups are increasingly concerned with treaty claims of foreign investors, who sometimes seek compensation for the States' legitimate regulatory measures, such as tobacco plain packaging, nuclear energy phase out and environmental regulations. International investment law has yet to develop a comprehensive and predictable framework addressing some of the basis questions related to compensability of legitimate regulatory measures. The thesis carries out a comparative legal analysis to identify the key features of the prohibition of uncompensated expropriation as a general principle of law, and explores the rationale of that principle in political philosophy. Equipped with the results of this analysis, it proceeds to propose an analytical approach addressing practical questions related to the compensatory protection of foreign investments.
Keywords: Climate Change; Compensation; Expropriation; Investments; Police Powers; Regulatory Powers

A developing country's perspective on forum shopping and long arm jurisdiction in light of US and UK insolvency laws - Gatoto, Phoebe Njoki (Nottingham Trent University, 2021)
The trend for multinational companies has been a preference to forum shop rather than to open insolvency proceedings in developing countries. The US and the UK are prime venues for such bankruptcy tourism enabled by long-arm jurisdiction through extraneous connection. At the same time, there has been a pattern in developing countries of insolvency law reforms which have been circumvented when multinational companies forum shop. Using doctrinal and comparative methodologies, this thesis examines how forum shopping and long-arm jurisdiction to the US and UK affect the efforts of developing countries to reform their insolvency laws and their possible effects on local stakeholders of multinational companies in developing countries. Additionally, the thesis proposes a longer-term strategy of dealing with forum shopping and long-arm jurisdiction by using the concept of centre of main interests ('COMI') as the basis for opening main insolvency proceedings. To ensure that the proposed insolvency procedural legal law is implemented uniformly, the thesis proposes the creation of a supranational court from which national courts, insolvency practitioners and multinational companies can request clarifications on the provisions of the proposed insolvency procedural legal framework. The thesis identified that developing countries require effective insolvency laws and institutions and highlighted key principles that should be included in the reforms. The hope is that developing countries can improve their insolvency laws and institutions to a global standard. Once the proposed insolvency procedural legal framework is implemented, multinational companies will be encouraged to utilise them once jurisdiction is identified through the COMI test rather than forum shopping.
https://irep.ntu.ac.uk/id/eprint/46506/

Corporate Social Responsibility, Corporate Governance and Banking Performance in the CEMAC Region - Fondem, Divine (Liberty University, 2021)
This researcher examined the effect of corporate governance (CG) and corporate social responsibility (CSR) on banking performance in the Central African Economic and Monetary Community (CEMAC) region. The data was obtained from the Worldwide Governance and the World Bank sovereign database from 2003 to 2018. This study employs the z-score to proxy the CSR factors such as labor force participation rate, population density, and renewable energy. The results reveal that the fixed effects model is superior to the pooled ordinary least square (OLS) and the random-effects model. The findings show that CSR has a significantly positive relationship, while CG has a positive but insignificant relation with banking performance in the CEMAC region. It suggests an ineffective implementation of CG strategies in the entire CEMAC region.
Keywords: Banking Performance; CEMAC; CSR; Central Africa Economic and Monetary Community; Corporate Social Responsibility; Corporate governance; RSE

Legal Challenges in the Enforcement of Foreign Arbitral Awards in Nigeria - Kudirat, Magaji (University of Ilorin, 2021)
Businessmen have a choice in the resolution of disputes, they may elect litigation or submit to arbitration. Delays, outrageous cost and undue technicalities associated with courts, makes commercial arbitration the preferred mode of settlement in the business world. However, the recalcitrance of an award-debtor to comply with the terms of the award necessitates the intervention of the courts. Nigeria has provisions for enforcement of foreign arbitral awards within her legal system. However, reliance on courts for enforcing foreign awards frequently frustrates the gains initially made by arbitration. Enforcement of arbitral awards via the courts has numerous legal challenges. This study is therefore aimed at analysing the challenges facing enforcement of foreign awards in Nigeria. The objectives of the study were to: (i) analyse the impact of extant legal regimes on the recognition and enforcement of foreign awards in Nigeria; (ii) examine the effects of the concepts of arbitrability and public policy exceptions on the enforcement of awards in Nigeria; (iii) examine the challenges inherent in judicial review on the enforcement of foreign awards in Nigeria; and (iv) examine the adequacy of the Arbitration and Conciliation Act 1988 (ACA 1988) in the recognition and enforcement of Islamic commercial arbitral awards. The study employed doctrinal methodology of legal research where primary and secondary of legal materials were subjected to descriptive and content analysis. The primary sources used were legislations, regulations, treaties, conventions and case laws, while secondary sources used were texts books, journals, internet materials, conferences and seminars papers. The findings of the study were that: i. the provisions of the laws regulating enforcement of foreign arbitral awards in Nigeria, particularly, Sections 51 and 54 of ACA 1988 have inherent and procedural defects, thus preventing the smooth enforcement of the award; ii. the narrow interpretation by the Nigerian courts on ‘arbitrability’ based on Sections 54 and 57 of ACA 1988 which restricts disputes to contractual and commercial disputes only, prevents the enforcement of foreign awards from jurisdictions with liberal interpretation. iii. the amorphous nature of the scope of public policy creates a challenge for the courts in Nigeria in determining whether a foreign award violates the country’s public policy or not; iv. the powers of the courts to set aside foreign awards based on grounds contained in Sections 29, 30 and 48 ACA 1988 are open-ended and allow the courts to examine the merit of the disputes rather than limit themselves to the validity of the award for enforcement; v. the provisions of ACA 1988 on enforcement of foreign arbitral awards do not consider the idiosyncrasies of awards from Islamic law jurisdictions, despite growing investors’ interests in Islamic commercial transactions. The study concluded that it is obvious that the various legal challenges identified showed that the existing legal frameworks on enforcement of foreign arbitral award in Nigeria are weak and ineffective. The study therefore recommended that the Nigerian arbitral laws in particular, the provisions on enforcement of arbitral awards under ACA 1988 should be amended.
Keywords: Enforcement; Foreign Arbitral Awards; Legal Challenges; Nigeria

The legal nature of debt securities in South African law - Beer, Johan Philip de (Stellenbosch University, 2021)
The problem statement of this thesis is ascertaining the legal nature of debt securities in furtherance of a consistent and coherent legal description of the South African positive law as it relates to this class of instruments. It focuses on four core issues: the legal history, legal nature, classification, and current legal issues relating to debt securities. Historical and analytic-systemic approaches to the problem statement make up Part 1 of the study. The historical approach shows an emergent commoditisation of debt, which is an important phenomenon in the analysis of securities law. It further shows a great deal of English influence in the development of the South African legal environment, most notably in terms of company law (as the primary driver of securities law) and the financial marketplace, its institutions and its regulation. Also highlighted is a notable scarcity of debt securities relative to equities, which materially impacted legislative developments. Finally, it points to an increase in the legal importance of the “securities” concept as a legal term to describe and govern debt and equity securities. Thereafter the analytic-systemic approach is used to identify a set of private law-rooted first principles applicable to South African registered securities, and herefore to debt securities as well. It posits that these securities should be understood conceptually as comprised two interdependent but functionally separate legal objects, rather than in terms of two different kinds of ownership (i.e. beneficial and registered). The first object is the "security instrument”, a locus for (holdership of) the incidents that flow from the entitlement of determination (beskikkingsbevoegdheid) over the underlying complex of rights and competencies of registered securities. These can be understood as incidents of execution. The second is the "security asset”, a locus for (holdership of) the incidents that flow from the entitlement of enjoyment (genotsbevoegdheid) over that underlying complex, and corresponds with the proprietary, patrimonial dimension of securities. These can be understood as incidents of enjoyment. This construction enables a more coherent understanding of the sui generis relationship of agency between beneficial owner and her nominee, as well as of the dynamics of ownership and quasi-possessio. These insights are then applied to the uncertificated environment, addressing a number of difficult and uncertain problems within the system that enables uncertificated securities and their holdership. Finally the particularly difficult issue of how to classify (and therefore identify) debt securities is dealt with. Here it is concluded that a typological approach is the only viable methodology to deal with this problem, and a number of necessary and thereafter possible classificatory indicia are outlined for this purpose. The functional-policy approach makes up Part 2 of the study. It is a policy-aware application of the theoretical framework developed to a select number of themes and legal issues of the current environment. Principally it shows that the reconceptualisation of registered securities has explanatory and problem-solving value, specifically relating to transfer, the granting of limited real interests, good faith acquisition, and the protection of holdership of certificated and uncertificated securities.
URI: http://hdl.handle.net/10019.1/110018
Keywords: Beneficial ownership; Debt and equity Securities; Securities; Securities industry; South Africa; Titre de créance

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

The influence of capital structure and profitability on the solvency of nascent SMEs - Amoa-Gyarteng, Karikari (University of Johannesburg, 2021)
Even though small and medium enterprises contribute significantly to the growth of national economies, they are vulnerable in their early stages and may fail. Hence younger businesses are more likely to fail than more established ones because they face complex challenges that may limit their viability. This is a notion established in the liability of newness framework. According to the liability of newness concept, the precarious existence of emerging organisations is due to difficulties in managing relationships among strangers, not quickly assembling resources, and not coping with difficult environments, among other issues. All these elements notwithstanding, previous literature suggests that small businesses can, and sometimes do engage in techniques or approaches to help reduce the liability of newness, such as raising adequate capital. This study suggests that not only is adequate capital important but that the right mix of capital also results in higher solvency, thereby mitigating the liability of newness. Because the various funding forms have distinct advantages and disadvantages, an appropriate capital structure reduces the cost of financing while increasing the value of the firm. This study also advances the idea that profitable businesses are productive and financially strong, and thus nascent enterprises with high profitability can minimise the liability of newness. As a result, the study sought to examine the influence of capital structure and profitability on the solvency of nascent small and medium enterprises. To put the study's hypotheses to the test, 1106 nascent small and medium enterprises that are registered with the National Board for Small Scale Industries were sampled across three major cities in Ghana. Thus, data was gathered from every member of the population. Such data, gathered from the SMEs' financial statements, was submitted to preliminary screening as well as a number of statistical measurements. Operationally, the dependent variable, solvency, was defined as the solvency ratio, working capital ratio, and net worth. As a result, three distinct regression models were developed for robustness. The study's findings broadly indicate that capital structure and profitability have an influence on the solvency of nascent small and medium enterprises. The study also determined that emerging small and medium enterprises should follow the principles of the pecking order theory to reduce the liability of newness. These findings, if adopted by SME owners, can aid in the maturation of their fledgling businesses.
Keywords: Entrepreneurship; New business enterprises

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa - Baines, Daniel (University of Pretoria, 2021)
A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa', Daniel Baines explores whether South African resident taxpayers' constitutional rights to equality and property are infringed by current laws which tax residents at higher rates than non-residents on rental income and proceeds from the disposal of fixed property. He aptly sets out what the right to equality and property entails and how these relate to taxpayers. He finds that the higher effective tax rates paid by residents violates their constitutional right to equality. The thesis provides valuable insight into a resident's right to equality and property in terms of current tax rates and illustrates how current tax rates are unconstitutional. The recommendations brought forward contribute toward the discussion of how tax rates should be altered in order to ensure that residents' constitutional rights are no longer violated.
URI: https://repository.up.ac.za/handle/2263/82750
Keywords: Immovable property; Income tax; South Africa; Tax treatment

The arbitration of internal trust disputes in English law: Legal challenges and pathways - Clover Alcolea, Lucas (McGill University, 2021)
The arbitration of internal trust disputes has attracted significant attention in the arbitration and trust law communities in recent years with draft clauses and rules produced by arbitral institutions, several states undertaking legislative reform in order to provide such arbitrations with a statutory basis and numerous scholars as well as practitioners writing articles on the subject. Such enthusiasm is justified on the basis that arbitration has several advantages over litigation, such as confidentiality, international enforceability of judgments, the ability to choose one’s judge and the power to tailor the procedure. Notwithstanding these advantages, trust arbitration has failed to make any great inroad into trust disputes due to the many novel and complex points of legal practice and theory which it entails. For example, although arbitration does not typically involve minors or legally incapable parties’ trusts do, and thus trust arbitration raises numerous due process and human rights concerns. Similarly, court supervision and enforcement of trusts is sometimes considered essential to the very nature of trusts and questions therefore arise concerning the extent to which arbitral tribunals could supplant courts in that regard. Another complication is that trusts are not contracts and questions therefore arise about how to bind individuals to a trust arbitration agreement, particularly as regards beneficiaries who may be unascertained, minor or legally incompetent at the time the trust was created. The aim of this thesis is to analyse and present potential solutions to these complications from an English law perspective, although other common law legal systems will be analysed where relevant
Identifier: https://escholarship.mcgill.ca/concern/theses/x346d9718
Keywords: Arbitrage; Arbitragem; Arbitration; Internal trust disputes

Optimising regulatory responses to consumer disempowerment over personal data in the digital world - D'Amico, Alessia (European University Institute, 2021)
This thesis addresses the problem of individuals’ lack of control over personal data in the digital world. It sheds light on market and regulatory failures that lie behind the status quo and proposes a framework to improve regulatory responses. The two regulatory regimes that are at the core of this thesis are EU data protection regulation, which protects individuals’ fundamental rights over data, and EU competition law, which safeguards the sound functioning of the market and consumers’ economic interests. Despite the existence of these two regulatory regimes, individuals do not have sufficient control over personal data collected by digital firms, whose control over large datasets is a factor contributing to market monopolisation. The thesis argues that one reason for the shortcomings of today’s regulatory framework is that the market failure is composed of a combination of factors, which are currently addressed by the different regimes relatively independently. This dichotomy hinders the development of an effective strategy to tackle the market failure in its entirety. The approach taken in this thesis is that by integrating the two regimes, it might be possible to close the gaps deriving from a narrow perception of their regulatory spaces. Hence, the thesis formulates a holistic approach, encompassing data protection regulation and competition law, designed to increase the effectiveness of the regulatory framework as a whole. Different dimensions of the regimes’ interrelation are analysed, to uncover new ways to harness their complementarity and minimise their inconsistencies and overlaps. The thesis looks at how the regimes can incorporate elements from each other to inform their policies and application of their rules, as well as developing a complementary enforcement strategy. The holistic framework ultimately allows both regimes to better tailor their regulatory responses to the functioning of the digital market and take account of the diverse elements that constitute the market failure they seek to correct.
Accepted: 2021-07-07T10:12:30Z
Keywords: Data Protection; Personal data; Privacy

The conflict of jurisdiction between intra-EU BITs and European law: proposal for an EU investment court - Lewis, Krystle (Canterbury Christ Church University, 2021)
This work aims to find a practical solution to the problem that exists between intra-EU Bilateral Investment Treaties (BITs) and European Union (EU) law over conflict of jurisdiction issues. Currently, there is a problem as the EU Commission has rendered intra-EU BITs incompatible with EU law. This work argues that the current conflict of jurisdictional problems within investment agreements can be overcome by the creation of an EU investment court. The reliance on this court for the resolution of this conflict, as opposed to private law mechanisms, is important as it is the way forward in handling the conflict of jurisdiction issue at its best. This work argues that an EU investment court will be a panacea to the current problems concerning the conflict of jurisdiction. These problems will be presented through a positivist method where the law is analysed in its current form, highlighting its current weaknesses and resolving these weaknesses by proposing recommendations for such a court through a comparative examination of other international courts that fulfil a similar dispute resolution function, namely the Organisation for the Harmonisation of Business Law in Africa (OHADA) and the Unified Patent Court (UPC) and the World Trade Organisation (WTO). The purpose of this work is manifold. The work will provide an analytical examination of the relationship between EU law and international obligations within intra-EU BITs. It will further explore and assess the viability of a range of alternative solutions to intra EU BITs enforcement within the EU. It will additionally examine the operation of the OHADA, the UPC and the WTO to inform the proposal of an EU investment court. This is important as the outcome of these examinations will support the argument made in this thesis. It will also impact dispute resolution beyond academia by providing a practical solution to alleviate the current challenges with intra-EU BITs. The recommendations thus can inform changes for lex ferenda.
Permalink: https://repository.canterbury.ac.uk/item/94574/the-conflict-of-jurisdiction-between-intra-eu-bits-and-european-law-proposal-for-an-eu-investment-cour
Keywords: Bilateral Investment Treaties (BITs); Investissements; Investments

Optimising the legal regulation of circular labour migration between South Africa, Lesotho and Zimbabwe - Matete, P. (North-West University, 2021)
Circular labour migration is steadily gaining prominence the world over, primarily due to the benefits it offers to the migrants, to the sending country, and to the receiving country – the so-called "triple-win" benefits. In order to enhance the benefits of circular labour migration, both the International Labour Organisation and the International Organisation for Migration recommend that adequate instruments of governance should be utilised. From the outset, this thesis recognises bilateral labour arrangements as the ideal instruments for enhancing the potential benefits that circular labour migration offers to the stakeholders involved in the process. As far as could be established, there has been no comprehensive research that seeks to provide insights on how the selected countries in the Southern Africa Development Community (South Africa, Lesotho and Zimbabwe) could optimise the benefits of circular labour migration for all stakeholders, primarily through the use of bilateral labour arrangements. The need for these insights in Southern Africa is pertinent due to the absence of a contemporary and clear framework regulating circular labour migration in the region. Based on the foregoing, this thesis advances the proposition that the guidelines provided by international law and standards of labour migration, and the best practices in Spain and New Zealand, can provide significant insights on how South Africa, Lesotho and Zimbabwe can enhance the regulation of circular labour migration to provide optimised benefits for all stakeholders. Proceeding from the above premise, this thesis makes a number of findings. These include the affirmation that bilateral labour arrangements are indeed the key regulatory instruments for promoting the triple-win benefits that circular labour migration offers; that circular labour migration, if managed well, plays an instrumental role in development in both the sending countries and the receiving countries; and that three key areas should be addressed in bilateral labour arrangements in order to effectively promote triple-win benefits. The three key areas that need to be addressed in bilateral labour arrangements in order to enhance the benefits for all stakeholders are linking migration with development, migration governance, and the protection of the rights of migrant workers. This thesis outlines the various principles that are necessary to give effect to these three key areas. This thesis finds that, based on the guidelines provided by international law and standards, it is essential that bilateral labour arrangements, at the minimum, incorporate provisions that facilitate skills training, the return and reintegration of migrants, the transfer of remittances, and the promotion of human resources development. In this regard, this study finds that the bilateral labour arrangements between South Africa and its neighbours, Lesotho and Zimbabwe, fall short of the guidelines provided by international law and standards on labour migration and by the best practices in New Zealand and Spain. The original contribution of this study lies in it being the first study to comprehensively explore the legal measures that South Africa, Lesotho and Zimbabwe could utilise to optimise the regulation of circular labour migration to South Africa as the main receiving country in SADC. This study makes recommendations on how the labour migration legal framework between the three countries can be improved, based on lessons learned from international law and standards on labour migration and best practices from selected countries.
Keywords: Bilateral arrangements; Circular labour migration; Droit du travail; Labour law; Migrant workers; Remittances; Travailleur migrant

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

Governance of non-bank systematically important financial institutions - Morbee, Katrien (University of Oxford, 2021)
This thesis identifies the circumstances under which corporate governance regulation can help gain traction to minimise systemic risk. Systemic risk is the risk that local losses spread through the financial system and badly affect the financial system and the real economy. Excessive risk-taking by financial institutions can contribute to such systemic risk. Prudential regulation and supervision of financial institutions leave corporate decision-makers with room for discretion to increase or decrease systemic risk. The incentives of these decision-makers are not necessarily aligned with minimising systemic risk. The thesis shows that this problem exists across different business models. More specifically, it identifies perverse incentives in the case of systemically important banks, CCPs, mutual funds, and hedge funds. The need for corporate governance regulation therefore lies in the inherent incompleteness of prudential regulation and supervision. Corporate governance regulation can help fill this gap by regulating the environment within which choices are made within these types of institutions. The analysis has three steps. First, it characterises the systemic importance of financial-sector activities carried on outside the context of ‘banks’. The governance literature so far has focused on the ‘systemic externalities’ created by banks. However, our analysis shows that other non-bank SIFIs generate similar systemic externalities with socially harmful consequences. These systemic externalities are not considered by SIFIs when taking business decisions. In a second step, the thesis shows that prudential regulation and supervision are incomplete and leave room for governance regulation to fill in the gaps. The final step shows that a corporate governance framework focused solely on the interests of shareholders will have negative consequences for systemic stability. Given such divergence between the decision-makers’ and society’s interests, corporate governance regulation can complement the traditional prudential framework.
Keywords: Asset managers; Central counterparties; Corporate governance; Finance; Non-bank financial institutions; Systemic risk

Regulatory measures to address bank failures in Zimbabwe - Nyaude, Ashley Batsirai (University of Pretoria, 2021)
The main rationale of prudential bank regulation and supervision of banks has traditionally been to ensure the safety and soundness of banks and protection of depositors. However, best practice standards in bank supervision acknowledge that it is impossible to completely prevent bank failures. Therefore, it is crucial to have regulatory measures in place to deal with banks that fail. Banks are core players in the financial system as the intermediaries between savers and users of capital. In addition, banks provide critical services to consumers, small and medium-sized businesses, large corporate entities and governments who rely on them to conduct their daily business, both at domestic and international level. Banks also fulfil a sui generis role that sets them apart from other financial institutions that are role players in the financial system because, inter alia, they hold “highly” liquid liabilities in the form of deposits that are repayable on demand; they extend long-term loans that may be difficult to sell or borrow against on short notice; they are the back-up source of liquidity to all other institutions (financial and non-financial); and, are also the transmission belt for monetary policy. Unlike other players in the financial system, banks are vulnerable to loss of public confidence and to liquidity risk. Liquidity risk being the risk that a bank will not have sufficient cash to meet short term obligations and the fact that a "run on the bank" by depositors can result in devastating liquidity drainage. Because banks play a special role in the economy and their failure may have a significant impact on financial stability, they need a special approach when they become insolvent or are likely to become insolvent. The 2008 Global Financial Crisis (“GFC”) demonstrated the importance of special resolution regimes for banks; and the need to balance the interests of shareholders, creditors and depositors, while promoting financial stability objectives. Given the critical role of banks in the economy the need is clear for a special resolution regime for banks that provides a legal framework for regulators that avails to them a suite of resolution tools which they can apply to resolve the bank in an orderly manner; to rescue those parts of the bank that may still be viable and to liquidate those parts that are not whilst avoiding a drain on public funds. In order to deal with bank failures in Zimbabwe, the Banking Act [Chapter 24:20] has provided for the mechanism of curatorship since 2000, as a rescue measure aimed at restoring failing banks to economic viability. Curatorship has over the years been applied with mixed success; consequently, Zimbabwe has undertaken a number of reforms which include the enactment of the Troubled Financial Institutions (Resolution) Act in 2005; and the introduction of the problem bank regime via the Banking Amendment Act of 2015. Throughout these reforms, Zimbabwe has elected to retain curatorship, which was once a standalone process in banking legislation to enable bank rescue; and assimilated it into a broader bank resolution framework. This study seeks to determine whether Zimbabwe’s resolution regime requires to be strengthened and if so, to recommend reforms that will align the resolution regime in Zimbabwe with international best practice. For such purpose it will draw upon the Financial Stability Board’s Key Attributes of Effective Resolution Regime as international best practice benchmark. It will further also consider guidance yielded by a comparative study of the resolution regimes in the United Kingdom and South Africa.
URI: https://repository.up.ac.za/handle/2263/80388
Keywords: Bank failure; Bank supervision; Zimbabwe

Allocating rights between nations: Legitimacy and justice in international tax policy - Ozawa Ozai, Ivan (McGill University, 2021)
Although extreme poverty has decreased in the last decades, we are a long way from eradicating global poverty. Similarly, the world has seen a considerable decrease in global inequality due to recent developments in emerging economies, but overall inequality between nations has risen in the last decades. International tax law may have a relevant role in improving or worsening global inequality. Extensive research has shown that the present international tax system was designed in a way that tends to benefit high-income economies. However, there has been no significant discussion about whether and how international tax law rules should be changed to address global inequality. The main goal of this thesis is to analyze the existing legitimacy and distributive justice issues that limit the ability of lower-income countries to raise tax revenues and consider what can be done to make the current international tax regime more aligned with global justice principles.The thesis builds on the contemporary literature in international political economy and global distributive justice and puts forth a normative framework for allocating the international tax base among states. First, it analyzes some of the legitimacy deficits of the present international tax system. In contrast to prevailing views about improving legitimacy, it demonstrates the shortcomings of focusing solely on making international tax policymaking processes more inclusive and argues for a greater focus on global distributive justice. It then analyzes the main tax theories that have defined international tax relations to date and demonstrates some of their limitations. The final part of the thesis puts forth normative principles that integrate distributive justice and considers the practical implications of the proposed normative framework for some of the most recent issues discussed in international tax policy
Identifier: https://escholarship.mcgill.ca/concern/theses/rf55zd52x
Keywords: International tax; International tax policy

Improving international investment law’s treatment of (anti-)corruption: Towards a more balanced approach - Yan, Yueming (McGill University, 2021)
In recent years, investment arbitration tribunals are increasingly confronted with allegations of corruption, mostly invoked by host States as a defense to investors’ claims. After an affirmative finding of an alleged corrupt act between the investor and a public official of the host State in the establishment or conduct of the investment, tribunals have adopted a binary approach to the issue – if they uphold allegations of corruption, they completely dismiss the investor’s submissions. This binary approach has resulted in an asymmetry of liability for the two parties to a corrupt act (i.e., investors and host States/host State officials), failing to take into account the inherent bilateralism of corruption and the fact that domestic laws and international norms have outlawed both the act of offering and of accepting bribes. In particular, public officials’ free participation in a corrupt act to advance investments is attributable to the host State and requires State responsibility under international law. Moreover, the increasingly prevalent practice of inserting anti-corruption provisions in investment treaties has reinforced this lop-sided feature, as well as offering only weak effectiveness in terms of deterring corruption. After a careful examination of the treatment of corruption issues in investment arbitration and investment treaties, this thesis proposes a paradigm shift from the current asymmetric approach to a more balanced approach. It calls on investment tribunals to take a dual-track approach that investigates both corruption and investors’ claims, and ensures that each party assumes responsibility for its own misconduct. It also proposes that treaty drafters include anti-corruption provisions that impose strong obligations of anti-corruption on both sides of corruption (i.e., investors and host States) rather than merely on a single party to it
https://escholarship.mcgill.ca/concern/theses/5q47rt984
Keywords: Anti-Corruption Law; Investment arbitration; Investment treaty; Investments

Legalization through adjudication: The case of investor-state dispute settlement - Yu, Chen (McGill University, 2021)
The reform of the Investor-State Dispute Settlement (ISDS) mechanism has provoked much debate among legal scholars and practitioners. The critiques of ISDS mainly arise from concerns regarding the legitimacy of the mechanism such as the perceived tolerance for the lack of impartiality and consistency. To allay these concerns, there have been proposals to reform ISDS by establishing investment courts with tenured judges and appellate tribunals. However, international adjudication systems like ISDS cannot be fully analogized to domestic courts in common law countries: ISDS falls into a broader international regime where there are neither hierarchical/centralized decision-making and enforcement authorities nor a multilateral investment treaty, and the rules and principles on foreign investment protection are fragmented in around three thousand Bilateral Investment Treaties (BITs). Against this backdrop, this thesis argues that, although there is a general agreement among the international community to further legalize international investment law, the process of legalization via the specific avenue of reforming the adjudication mechanism (i.e. ISDS) is subject to (1) the institutional constraint of international investment law, especially the lack of shared understanding among the international community regarding the treatment of foreign investments, and (2) the internal constraints of adjudication as a mode of social ordering. It further cautions that pursuing predictability while disregarding the low level of shared understandings regarding investment protection may cause more legitimacy problems than it solves
https://escholarship.mcgill.ca/concern/theses/2j62s986g
Keywords: Bilateral Investment Treaties (BITs); ISDS Reform; International Investment Law; Investments; Investor-State Dispute Settlement

The Development of Accounting in Africa in the Era of International Financial Reporting Standards - Agyeman, Charles Gyamf (University of Westminster, 2020)
This thesis consists of two separate, but related studies on the development of accounting in Africa in the era of International Financial Reporting Standards. The first part of this thesis presents the first empirical test of a hypothetical classification of financial reporting in Africa based on de facto or actual practices as opposed to de jure rules. Three multivariate techniques (principal component analysis, cluster analysis, and multidimensional scaling) were used to analyse the accounting policies of large, listed companies in Africa that are required by law to adopt IFRS. It was found that there is a dichotomy between the IFRS policy choices of companies in Francophone and Lusophone countries, on the one hand, and those in common law jurisdictions, on the other, thus confirming the two-group classification schemes proposed by Elad (2015) and Nobes (1983). The results of this study extend previous research by demonstrating that international differences in financial reporting in Africa have survived in the era of IFRS and that pre-IFRS regulations enshrined in national and regional charts of account appear to have influenced IFRS policy choice. Furthermore, companies in common law countries tend to provide more extensive disclosures in their IFRS financial statements than their counterparts in code law countries. These findings have important policy implications, particularly in the context of recent recommendations of the World Bank, the International Monetary Fund, and the Pan-African Federation of Accountants that large entities in Africa adopt IFRS. The systematic differences in the choice of IFRS options between companies in civil law and common law jurisdictions suggest that it would be difficult to achieve internationalcomparability and consistency in financial reporting. The second part of the study uses semi structured telephone interviews to undertake interpretive accounting research (Baker and Bettner, 1997, p.293) to assess the perception of accounting professionals in relation to IFRS adoption and its use in Ghana. It concludes that despite the problems associated with its adoption and implementation, overall, International Financial Reporting Standards are viewed as necessary for the financial reporting needs of the country.
Keywords: Accounting classifications; CFA franc zone; IFRS practices; OHADA accounting system; Plan Comptable Général; SYSCOHADA

Consumer protection in an electronic environment - Akhigbe, Iyen Joy (University of South Africa, 2020)
Consumer protection laws have not evolved on par with the development of electronic media. As a result, consumer protection laws do not address all major areas of legal concern that affect the electronic commerce (e-commerce) consumer. Furthermore, differing laws in the area of consumer protection make harmonised consumer protection neigh on impossible. Currently, there is a plethora of laws on the protection of consumers but most of these laws are within the sphere of conventional consumer protection legislation which does not adequately address the legal challenges posed by the proliferation of electronic transactions (e-transactions). Specific e-transaction laws are now to be found in certain international and regional documents emanating from organisations including: the United Nations (UN); the Council of Europe; the Organisation for Economic Cooperation and Development (OECD); the African Union (AU); the Economic Community of West African States (ECOWAS); the Southern African Development Community (SADC); the Common Market for Eastern and Southern Africa (COMESA); and the East African Community (ECA). These legal instruments have already been implemented in certain states’ national legislation, while other countries have yet to accede to them. Despite these legal instruments, e-commerce consumers are faced with inadequate or obsolete legislative provisions and are yet to enjoy full protection equivalent to that accorded to the “traditional” consumer. Furthermore, given the trans-national nature of the internet, divergent laws will inevitably prove to provide inadequate protection to e-commerce consumers. In this research, international and regional legislative instruments, as well as the national laws of selected countries such as the United States (US), the United Kingdom (UK), the Republic of South Africa (South Africa), the Federal Republic of Nigeria (Nigeria), and the Commonwealth of Australia (Australia) are examined. The strengths and gaps in each of these instruments and laws are identified with the aim of harmonising the principles they espouse in a single, cogent, and comprehensive body of rules which could take the form of an international convention. An international convention should be based on national and international best practices. The national adoption of the minimum standards espoused in the proposed Convention will ultimately, promote harmonisation.
Keywords: Borderless jurisdiction; Cooling-off; Cyberspace; E-agent; E-commerce consumer rights; Electronic transferable record; Hidden charges; Information; Keystroke error; M-commerce; Shrinkwrap; Single window facility; Terms and conditions; Transaction; Web-wrap; Wireless Application Protocol

Historical and comparative perspectives on trade union regulation with specific emphasis on the accountability of trade unions to their members - Greenhalgh, Bradley Paul (Stellenbosch University, 2020)
How do members hold their own trade unions accountable in South Africa? What legal mechanisms, if any, are available to assist union members in receiving adequate representation and service from their unions? This study approaches these questions through a comparative and historical examination of the regulation of the union member relationship in the UK, USA and the RSA. The study commences with an examination of what unions do, how they function and what benefits potentially accrue to their members, while the role played by unions in utilising collectivisation to offset the bargaining power of employers is demonstrated. The need for organised labour, by society in general, but South Africa specifically, is brought into sharp relief. This is, however, offset by the examination of 25 constitutions of broadly representative South African trade unions, where the lack of proper regulation of the union-member relationship is brought to the fore. This already means the common law and current judicial approach that is so reliant on the interpretation and implementation of trade union constitutions to address union-member disputes is unsuitable, certainly in those instances where the constitution is either silent or ambiguous, or where the nature of the relationship between the union and its member(s) mimics that of the constantly present imbalance of power and influence between employers and employees. The comparative examination of union accountability is undertaken against the backdrop of the common historical phases of proscription, acknowledgement/assimilation, and readjustment of and towards trade unions. The historical and contemporary regulation of the union-member relationship in South Africa is examined in the same way. The study demonstrates that purely statutory regulation of the union member relationship by means of punitive provisions and inter-union self-regulation measures are not feasible. A series of possible legal mechanisms – that draw from the comparative examination – are suggested, even though they are to be utilised in a collective (rather than individual) way. Even these suggestions, however, are subject to the challenges of cost-effectiveness, accessibility and efficiency of enforcement by (the) average union member(s). Three proposals are made to foster improved union member accountability: Firstly, the use of section 103A of the LRA by the Registrar so as to place unions that meet the appropriate criteria under administration, in order to restore accountable functioning and elevate the interests of the member(s) over that of the officials of the union; secondly, the introduction of a duty of fair representation – to be administered by the CCMA – to hold both union and employer accountable to members, and; thirdly, in conjunction with the first two proposals, the use of a package of further measures (and an associated information campaign), such as bolstering the financial/institutional capacity of the Registrar’s office, compelling the inclusion of accountability clauses within union constitutions, and minor amendments to the LRA with regard to balloting, reporting/transparency (and the enforcement thereof). If implemented, the expected outcomes are improved labour relations, increased accountability and professionalisation of trade union administration, a realignment of the employer-union divide and elevating the awareness of union member rights and concomitant obligations on trade unions – all of which are of critical importance in South Africa’s post-Marikana society.
URI: http://hdl.handle.net/10019.1/109343
Keywords: Labor union members; South Africa; Trade union accountability; Union security

Decompilation and copyright in ideas - the protection of non-literal elements of computer software and the idea/expression dichotomy - Jooste, Jacobus Petrus (Stellenbosch University, 2020)
The maxim, that copyright law does not protect ideas, is frequently challenged when the established principles are tested against new forms of expression or exploitation of a work. The evolution of computer programs, its unique characteristics and the increasing value of software as a commodity have resulted in a strained relationship between copyright law and the public interest regarding access to the underlying ideas in a computer program. This work examines the misalliance between copyright principles and the technical nature of computer programming, with a specific focus on the act of decompiling an existing program where it is undertaken in order to understand the underlying ideas and techniques. The impetus for this analysis is the sui generis classification of computer programs in South African copyright law and the potential this offers for development of domestic law in pursuit of national policy goals. This work conducts a normative analysis of the law and the technical reality of decompilation, from the perspective that copyright law must maintain a clear separation between the idea and the expression. The review of national and foreign copyright law is, throughout, conducted with a perspective on the effect of protection and a critical examination of the degree to which the law maintains an adequate balance between the private and public interests in the protection of software. In this respect, the current legal position is evaluated and a different, normative and prodevelopmental perspective regarding decompilation is proposed. It is submitted that are balancing of interests is justified and essential in order to establish an appropriate level of fairness and, at the same time, stimulate progress in this industry. It is argued that the act of using computer code to discover its meaning should not amount to infringement in the form of reproduction or adaptation of the work. It is found that the perception of decompilation, as a form of infringement, relies on an analogy to literary work. This view, it is argued, is ill suited to the nature of computer programs, at odds with the sui generis classification in SA copyright law, causes overbroad protection and violates the idea/expression separation. In light of the technical review of decompilation, it is found that the legal basis for prohibiting decompilation as a form of infringement is narrower than commonly assumed and that copyright law principles should be reinterpreted purposefully to permit decompilation. This work advocates that decompilation must be permissible and that an exemption, in SA copyright law, which is limited to decompilation for interoperability alone, is not appropriate in light of the national developmental agenda. Therefore, an alternative exemption is proposed which accommodates the technical reality of decompilation, the public interest in access to ideas and the commercial interests of copyright owners. This approach is supported by an analysis of international copyright law and is based on the inherent flexibilities of the three-step test. The justification for the findings of this work and the proposed departure from foreign precedent is supported by a close examination of the effect of a limited decompilation exception in foreign law and the impact of legislative measures to restrict circumvention of technological protection measures.
URI: http://hdl.handle.net/10019.1/109088
Keywords: Copyright; Copyright infringement; Decompilation; Intellectual property; International Copyright

Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

A review of the Libyan insolvency and restructuring laws informed by insolvency law theory and international benchmarks - Hosen, Emad-edden Rajab A. (Nottingham Trent University, 2020)
The research aims to evaluate the adequacy of the insolvency system in Libya to support the national desires and objectives identified in the country to enhance the national economy and to maintain social stability. The thesis considers the need for reform in the current business insolvency and rescue framework taking into account the country’s domestic circumstances. To conduct this evaluation, the research reviews the Libyan insolvency law by examining the theoretical approaches to corporate insolvency laws in order to understand the role that should be played, or the goal that should be reached, by the insolvency law. This is important to identify whether the insolvency and rescue laws should be concerned only about maximising economic interests or should be concerned also about wider societal interests and objectives. The study also undertakes an in depth evaluation of the current business insolvency and rescue framework by using the international benchmarks with particular reference to the UNCITRAL Legislative Guide on Insolvency Law. The thesis establishes that the current insolvency law is insufficient to promote the economic and social goals of the country because of both the deficiency of the legislative framework and inefficient institutions. The investigation reveals also that an application of the social justice theory as traditionally perceived by the Civil Code 1953 (as manifested in property law and contract law) that is primarily designed to achieve social goals (for example, the priority given to the wide-ranging category of privileged creditors over secured creditors) prevents the insolvency law from achieving the sought-after objectives leaving much to be desired for a reform. The research builds on these foundations to identify challenges and impediments to the development of the insolvency and rescue regime of Libya.
https://irep.ntu.ac.uk/id/eprint/41433/
Keywords: Company law; Corporate law; Insolvabilité; Insolvency; Libya; Procédures collectives; Restructuration; Restructuring law

The Impact of Employee Board Representation on the Firm’s CSR Engagement : evidence from the French Context - Boukadhaba, Amal (Le Mans Université, 2020)
Cette thèse propose d’examiner la relation entre la représentation des salariés dans le conseil d’administration et l’engagement RSE de l’entreprise. En particulier, nous étudions comment les investisseurs perçoivent-ils le reporting RSE et laperformance ESG lorsque les salariés sont représentés au sein du conseil d’administration. En utilisant un échantillon de sociétés françaises appartenant à l’indice SBF 120 sur deux périodesdifférentes de 2001 à 2011 et de 2007 à 2017, nos résultats montrent que la présence des administrateurs salariés modère positivement la perception du reporting RSE et négativement la perception de la performance ESG par les investisseurs. Un examin plus détaillé montre que les administrateurs élus par les salariés par leur droit de travail améliorent exclusivement la performance sociale et modèrent négativement la perception des investisseurs vis-à-vis de la performance ESG. Au contraire, les administrateurs élus par les salariés actionnaires renforcent la performance ESG globale ainsi que les performances environnementale et de gouvernance et modèrent positivement la perception de la performance ESG par les investisseurs. Nos résultats mettent en évidence un conflit d’intérêts entre les actionnaires et les administrateurs salariés, notamment avec les représentants des travailleurs. Cette thèse couvre plusieurs disciplines à savoir la comptabilité, la gouvernance d’entreprise et lagestion des ressources humaines. En conséquence, elle intérèsse vivement les législateurs, les investisseurs, les managers et les actionnaires.
Impact de la représentation des salariés au sein du conseil d’administration sur l’engagement RSE de l’entreprise : Etude du contexte français
Keywords: Actionnariat du personnel; Administrateurs salariés; CSR reporting; ESG performance; Employee board representation; Firm market value; Gouvernement d'entreprise; Performance ESG; Performance boursière; Personnel – Participation à la gestion; Relations avec les actionnaires; Reporting RSE; Responsabilité environnementale; Responsabilité sociétale; Sociétés

State aid to state owned enterprises in South Africa : the need for a comprehensive State aid policy : a competition law inquiry - Afrika, Sasha-Lee Stephanie (Stellenbosch University, 2020)
The Competition Act 89 of 1998 applies equally to all firms with regard to anti-competitive behaviour regardless whether it is privately or publicly owned. Therefore it applies to stateowned enterprises (SOEs) if their actions fall short of the Act. There is however one aspect relating to SOEs which is not covered by the application of the Competition Act but may have a significant impact on free and fair competition and can be of big concern for private competitors of SOEs. Since discriminatory policies during Apartheid have created a huge inequality gap in post-Apartheid South Africa, the government has to be actively involved in the economy to address the inequality. Therefore the government uses SOEs as vehicles to achieve its developmental goals. As a result SOEs in South Africa which are active market participants may always rely on the financial support of the state. They may do so purely because of their crucial governmental mandates regardless of financial mismanagement, poor corporate governance and deep seated corruption in almost every SOE. Even though the fundamental need for the existence of SOEs in South Africa is acknowledge, it is argued that state financial aid could qualify as a state-initiated constraint on competition in South Africa as it creates an uneven playing field between SOEs and their private competitors, which is always skewed in favour of the SOEs. It may create warped incentives and SOEs may not compete efficiently if they know that they are protected by a state sponsored safety net. This dissertation asks the question whether the time has not arrived in South Africa for state aid to SOEs to be subjected to a certain degree of scrutiny in order to bring about a level playing field between SOEs and their private competitors. It is recognised that privatisation of SOEs is not always the better option as it could threaten the delivery of basic services and goods to poorer South Africans. Hence, the dissertation investigates whether a state aid control model, based on the European Union state aid rules, is not perhaps a solution to address the potential distortion of free and fair competition by state financial aid. It proposes a customised state aid control regime for South Africa which provides for an active role by the competition authorities in state aid decisions and it presents draft legislation which could be used as a basis for the implementation in South Africa of a regulated system of state financial aid to SOEs (and even private enterprises where applicable).
URI: http://hdl.handle.net/10019.1/108193
Keywords: Government business enterprises; South Africa; State aid; State-owned enterprises; Unfair competition

The Effect of EU State Aid Law on the Future of EU Investment Policy - Finckenberg-Broman, Pamela (Griffith University, 2020)
On 1 July 2017, the Commission of the European Union (Commission) announced that investor state dispute settlement (ISDS) was dead. Apart from the fundamental public distrust of ISDS, its rejection by the European Union (EU) is a symptom of several underlying causes, the foremost of which is the need to protect the autonomy of the EU legal order and its right to regulate public policy objectives, as well as to avoid jurisdictional conflicts. With this backdrop EU state aid law, which enjoys public policy status, has emerged as a major example of the conflict between investor protection and the right to regulate. As state aid law imposes measures on the EU Member States that conflict with these states’ international obligations to foreign investors under bilateral investment treaties (BITs), they have become subject to claims and substantial liabilities. This dilemma can arise in any setting that involves the EU or one or more of its Member States. It also includes relations with non-EU countries, as the web of international investment agreements (IIAs) operates, in different forms, on an international scale. Therefore, this dilemma and the EU’s responses to it is analysed through the different forms in which EU state aid law appears, dependent on the EU investment policy aspect utilised as a platform for analysis. Utilising a doctrinal analysis by studying, discussing and analysing the impact of EU state aid law on the EU Member States’ BITs and EU Trade Agreements, this dissertation provides an insight into the function and logic behind international treaties involving the EU’s competition and investment policy. This is done by utilising the research question: How does the European Union (EU) state aid law affect the future of EU investment policy in a global context? Further, this thesis puts forward three arguments in which EU state aid law is affecting the future of EU investment policy in a global context. First, state aid law applies in the EU’s incorporation of clauses promoting fair competition and state aid policy in international trade agreements. Second, state aid law and policy has contributed to recent EU internal development, which led the EU Member States to terminate their bilateral agreements with each other (intra-EU BITs) by the end of 2019. Third, the EU has been working towards replacing the existing BITs between the EU’s Member States and third countries (extra-EU BITs) with the EU’s own trade agreements, which are aligned with EU legislation. Essentially, this thesis golden thread is a debate on who gets to decide on the scope of state aid law now and in the future. In other words, is it the EU that sets the borders and the status of state aid law and policy law regarding investment protection or the international investment tribunals by their legal practice? Hence, this thesis offers a glimpse of a conceivable future of EU investment policy in a global context. An analysis of the relevant literature, and observation of recent policy changes on its subject matter, as reflected in the Commission’s policy documents, the EU’s international agreements and declarations by the Member States, leads to the findings of this dissertation. A conflict situation that originated from legal conflicts within the EU, the EU experience of investment protection and state aid regarding intra-EU BITs, provided some lessons to learn for the EU organs. These lessons learned have found expression on a global scale. By incorporating fair competition and state aid policy in international trade the EU is reasserting that it is the EU that decides on state aid law and policy law regarding investment protection. Indeed, the EU is attempting to tame investment protection in such a way that fair competition and investment protection can peacefully coexist in international trade. Ultimately, the interplay of state aid and the EU’s investment policy within the internal market reflects on the external trade relations of both the Member States and the EU through this practice. Thus, state aid law affects and will continue to affect the future of EU investment policy in a global context.
Keywords: EU; European Union; Investment protection; Investments; Policy Law; State aid law

Corporate Social Responsibility and Organizational Performance of Oil Companies in Southern Nigeria - Daubry, Powei Martin (Walden University, 2020)
In this study, the relationship between corporate social responsibility (CSR) activities and organizational performance (OP) of international oil companies (IOCs) operating within the Niger Delta Region of Nigeria was investigated. Grounded on the stakeholder theory, the problem being investigated involved the extent to which dimensions of CSR in terms of centrality, visibility, and voluntary contributions impact measures of OP (relational capital and employees’ commitment) specifically within the oil industry in Nigeria. Data for the study were obtained through a quantitative survey instrument from a sample of a population of individuals (N=270) living in host communities who are impacted by IOC activities in Rivers, Delta, and Bayelsa States. The results of the multiple regression analysis indicated a predictive model F (1, 268) = 774, p < 0.05, and R 2 = .742, which indicated that CSR was positively and significantly correlated with OP. In addition, centrality and voluntary contributions significantly affected OP. Also, centrality and voluntary contributions significantly correlated with employees’ commitment while only voluntary contributions significantly correlated with relational capital. The results of the study corroborated the need for CSR practitioners in the oil industry within the Niger Delta to operate in a socially responsible manner. The implications for positive social change include the potential for policy makers to use the findings to create mutually beneficial relationships that could contribute to resolving persistent adverse issues involving oil exploration and production in the Niger Delta Region by improving the socioeconomic dynamics of the host population, not only in the region, but also throughout Nigeria and similar countries.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Oil companies; Organizational performance

Capital market effects of adoption of IFRS - Opare, Solomon (Victoria University of Wellington, 2020)
This thesis examines the impact of adoption of IFRS (International Financial Reporting Standards) on two aspects of the operation of capital markets. Firstly, the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital. Secondly, the impact of adoption of IFRS on seasoned equity offering (SEO) underperformance. To examine the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital, the study used meta-analysis of empirical studies published since 2000. Meta-analysis provides an objective view of the empirical results, in contrast to narrative reviews, which offer subjective conclusions. From meta-analysis of 55 empirical studies with 1,259 effect sizes, the study finds that IFRS adoption has increased financial reporting comparability, market liquidity, and reduced cost of equity. For cost of debt, a decrease is observed only for voluntary adoption. The meta-regression analysis shows how the results differ across mandatory and voluntary adoption of IFRS and that the measurement choices, type of control variables, study design, and strength of empirical results explain the variation in the observed effect of adoption of IFRS. To examine the impact of adoption of IFRS on SEO underperformance the study analyses a large sample of SEOs from 51 countries over the period 1992-2017. Given that the empirical literature on SEOs has established that information asymmetry contributes to SEO underperformance, it is important to assess whether adoption of IFRS has reduced the uncertainties surrounding SEOs and, thus, subsequent underperformance. The study employs a control sample of non-IFRS adoption countries and applies a difference-in-difference (DiD) design to test for the incremental change for IFRS adoption countries over non-IFRS adoption countries. The study finds that SEO underperformance reduces for IFRS adopters relative to non-IFRS adopters in the post-adoption period. The reduction in SEO underperformance is influenced by increased disclosure, increased comparability, and number of accounting changes. The study also finds that the impact of adoption of IFRS on SEO underperformance exists only for firms in countries with strong enforcement, and is conditional on the implementation credibility of countries. The findings are robust to the application of a different measure of SEO underperformance. Overall, the study suggests that IFRS has had a positive impact on capital markets. However, increased disclosure, comparability, and credible implementation play important roles in realising the benefits of adoption of IFRS. Thus, policymakers of weak enforcement countries are encouraged to strengthen their institutional environment in order to reap the benefits that adoption of IFRS can provide to their capital market.
Keywords: Cost of debt; Cost of equity; Enforcement; Financial reporting comparability; IFRS adoption; Market liquidity; Meta-analysis; SEO underperformance; Seasoned equity offering

Protecting the Industrial Designs of Today and the Future - Samoylov, Vladimir (Victoria University of Wellington, 2020)
This study examines and critiques New Zealand intellectual property protection for industrial designs, taking into account that many New Zealand industrial design owners outsource manufacture of their designs to China. Industrial design, which refers to improving the aesthetics of products to increase their marketability, is evolving conceptually and practically. In New Zealand, copyright and registered design laws each protect, respectively, the visual expression and the “eye appeal” of an original design. As design practices evolve with advances in technology however, it is increasingly evident that industrial design is about more than just visual expression or “eye appeal”. Many designers are not focusing solely on product stylisation and decoration, but on the provision of a more holistic product experience for the consumer. The development process of industrial designs from concept to marketable product is also changing, with many New Zealand industrial design owners employing increasingly efficient design development strategies. The fast-paced, cost-effective infrastructure of China is often utilised by New Zealand businesses for the manufacture of industrial designs. This study therefore sought to determine how to appropriately protect New Zealand industrial designs, in light of: a. foreseeable advances in technology; and b. the fact that many New Zealand industrial designs are manufactured in China. To answer these questions, this study examined and analysed New Zealand’s copyright and registered design laws, taking into account not only existing protections, but also factors that are likely to be of significant relevance in the future, such as the impact on industrial design from developments in 3D printing and virtual reality. The Chinese intellectual property regime for industrial designs was also examined because China is a major trading partner and often, as noted, the locus of manufacture. The study included an empirical investigation, in the form of interviews with designers and design academics as well as legal practitioners specialising in intellectual property law. The input of the interviewees, together with the legal analysis, informed a series of suggestions and recommendations for New Zealand policy and its law-makers regarding how industrial design protection can be improved. A key finding of this study was that existing legal protections do not appropriately protect increasingly holistic designs, as well as new types of designs emerging from developing fields such as virtual reality. In assessing the appropriateness of protection, the interests of industrial design owners were balanced against the public interest in protecting the public domain. It is suggested that to achieve equilibrium copyright law should be expanded to protect design expressions for all senses. Moreover, new categories of copyright protected works should be introduced to accommodate emerging design. The definition of design in registered design law should also be reconceptualised in order to acknowledge new types of designs and evolving design practices. Industrial design owners who outsource manufacturing to China can protect their designs via copyright as well as design patent. However, enforcement of intellectual property protection is unsatisfactory in many areas of China. Therefore, New Zealand industrial design owners should also employ non-legal protection strategies. Interviews with successful businesses, in the course of the empirical investigation for this study, revealed that the leveraging of existing relationships of those with already established operations in China, and intentionally splitting an industrial design’s component parts for manufacture among several factories in different locations, are useful strategies to employ.
Keywords: 3D printing; Artistic Craftsmanship; China; Copyright; Doing business in China; Intellectual property; Multisensory Designs; Propriedade intelectual; Propriété intellectuelle; Registered design; Spare Parts; Virtual Designs; Virtual Reality

The Distributional Effects of Value-Added Taxes in OECD Countries - Thomas, Alastair (Victoria University of Wellington, 2020)
Most OECD countries’ value-added tax (VAT) systems apply reduced VAT rates to a selection of expenditure items in order to achieve distributional goals, and – to a lesser extent – social, cultural and employment-related goals. This thesis investigates the distributional effects of the VAT in OECD countries, and the merits of using reduced VAT rates to achieve distributional goals. The research adopts a microsimulation modelling approach that draws on household expenditure microdata from household budget surveys for an unprecedented 27 OECD countries. A consistent microsimulation methodology is adopted to ensure cross-country comparability of results. Non-behavioural VAT microsimulation models are first built to examine the overall distributional impact of the current VAT systems in each country. The research assesses the competing methodological approaches used in previous studies, highlighting the misleading effect of savings patterns on cross-sectional analysis when VAT burdens are measured relative to income. Measuring VAT burdens relative to expenditure – thereby removing the influence of savings – is found to provide a more reliable picture of the distributional impact of the VAT. On this basis, the VAT is found to be either roughly proportional or slightly progressive in most of the 27 OECD countries examined. Nevertheless, results for a small number of countries (Chile, Hungary, Latvia and New Zealand) highlight that broad-based VAT systems that have few reduced VAT rates or exemptions can produce a small degree of regressivity. Results also show that even a roughly proportional VAT can still have significant equity implications for the poor – potentially pushing some households into poverty. Behavioural VAT microsimulation models are then built for 23 OECD countries to investigate whether reduced VAT rates are an effective way to support poorer households, and whether the use of targeted cash transfers would be more effective. The behavioural microsimulation methodology follows the Linear Expenditure System based approach of Creedy and Sleeman (2006). Complementing this approach, a Quadratic Almost Ideal Demand System (QUAIDS) is estimated specifically for New Zealand, thereby providing the first estimates of a QUAIDS model based on New Zealand data. Simulation results show that, as a whole, the reduced VAT rates present in most OECD countries tend to have a small progressive impact. However, despite this progressivity, reduced VAT rates are shown to be a highly ineffective mechanism for targeting support to poorer households: not only do rich households benefit from reduced rates, but they benefit more in aggregate terms than poor households do. When looking at reduced VAT rates applied to specific products, results are found to vary considerably. Reduced VAT rates specifically introduced to support the poor (such as reduced rates on food consumed at home and domestic utilities) are generally found to have a progressive impact, though rich households still receive a larger aggregate benefit than poor households. In contrast, reduced VAT rates introduced to address non-distributional goals (such as reduced rates on restaurants, hotels, and cultural and social expenditure) often have a regressive impact. Additional simulation results show that an income-tested cash transfer will better target support to poorer households than reduced VAT rates in all countries. Furthermore, even a universal cash transfer is found to better target poorer households than reduced VAT rates. However, results also show that it is very difficult for an income-tested cash transfer to fully compensate all poor households for the removal of reduced VAT rates. This is due to the significant variation in the underlying consumption patterns across households. While a small number of poor households lose out from replacing reduced VAT rates with targeted cash transfers, those that receive support are instead determined by income and family characteristics as opposed to consumption tastes – thereby increasing horizontal equity. Furthermore, many households are lifted out of poverty as revenue previously transferred to richer households is now transferred to poorer households. These results empirically confirm the theoretical expectation that, where available, direct mechanisms (whether via the income tax or benefit system) will better achieve distributional goals than reduced VAT rates. Countries that currently employ reduced VAT rates to achieve distributional goals should therefore consider removing these reduced rates and adjusting their income tax or benefit systems to achieve these distributional goals instead. Countries should also consider removing reduced VAT rates aimed at non-distributional goals where a more effective instrument is available to achieve the particular policy goal. At a minimum, the merits of these reduced VAT rates should be reassessed in light of their negative distributional impact.

Selected legal aspects of liability insurance - Jacobs, Wenette (University of South Africa, 2020)
Liability insurance concerns an insured’s insurance of its legal liability towards a third party for the latter’s loss. This specialised type of insurance is rather neglected in South African insurance law. There is a lack of understanding of the intricacies of liability insurance and its unique challenges. This flows primarily from its complex nature as third-party insurance, which involves legal obligations between multiple parties, and a lack of statutory regulation of the distinctive contractual aspects of liability insurance. Furthermore, limited authority exists on contentious legal aspects as a result of the relatively small number of judicial decisions in this field of law. It is also evident that liability insurance constantly evolves as new grounds of liability emerge and new insurance products develop in response to the changing demands of society. The rise of consumerism and the increase in third-party claims amplify the economic significance of the law of liability insurance in South Africa. A substantial knowledge gap remains in our jurisprudence, irrespective of the recent introduction of new statutory instruments aimed at regulating insurance practice in general. These reforms have not as yet been applied critically to liability insurance, and no specialised legislation in South Africa regulates aspects of this branch of insurance as is the case with microinsurance. The focus in this thesis is on two main issues: the insurer’s duty effectively to indemnify the insured, and the insurer’s defence and settlement of third-party claims brought against the insured. As a subsidiary theme, this thesis analyses legal uncertainties that may persist during pre-contractual negotiations, the liability insurance contract lifecycle, and even after the expiry of the contract. Legal challenges can be addressed by novel and creative application of the national law. Potential solutions can be gleaned from the other progressive jurisdictions reviewed – English and Belgian law. It is evident that this research may prompt Parliament to develop specific rules and regulations for liability insurance contract law. This thesis includes a check list of some of the most important disclosure duties for procuring liability insurance cover, its operation, and claims processes.
Keywords: Claims-made policy; Duty to indemnify; Indemnity insurance; Liability insurance; Liability insurer; Third-party insurance

Investor-state arbitration and African states: a proposal for a Pan-African investment court - Ama, Obiajunwa (Canterbury Christ Church University, 2020)
This thesis proposed for the reform of Africa’s Investor-State Dispute Settlement (ISDS) landscape through the establishment of a Pan-African Investment Court (PAIC) as a mechanism for the resolution of Investor-State Disputes. This proposal is influenced by the findings of my investigation on the functioning of Investor-State Dispute Settlement (ISDS) through the deployment of Investor-State Arbitration to resolve Investor-State Disputes between African states and foreign investors. This research is motivated by the criticisms of the Arbitration mechanism by a broad spectrum of constituencies within international investment law. These criticisms are primarily anchored on the legitimacy crises of ISDS, a dissatisfactory notion that denounces the deployment of the private mechanism and privity of contract ingrained investment arbitration framework to resolve publicly-inclined investor-state disputes. Ancillary to this critical holy grail are further dissatisfactions on the practical functionality of investment arbitration in aspects of high volume of cases against developing states, lack of diversity in the appointment of arbitrators and curtailment of sovereignty of host states through the intrusion of provisions of International Investment Agreements on legitimate internal decision-making powers. Consequently, this thesis investigated the practical functioning of ISDS in African states. After the study of the experiences of Egypt, South Africa and Tanzania; it was found that the legitimacy crises of ISDS also impacts on African states, and does not support their socio-economic and sustainable developmental aspirations. As a remedy, I proposed for a reform to an Investment Court System (ICS) through the establishment of a Pan-African Investment Court (PAIC). An evaluation of this recommendation was conducted that evidenced potential challenges that may mitigate its feasibility, thus leading to the advancement of two secondary reform alternatives vis the reform and retention of the current investor-state arbitration framework and engagement in innovative treaty-making practices by African states. To the best of my knowledge, this thesis has not been previously submitted in any higher institution or published by another person. The contents of this thesis are my ideas. Where the materials of others were used, due acknowledgement and reference was provided. Acknowledgements
Permalink: https://repository.canterbury.ac.uk/item/90873/investor-state-arbitration-and-african-states-a-proposal-for-a-pan-african-investment-court
Keywords: Arbitration; Investment Court System; Investments; Investor-State Dispute Settlement; Investor-state arbitration

Rights on news : expanding copyright on the internet - Furgal, Urszula (European University Institute, 2020)
The internet and digital technologies have irreversibly changed the way we find and consume news. Legacy news organisations, publishers of newspapers, have moved to the internet. In the online news environment, however, they are no longer the exclusive suppliers of news. New digital intermediaries have emerged, search engines and news aggregators in particular. They select and display links and fragments of press publishers’ content as a part of their services, without seeking the news organisations’ prior consent. To shield themselves from exploitation by digital intermediaries, press publishers have begun to seek legal protection, and called for the introduction of a new right under the umbrella of copyright and related rights. Following these calls, the press publishers’ right was introduced into the EU copyright framework by the Directive on Copyright in the Digital Single Market in 2019.
Accepted: 2020-02-20T11:26:15Z
Keywords: Copyright; Digital media; Electronic information resources; Intellectual property; Internet; Propriedade intelectual; Propriété intellectuelle

Re-integration, rehabilitation and return-to-work of disabled workers : a comparative legal enquiry - Gresse, E. (North-West University, 2020)
There are many employment positions in the labour market that could be filled by the disabled of whom most, given the right environment, could be productive in the workplace. However, there are employers who still labour under the misconception that Persons with Disabilities (PWDs) are unqualified and unproductive although their participation in the workplace could contribute to the national economy, while restoring their dignity and social integration. The United Nations Convention on the Rights of Persons with Disabilities (CRPD) entered into force on 3 May 2008. The CRPD is the first international legally binding treaty aimed specifically at protecting the rights of PWDs. It is expected of ratifying States Parties to either amend their domestic existing laws or to enact new legislation in order to meet their obligations, as set out in the CRPD. In 2008, South Africa ratified the CRPD and the Optional Protocol, thus committing itself to the provisions relating to, inter alia, workplace integration. Article 26 of the Convention mandates States Parties to take effective and appropriate measures to enable PWDs to attain and maintain maximum independence, physical, mental, social and vocational ability, and to ensure their social inclusion. Article 27 stipulates, inter alia, that States Parties shall safeguard and promote the realisation of the right to work, including those who incur a disability during the course of employment. Legislation should make provision for, inter alia the following: • enable PWDs to have effective access to general technical and vocational guidance programmes; • placement services and continued vocational training; • promote employment opportunities and career advancement; • assistance in sourcing, obtaining, maintaining and returning to work; and • reasonable accommodation in the workplace as well as vocational and professional rehabilitation. Although the Compensation for Occupational Injuries and Diseases Act 130 of 1993 was amended recently to include rehabilitation, re-integration and return to work (RTW) as part of its objectives, it will be argued that South Africa needs to initiate targeted legislation and policies that make disability management functions mandatory. Employers’ obligations need to be set out clearly in the Act, because, as it stands, the following lacunae exist: • There is no obligation to appoint Case Managers; • Dismissal protection is not provided for; • The regulation of negative incentives to assist with RTW compliance is lacking; and • The roles of different stakeholders in the RTW process require clarification. Without South Africa having an appropriate and detailed RTW framework, ill or injured employees stand the risk of losing their jobs and becoming dependent on family members and/or disability grants. Against this background, a comparative analysis of international and regional law and the RTW practices of two foreign jurisdictions were made. This enabled the author to devise recommendations and identify the roles of the government, employers, employees and Case Managers. The primary objective of this thesis is to determine how and to what extent regional and international standards and RTW programmes in other countries could assist in developing and amending the current legislative and policy framework in South Africa to promote the RTW of disabled employees.
Keywords: Disability management; Persons with Disabilities; Re-integration; Rehabilitation; Return to work

The effectiveness of the adopted OECD transfer pricing dispute resolution mechanisms in an African context - Kekana, Nelson Doctor (University of Pretoria, 2020)
With the developments happening globally that are aimed at curbing base erosion and profit shifting by multinationals, improving the resolution of transfer pricing disputes has been identified as one of the key issues. This thesis investigates the challenges uniquely faced by African countries that militate against the use of the OECD transfer pricing dispute resolution mechanisms. The thesis starts by reflecting on the effect of transfer pricing manipulation by multinational enterprises in Africa in particular. Transfer pricing manipulation is one of the causes of the so-called tax gap, which is, the gap between anticipated and actual revenue collection. The aggression by revenue authorities against transfer pricing manipulation in order to close this gap has triggered a lot of transfer pricing adjustments. These adjustments have resulted in multiple transfer pricing disputes. In the analysis of the adopted OECD dispute resolution mechanisms, the thesis focuses on the effectiveness of the mutual agreement procedure (MAP), the advance pricing arrangement (APA) and the mandatory binding arbitration (MBA). It identifies the problems that result in the failure of or the delay in the resolution of many transfer pricing disputes by analysing the domestic frameworks that exist in four African countries namely: South Africa, Kenya, Uganda and Ghana. The thesis identifies problems such as the absence of a tax treaty network within the African continent, the use of underdeveloped double tax agreements and the lack of commitment from African countries to subscribe to and ratify multilateral conventions. These problems delay or stifle the resolution of tax treaty disputes. They also cause uncertainty for taxpayers and lead to continued tax avoidance by multinational enterprises that essentially avoid paying tax in African countries where the economic activities of these enterprises take place. The thesis also identifies the importance of other OECD supporting tools such as the exchange of tax information in the resolution of transfer pricing disputes. It focuses on tools such as country by country reports, the master file, the local file and simultaneous tax examination as covered by the Multilateral Convention on Mutual Administrative Assistance in Tax Matters. The thesis contributes to the resolution of the identified problems with transfer pricing dispute resolution in Africa by recommending certain improvements that can be effected. These recommendations entail, regarding the MAP, the expansion of tax treaty networks by African countries and the establishment of a Tax Treaty Dispute Resolution Committee by ATAF. Regarding the APA, it is recommended that African countries should sign the multilateral instrument (MLI) and make use of advance tax rulings (ATRs) as alternatives. With respect to the MBA, this thesis recommends that African countries should use optional arbitration by effectively using article 25(4) of the OECD Model tax convention (MTC). It also recommends that African countries must enhance their tax transparency by ratifying multilateral conventions that seek to address international tax co-operation and to improve compliance with transfer pricing documentation requirements in order to make the resolution of transfer pricing disputes more effective.
https://repository.up.ac.za/handle/2263/80889
Keywords: Dispute resolution; Model Tax Convention; OECD; Transfer pricing

Algeria and the African Union - between security and economic integration: a neofunctionalist and regionalist reading - Lamri, Amel (Canterbuy Christ Church University, 2020)
This thesis investigates the process of integration in the African Union (AU), and the reasons behind the slow progress of the AU to achieve the goal of deeper economic integration. In the research I explore the role of an AU member state in the process of African integration: Algeria. The research scrutinises the development of Algerian foreign policy towards the AU and highlights any changes in the Algerian FP attitudes and the reasons behind these changes. Similarly, the research unveils the reality of the decision-making process in this country, and the different agents that influence it. To achieve the main goals of the research, different theoretical choices were elaborated. This resulted in researching European integration theories; Neofunctionalism was, then, selected to study the Algerian development in the making of its foreign policy in general and towards the African Union specifically. Some concepts within the Neofunctionalist thinking were used including the principle of the shift of loyalties, the socialisation process, the spillover system, and the role of interest groups in the process of integration. Moreover, the theory of Regionalism was used to examine the process of integration in the AU discovering new reasons that led to the slow development of economic integration in Africa. Consequently, the research highlights the current obstacles and challenges that have hindered the process of economic integration in the AU, including the poverty of most of the AU member states, the limited financial budget of the Union and the instability of the majority of African countries. Furthermore, the research unveiled the lack of political will towards AU economic integration plans. Hence, this contribution extends beyond the traditional models of explanation, and discusses the situation in AU member states (in this case Algeria) and points to other factors as well such as the weakness of the lobbyist activities and business groups in Algeria specifically and Africa more generally. The thesis, then, focusses on Algeria’s supportive and active status in the AU security sector, highlighting how Algeria has been successful in pushing its own security and antiterrorism agenda to the AU level, thereby demonstrating that integration into the AU is possible, if it is backed by influential member states, and wider coalitions can be built to promote integration and cooperation.
Permalink: https://repository.canterbury.ac.uk/item/8y60y/algeria-and-the-african-union-between-security-and-economic-integration-a-neofunctionalist-and-regionalist-reading
Keywords: Africa Union; Algeria; Intégration régionale

An Empirical Analysis of Private Equity Investment Affecting Enterprise Value - Li, Jianhong (Université de Genève, 2020)
The lack of long-term and stable financial support for SMEs is the fundamental reason why enterprises cannot develop for a long time. At present, the situation of financing difficulties for SMEs is becoming more and more serious. Private equity (PE) investment has emerged as an important financing method. Private equity investment, while broadening the financing channels of SME capital markets, brings advanced management experience to enterprises, which helps enterprises to develop rapidly and effectively. According to the statistics of the Zero2IPO Research Center, the active investment institutions in China's equity market have grown from more than 200 in 2000 to more than 14,000 in 2018, with a total asset under management over RMB 9 trillion. Great progress has been realized in the scale and development of the industry. In addition, with the launch of the GEM in 2009, PE investment industry met new opportunities of development and became popular. At present, the development of China's PE investment business is still at an early stage. Neither relevant policies, laws and regulations nor supporting mechanisms are mature enough. Therefore, researches on China's PE investment business needs to be carried out. In this context, more and more scholars are beginning to focus on the field of PE investment. This paper focuses on whether PE investments can fundamentally increase the enterprise value. The basic theory is sorted out to serve as the theoretical basis for this study. Through a systematic analysis, this paper draws out 4paths of PE investment affecting enterprises, which are the influence on technological innovation, corporate governance activities, dividend distribution decision and earnings management, respectively. And through empirical analysis, it finds the empirical basis of the impact of PE investment on enterprise value, and investigates how PE investments affect enterprise value based on the difference in investment characteristics such as investment duration and whether the investment is joint or not. This paper conducts an empirical test by selecting the listed companies of the Shenzhen Stock Exchange GEM in 2015-2018 as sample. The results show that the investment of PE firm will significantly increase the value of the target enterprise. This paper makes a detailed analysis of sample data. The conclusion of the study is that private equity investment will have a significant impact on the value of target enterprises. Private equity investment plays an important role in the modern governance structure of small and medium-sized enterprises in China This paper enriches the existing literature and provides constructive suggestions for the health development of the PE investment market. 中小企业缺乏长期稳定的资金来源是企业无法长久发展的根本性原因，目前 中小企业融资难的形势越来越严峻，私募股权投资作为一种重要的融资手段应运 而生。私募股权投资在拓宽中小企业资本市场融资渠道的同时，给企业带来先进的 管理经验，有助于企业快速并有效的发展。据清科研究中心的统计数据显示，中国 股权市场活跃的投资机构已由 2000 年的 200 多家发展到 2018 年的 1.4 万多家，管 理资本量超过 9 万亿人民币，行业规模和发展实现了质的飞跃。此外，随着 2009 年创业板的推出，私募股权投资行业的发展业迎来了新的希望和契机，私募股权投 资业务开始盛行。目前，我国私募股权投资业务的发展还处于早期阶段，无论是从 政策还是法律法规再到配套机制，都还不够健全。因此，对我国私募股权投资业务 的研究亟需开展，在此背景下，越来越多的学者开始关注私募股权投资这一领域。 本文研究的重点是私募股权投资是否能够根本上提升企业价值。本文首先对 基础理论进行了梳理，以此作为研究的理论依据，而后论述了私募股权投资对被投 资企业价值影响的理论分析，。本文通过系统的理论分析得出了私募股权投资影响 企业的路径，并通过实证分析，得到私募股权投资对企业价值的影响的实证依据， 并且从投资期限和是否联合投资等投资特征的差异性，深入研究私募股权投资对 企业价值的影响方式。本文通过选取深圳证券交易所创业板 2015-2018 年的上市企 业作为样本，进行了实证检验，并得出以下研究结论:私募股权投资的参与会显著 提升目标企业的价值，同时，私募股权投资的期限越长、联合投资机构的数量越多， 目标企业的价值也会越高。 本文基于理论又结合实际，对样本数据进行了分析，研究的结论是私募股权投 资会对被投资企业的价值产生显著影响。私募股权投资对于我国中小企业的现代 化治理结构起到了完善作用。本文的研究结果丰富了现有文献，对私募股权投资市 场健康发展提出了建设性的建议。
Keywords: Enterprise Value; Investment Term; PE Investment

Corporate social responsibility and executive personality - Li, Xin (Simon Fraser University, 2020)
My dissertation investigates two streams of managerial accounting literature; specifically, corporate social responsibility (CSR) and executive personality. Paper 1 focuses on whether companies strategically engage in CSR practices to retain employees. Using a difference-in-differences design, I find that an increase in the enforcement of non compete agreements (which enhances a firm’s ability to retain employees) deteriorates CSR performance. Paper 2 extends prior literature and links managerial risk tolerance and firms’ CSR performance. The empirical result of Paper 2 shows that pilot CEOs are less likely to exhibit better CSR performance. Paper 3 examines the spillover effect of managerial risk tolerance along the supply chain. Specifically, I follow Paper 2 to use the pilot status of CEOs to proxy for the customers’ risk tolerance level. Overall, the results support a negative association between customer risk tolerance and supplier investment efficiency, and customer companies ran by pilot CEOs leads to supplier investment inefficiency. Each chapter is designed to be self-contained and provides a more detailed discussion of the research question and contribution.
Keywords: CEO; CSR performance; Corporate Social Responsibility; Non-compete enforceability; Pilot; RSE; Risk tolerance; Supplier investment efficiency

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
https://ora.ox.ac.uk/objects/uuid:c2dd717f-e53b-4ab6-b848-c089b70adec2
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation

Portability of social security benefits of circular migrant workers in selected SADC member states - Masoebe, P. (North-West University, 2020)
The issue of portability of social security benefits is a daunting issue facing migrant workers in both Southern Africa and the world in general. In the Southern African Development Community region migration seems to be driven mainly by the need to attain economic freedom. The fact of the matter is that migrant workers from Lesotho and Swaziland who work and have worked in South Africa do play a major role in boosting these countries’ economies. Another issue that cannot be ignored is the fact that circular migration as a phenomenon is unlikely to come to an end any time soon in this part of the world. This means that social security benefits of migrant workers and its portability should be an issue that is dealt with cautiously and speedily, especially in terms of looking at the millions of unclaimed social security benefits reported each year by social security funds and schemes in South Africa. While examining the extent to which selected SADC member states, namely Lesotho, Swaziland and South Africa, have undertaken to combat this issue, international and regional instruments that have a bearing on social security rights are analysed and the realisation is that in as much as these do provide for social security rights and portability of benefits thereof, a lack of ratification and implementation play a vital role in achieving efficient portability of these rights. Although South Africa, as the largest migrant-receiving country in the SADC region, does provide for the right to social security in its Constitution, the fragmented nature of its social security framework, together with other factors such lack of information, exploitation by employers, distances travelled to lay claims and a non-existent social security adjudication system means that migrant workers are normally left with lack of redress when their contracts of employment reach an end. On the other hand, Swaziland and Lesotho, as migrant-sending countries, do not even have provisions in their constitutions that specifically deal with the right to social security. This means that citizens who work abroad do not have sufficient social security coverage in either country, as well as in South Africa as a host country. Consequently, multilateral and bilateral agreements on social security are pivotal in addressing this issue of unclaimed social security benefits as they go a long way in making sure that migrant workers are provided with adequate social security protection and coverage as a whole. Migrant sending countries also need to undertake unilateral initiatives to guarantee that their citizens are adequately protected in this specific sphere of social security. Examples are further drawn from the best practices of different regions in the world, namely the Southeast Asian Nations Region, Caribbean Community and Common Market and the Southern Common Market. The above-mentioned regions have established multilateral social security agreements that seek social security protection for migrant workers who play an undeniable role in their economies. Bilateral social security agreements between Zambia and Malawi, together with the one between Sweden and Philippines, are taken into consideration as best practices that Lesotho, Swaziland and South Africa may draw examples from when drawing up and concluding their own bilateral social security agreements. The Philippines’ unilateral initiatives are also discussed and hailed as the best practices that migrant-sending countries such as Lesotho and Swaziland may further draw examples from. The Philippines has developed strategies aimed at guaranteeing social protection for its migrant workers abroad and further makes sure that it enters into bilateral agreements with any country that receives services from its citizens. While the need to conclude multilateral and bilateral agreements on social security cannot be denied, there is also a need for migrant-sending countries to come up with unilateral initiatives to lessen the burden on migrant-receiving countries in this social security domain. Sectors such as the mining sector should also have mining-specific agreements that specifically deal with issues related to migrant mine workers. Lack of statistics of migrant workers moving in and out of South Africa has also been labelled as one of the reasons halting access and portability of social security benefits; hence there is a need to develop a data-base aimed at keeping track of all migrant workers, retired and otherwise. Migrant workers who seek redress regarding access of their unclaimed or unpaid social security benefits also have to be provided with comprehensive protection from the courts of law. This therefore means that an adjudication system should be established to deal with social security woes so that those seeking redress have adequate legal support.
Keywords: Labour and social protection; Migrant workers; Multilateral agreements; SADC; SADEC; Social protection; Social security; Sécurité sociale; Travailleur migrant

The liquidation process and unsecured creditors: using the resulting trust to restore the balance - Stubbins, Matthew (Canterbury Christ Church University, 2020)
Ever since the formation of limited companies became permissible, unsecured creditors have faced a Sisyphean struggle to regularly recover substantial levels of the debts owed to them should corporate creditors enter insolvency. These low recovery rates result in many issues for lenders, including large losses, and in some cases, the insolvency of the lender themselves. The causes of these low return rates are long established and clearly demarcated. They consist of the existence and widespread use of security interests - which remove the majority of the company’s assets upon insolvency occurring - and the statutory priority of distribution, which ensures that parties other than the unsecured creditors have their debts discharged first by the liquidator from the already insufficiently resourced asset pool. English insolvency law has sought to provide some protection to the unsecured creditors through the anti-deprivation and personal liability provisions of the Insolvency Act 1986, which are intended to protect the integrity of the insolvent company’s asset pool. However, as concluded by this thesis, these provisions fail to afford adequate protection as a consequence of their substantive, evidential and remedial limitations, potentially resulting in the distributable assets being misappropriated and out of the reach of unsecured creditors. This thesis therefore analyses the limitations of the existing anti-deprivation and personal liability provisions before concluding as to how and why they fail to adequately protect unsecured creditors. This is done through a doctrinal and theoretical analysis of the provisions, before these conclusions are then tested empirically in two case studies. Given the inadequate protection provided by the Insolvency Act, this thesis then analyses the resulting trust – on which little analysis has been conducted in the context of insolvency – to determine whether it is capable of assisting unsecured creditors to increase their liquidation return rates. This increase is achieved through returning assets beneficially owned by the company to the company, or by preventing parties from becoming unsecured creditors in the first place by removing assets beneficially owned by them from the company. This analysis too will adopt a doctrinal and theoretical methodology, and it is concluded that the resulting trust is able to assist should the requisite factual matrices occur.
Permalink: https://repository.canterbury.ac.uk/item/8z4x2/the-liquidation-process-and-unsecured-creditors-using-the-resulting-trust-to-restore-the-balance
Keywords: Insolvabilité; Insolvency; Insolvência; Liquidation

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework

The adaptation of China’s maritime arbitration system to international legal norms and practice - Xuan, Yan (The University of Queensland, 2020)
Maritime transport is essential to the world’s economy and maritime arbitration plays a crucial role in maritime dispute resolution. Nowadays, many coastal jurisdictions have set up their own maritime arbitration institutions such as those in the US, the UK, Germany, Australia, China, Japan, Hong Kong, and Singapore. Building a national world-advanced maritime arbitration system as soon as possible to suit China’s rapid developments in shipping and international trading does not permit of any delay. How should China improve her laws, rules and institutions, including those for the enforcement of maritime arbitration awards, having regard to leading international maritime arbitration systems? It is posited that selective adaptation from the successful experience of other maritime arbitration systems is the most convenient and effective way to achieve such a goal. This adaptation will follow from a comprehensive and comparative study of the maritime arbitration laws, rules and the maritime arbitration institutions, including the laws relating to the enforcement of maritime arbitration awards, from these main global maritime arbitration centres in order to make China’s maritime arbitration more competitive at the international level. This thesis does not purport to cover every research field relating to maritime arbitration. Instead, as previously stated, it will focus only on the comparative study of some selected key issues of international commercial arbitration among the selected jurisdictions. A comprehensive study of international commercial arbitration or international maritime law is not the subject of this thesis. It should be noted further that this research basically concentrates on the practical problems of maritime arbitration practices, rather than taking an overly theoretical approach. The thesis selects the UK, the US, Singapore and Hong Kong as the target jurisdictions for comparison. Through selective comparative analysis of the key issues of maritime arbitration systems in the selected jurisdictions, which are internationally recognised as significant by many arbitration scholars, this thesis proposes that all these issues could conveniently be categorised into four key criteria; namely, fairness, confidentiality, efficiency and enforceability. It follows that the adaptations of the Chinese maritime arbitration system should mainly focus on these four criteria, as these are the most critical factors for the development of Chinese maritime arbitration system. Moreover, these four criteria should also have significance for other underdeveloped maritime arbitration systems. Also, based on these four key criteria, the thesis provides some specific suggestions on how the Chinese maritime arbitration system can be adapted to reflect other selected jurisdictions in the respects of some key issues of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; Droit maritime; Efficiency; Enforceability; Fairness; Maritime arbitration

What drives individual decision-making of Foreign Direct Investments (FDI) to Sub-Saharan Africa - Yusuf, Mukhtar Abubakar (Case Western Reserve University, 2020)
This dissertation examines a multiplicity of factors that influence at the microeconomic level the level of Foreign Direct Investment (FDI). The main objective of the dissertation is to empirically explore and validate the effect of a select set of individual-level perceptual factors on FDI decisions. Given the paucity of research on the topic in comparison to macroeconomic studies of investment inflows between regions and countries, we conduct the study as a mixed-method study. The study consists of three interconnected empirical studies. The first seeks to identify the presence of factors that shape an individual’s decisions on FDI inflows. The two following ones seek to validate the effects of these factors on the individual decision maker's propensity to invest in a specific country. The first study belongs to a qualitative strand and answers the following research question: What are the investor’s critical perceptual factors and experiences that influence their FDI decisions? The study participants consisted of 30 foreign investors, the government’s Ministries, Departments, and Agencies (MDAs), and the Nigerian investors in the diaspora. The paper finds that on the supply side, several key FDI perception factors influence decision-making. On the demand side, there are four attractors and four repellents that influence potential investors' decisions. In the quantitative strand of the study, we offer the following questions: (1) To what extent do investment decision perception impact foreign direct investment (FDI) inflows? And (2) To what extent do the investors from Europe and North America and investors from Asia and Africa (the West and the East) influence what factors matter in foreign direct investment (FDI) decisions? The samples consist of 269 individuals from the private sector, both in Nigeria and in the diaspora that participated in the survey. I use structural equation modeling to find that Return on Investment (ROI), Security/Personal Safety, and Investment Facilitation Services have a significant direct effect on the FDI decisions. A post hoc exploratory analysis indicates positive relationships between Ease of Doing Business and Investment Promotion and FDI are significant for investors from the investors from Europe and North America as well as the negative impact of Corruption. In contrast, the positive relationship between Return-On-Investment and FDI is more substantial for investors from East Asia and Africa. The next part of the quantitative strand investigates (1) to what extent investment promotion services and Investment Facilitation effects in the receiving country shape positive investment decision outcomes, and (2) to what extent investment perceptions and related decisions vary across industry groups facing different investment horizons and risk levels. The analysis indicates that the Investment Promotion services significantly mediate Corruption Perceptions and Investment Facilitation services. And Investment Facilitation does moderate the effect of Investment Promotion. The exploratory industry-level analysis reveals that the effects of Return On Investment to FDI decisions and Security to FDI decisions significantly differ across Infrastructure-Mining/Services, Services/Agriculture-Manufacturing, and Agriculture-Manufacturing/Infrastructure-Mining industries suggesting significant Industry-level effects. Generally, these findings reveal much more refined and complex dynamics of FDI inflows and how individual investor’s perceptions shape them. Specifically, the results provide deeper insights into the investor’s risk perceptions that arise in a particular country. This depends on holistic perceptions of the country’s economic, political, and social environment, and also the investor’s time horizon and risk preferences signaling significant individual and situational differences in how decision-makers approach FDI.
Keywords: Corruption; Ease-of-doing-business; FDI; FDI attractors; Foreign direct investment; Investment decision-making; Investments; Nigerian Investment Promotion Commission; Perception; ROI; Return on investment; Security

The enforceability of interim measures granted by an emergency arbitrator in international commercial arbitration - Zhang, Junmin (ProefschriftMaken, 2020)
The emergency arbitrator mechanism makes interim measures possible for parties involved in international commercial arbitration before the constitution of arbitral tribunals under urgent situations. However, with the development of the emergency arbitrator mechanism, the enforceability of interim measures made by an emergency arbitrator is questioned. This uncertainty leads to the hesitation of legal practitioners to apply the emergency arbitrator mechanism in practice. The research conducted two comparisons between different arbitration rules and between arbitration laws in jurisdictions. After discussing the legal status of an emergency arbitrator, the legal criteria to render interim measures, the potential barriers for the enforceability, and possible harmonization, it concluded that the interim measures granted by an emergency arbitrator in international commercial arbitration should be enforced and even harmonized through mandatory and non-mandatory methods.
Keywords: Arbitrage; Arbitragem; Arbitral Tribunal; Arbitration; Arbitration Law; Arbitrator; Commercial Arbitration; Emergency arbitrator; Enforceability; Interim measures; International commercial arbitration